Lithium ion battery using crosslinked separator
Patent Information
- Application Number
- CN202211419385.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-07-31
- Filing Date
- 2019-10-11
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2039-10-11
AI Technical Summary
然而,只要采用聚烯烃作为树脂,则即使改良分隔件的机械上的微多孔结构,性能提高也是有限度的
[0376] According to the present invention, it is possible to provide an energy storage device and its assembly kit that can take into account both the low-temperature shut-off function and the high-temperature rupture-resistant film of the separator for the energy storage device, and also suppress the generation of unmelted resin aggregates in its manufacturing process, thereby contributing to productivity and economy, and thus having good cycle characteristics and high safety.
Smart Images

Figure CN115642366B_ABST
Abstract
Description
[0001] This application is a divisional application of the application filed on October 11, 2019, with application number 201980007742.8 and invention title "Lithium-ion Battery Using Crosslinking Separators". Technical Field
[0002] This invention relates to separators for energy storage devices and their crosslinking methods, energy storage device assembly kits, and methods for manufacturing energy storage devices. Background Technology
[0003] Microporous membranes are widely used as separation or selective permeation membranes and separation materials for various substances. Examples of their applications include microfiltration membranes, separators for fuel cells and capacitors, substrates for functional membranes that incorporate functional materials into their pores to achieve new functions, and separators for energy storage devices. Among these, polyolefin microporous membranes are suitable for use as separators in lithium-ion batteries, which are widely used in laptops, mobile phones, and digital cameras.
[0004] To ensure battery safety, the separator must balance the activation of the shut-off function with the increase in membrane rupture temperature. For example, Patent Document 1 describes adjusting the high-order physical properties of polyolefin resin, an essential component of separators for lithium-ion batteries. Furthermore, as shown in Patent Document 2, it is known that within specific crystallinity and gelation rate regions, the separator can suppress heat generation caused by short circuits within the battery while maintaining its shut-off function, and on the other hand, it can prevent membrane rupture (breakdown above 170°C) even when high temperatures are locally generated within the battery cell, thereby ensuring battery safety. More specifically regarding Patent Documents 1 and 2, it has been experimentally discovered that by constructing silane crosslinking portions (gelation structures) within polyolefin separators, high-temperature membrane rupture resistance can be achieved.
[0005] For example, Patent Documents 1-6 describe silane crosslinking structures formed by contacting a silane-modified polyolefin separator with water. Patent Document 8 describes a crosslinking structure formed by ring-opening of norbornene using irradiation with ultraviolet light, electron beams, etc. Patent Document 9 describes a separator whose insulating layer comprises a crosslinked structure, such as a (meth)acrylic acid copolymer or a styrene-butadiene rubber adhesive. Furthermore, for example, a separator has been proposed in which the thickness ratio of an A layer with blocking properties to a B layer containing aramid resin and inorganic materials is adjusted to a specified range (see Patent Document 11).
[0006] Regarding components used in lithium-ion batteries, positive electrode, negative electrode materials, electrolyte, and separators are employed. Among these components, the separator, due to its characteristic as an insulating material, is required to be inactive against electrochemical reactions or surrounding components. On the other hand, the negative electrode material for lithium-ion batteries was developed from the outset using a technique that suppresses electrolyte decomposition on the negative electrode surface by forming a solid electrolyte interface (SEI) through chemical reactions during initial charging (Non-Patent Document 1). Furthermore, cases have been reported where, even when polyolefin resin is used as the separator, oxidation reactions occur on the positive electrode surface under high voltage, leading to blackening and surface degradation of the separator.
[0007] Based on the above ideas, materials for separators in energy storage devices often employ chemical structures that are inactive to electrochemical or other chemical reactions. Therefore, the development and practical application of microporous membranes made from polyolefins have been widely pursued. However, as long as polyolefins are used as the resin, even improvements in the mechanical microporous structure of the separator are limited in terms of performance enhancement. For example, the thermal stability of separators above the melting point of polyolefins, or the electronegativity of the olefin units, results in insufficient affinity or liquid retention with the electrolyte, thus failing to meet the permeability requirements of Li ions or their solvated ion clusters within the separator.
[0008] Thus, due to the aforementioned limitations, the current approach cannot be expected to meet the high-speed charge-discharge or thermal stability requirements of modern battery development.
[0009] Existing technical documents
[0010] Patent documents
[0011] Patent Document 1: Japanese Patent Application Publication No. 9-216964
[0012] Patent Document 2: International Publication No. 97 / 44839
[0013] Patent Document 3: Japanese Patent Application Publication No. 11-144700
[0014] Patent Document 4: Japanese Patent Application Publication No. 11-172036
[0015] Patent Document 5: Japanese Patent Application Publication No. 2001-176484
[0016] Patent Document 6: Japanese Patent Application Publication No. 2000-319441
[0017] Patent Document 7: Japanese Patent Application Publication No. 2017-203145
[0018] Patent Document 8: Japanese Patent Application Publication No. 2011-071128
[0019] Patent Document 9: Japanese Patent Application Publication No. 2014-056843
[0020] Patent Document 10: Japanese Patent Application Publication No. 10-261435
[0021] Patent Document 11: Japanese Patent Application Publication No. 2007-299612
[0022] Patent Document 12: International Publication No. 2010 / 134585
[0023] Patent Document 13: Japanese Patent Application Publication No. 2016-072150
[0024] Non-patent literature
[0025] Non-Patent Document 1: Lithium-ion Secondary Batteries (2nd Edition), published by Nikkan Kogyo Shimbun.
[0026] Non-Patent Literature 2: Basic Polymer Chemistry, Tokyo Chemical Doujin Publishing Summary of the Invention
[0027] The problem the invention aims to solve
[0028] In recent years, there has been a focus on increasing the output and energy density of lithium-ion secondary batteries for mobile devices and automotive applications. On the other hand, there is a demand for miniaturized battery cells and stable cycle discharge / charge performance over long-term use. Therefore, the separators used need to be thin films (e.g., 15 μm or less) and of high quality (e.g., having uniform physical properties and being free of resin aggregates). Furthermore, the level of battery safety is becoming increasingly stringent. As described in Patent Documents 1 and 2, requirements include a shut-off function and high-temperature film-breaking resistance. There is a need to develop resin compositions and manufacturing methods for separators that can be stably produced. Relatedly, a shut-off temperature lower than 150°C is desirable, while a higher film-breaking temperature is desirable.
[0029] For example, the method described in Patent Document 3 uses a crosslinking catalyst masterbatch during the extrusion process to carry out the crosslinking reaction of silane-modified polyethylene in the extruder, but resin aggregates are generated, reducing the uniformity of the physical properties of the separator. To address this method, Patent Documents 4, 5, and 6 describe methods that incorporate a plasticizer extraction process or a silane adhesive crosslinking process, control the gelation rate of the resin membrane, or allow uncrosslinked resin to be formed in hot water and then dehydrated. Furthermore, Patent Document 7 proposes a heat-resistant resin microporous membrane that exhibits excellent low thermal shrinkage, low fluidity, and resistance to melt fracture by adjusting the gelation rate of the polyolefin microporous membrane, the storage modulus at temperatures between 40°C and 250°C in dynamic viscoelasticity (DMA) measurements, the maximum shrinkage rate based on thermomechanical analysis (TMA), and the amount of free radicals measured by electron spin resonance (ESR).
[0030] Furthermore, regarding the separator for energy storage devices, from the perspective of balancing dimensional stability, maintaining the shut-off function and improving the membrane breaking temperature, an inorganic porous layer containing inorganic particles such as calcined kaolin and boehmite and a resin binder has been proposed to be disposed on at least one side of the surface of a polyolefin microporous membrane (Patent Documents 12, 13).
[0031] However, the method shown in Patent Document 4 cannot fully carry out the silane crosslinking reaction, making it difficult to obtain a high-temperature puncture-resistant film. The plasticizer extraction process described in Patent Documents 3 and 4 uses a tin(II)-based crosslinking catalyst, which allows the crosslinking reaction to proceed, but there is a risk of catalyst residue remaining afterward.
[0032] The heat-resistant resin microporous membrane described in Patent Document 7 is obtained by coating a dry-pored membrane with a photopolymerizable coating liquid. Furthermore, Example 5 of Patent Document 7 adds a low-molecular-weight silane coupling agent, such as γ-methacryloyloxypropyltrimethoxysilane, to the porous membrane. However, assuming the low-molecular-weight silane coupling agent is used in a wet pore-forming process, it is foreseeable that the low-molecular-weight silane coupling agent readily reacts or binds with the plasticizer used for pore-forming, rather than binding with the resin of the porous membrane. Consequently, batteries using the heat-resistant resin microporous membrane as a separator, as described in Patent Document 7, exhibit poor cycle characteristics. Moreover, during long-term use, unpredictable side reactions may be induced within the battery, potentially reducing battery safety.
[0033] Furthermore, the coating layer described in Patent Document 7 is formed by coating a resin-based porous membrane with a compound having polymerizable functional groups and then conducting a cross-linking reaction through external stimulation. Therefore, it is foreseeable that liquid will infiltrate a portion of the resin-based porous membrane during the coating layer application, and a mixing region between the coating layer and the resin-based porous membrane will be formed near the interface after the cross-linking reaction. While this results in good TMA heat shrinkage performance, it is also foreseeable that the battery cycle characteristics will decrease due to clogging of the resin-based porous membrane, or that the melt-off (shutdown) performance will decrease due to melting of the resin-based porous membrane. Moreover, in the composite microporous membrane obtained by the method described in Patent Document 7, a small amount of free radical compounds were detected by ESR. Due to these residues, when the composite microporous membrane is assembled into a battery, it will undergo free radical reactions with other components, particularly with the electrolyte, and a chain reaction leading to electrolyte decomposition is foreseeable, which is believed to significantly degrade battery performance.
[0034] Furthermore, the microporous membranes and separators described in Patent Documents 1, 2, and 7 lack research on the application of inorganic porous layers containing inorganic particles and resin binders on their surfaces. Existing separators with inorganic porous layers on microporous membranes appear to have increased membrane rupture temperatures on the temperature-resistance curves of energy storage devices. However, in reality, resin can sometimes dissolve from the microporous membrane into the inorganic porous layer, thus anticipating a reduction in membrane weight as a whole and a consequent decrease in stress resistance. Therefore, while the multilayer porous membranes described in Patent Documents 12 and 13 possess both polyolefin microporous membranes and inorganic porous layers, there is room for further research into balancing low-temperature shut-off functionality and high-temperature rupture resistance as separators for energy storage devices, or improving the cycle characteristics and battery penetration safety of energy storage devices.
[0035] Furthermore, batteries using separators as described in Patent Documents 3-7 have poor cycle characteristics. In addition, during long-term use, unpredictable side reactions may be induced within the battery, potentially reducing battery safety.
[0036] In conventional molded products such as hot water pipes, tin (Sn)-based catalysts are added to the extruder during the extrusion process. On the other hand, the wet manufacturing process for separators in energy storage devices typically includes extrusion / sheet forming, stretching, plasticizer extraction (porization), heat treatment, and winding. Therefore, if silane crosslinking is promoted within the extruder during the sheet forming process, gelation will result in defects, and stretching of the silane-crosslinked polyolefin in the subsequent stretching process is difficult. Therefore, further research is needed on new separators for energy storage devices with suitable manufacturing processes.
[0037] Furthermore, the crosslinking methods described in Patent Documents 1-6, 8, and 9 are all performed during the separator film-making process or intermittently immediately after the separator is manufactured. Therefore, after the crosslinking structure described in Patent Documents 1-6, 8, and 9 is formed, the separator must be coated and slit. This increases internal stress during subsequent lamination / winding processes with the electrodes, sometimes causing the manufactured battery to deform. For example, if the crosslinking structure is formed by heating, the internal stress of the separator with this crosslinking structure may increase at room temperature or room temperature.
[0038] Furthermore, if cross-linking structures are formed by irradiation with light such as ultraviolet rays or electron beams, the irradiation may sometimes be uneven, resulting in heterogeneous cross-linking structures. This is believed to be because the periphery of the crystalline portion of the resin constituting the separator is easily cross-linked by electron beams.
[0039] It should be noted that Patent Document 10 describes a technique for improving the cycle characteristics of lithium-ion secondary batteries by adding succinimide or similar substances to the electrolyte. However, the technique described in Patent Document 10 does not improve cycle characteristics by specifying the structure of the separator.
[0040] Furthermore, the separator for the energy storage device described in Patent Documents 1, 2, and 11 still has room for improvement in terms of enhancing the performance of the energy storage device.
[0041] In view of the above-mentioned problems, the present invention aims to provide a separator for a storage device that can take into account both shutdown function and high-temperature rupture resistance, ensure the safety of the storage device, output and / or cycle stability, and a new crosslinking method or assembly kit or manufacturing method of the storage device suitable for its manufacturing process.
[0042] Solution for solving the problem
[0043] The above problems are solved through the following technical means. [1]
[0045] A separator for an energy storage device, characterized in that the separator comprises a silane-modified polyolefin, and when the separator comes into contact with an electrolyte, a silane crosslinking reaction of the silane-modified polyolefin is initiated. [2]
[0047] According to the separator for the energy storage device described in claim 1, the aforementioned silane-modified polyolefin is not a masterbatch resin containing a dehydration condensation catalyst that crosslinks the silane-modified polyolefin. [3]
[0049] According to the separator for the energy storage device described in claim 1 or 2, the separator for the energy storage device further comprises polyethylene in addition to the aforementioned silane-modified polyolefin. [4]
[0051] According to the separator for the energy storage device described in item 3, the mass ratio of the aforementioned silane-modified polyolefin to the aforementioned polyethylene (mass of silane-modified polyolefin / mass of polyethylene) is 0.05 / 0.95 to 0.40 / 0.60. [5]
[0053] A separator for an energy storage device, comprising 5-40% by mass of a silane-modified polyolefin and 60-95% by mass of a polyolefin other than the aforementioned silane-modified polyolefin, wherein the energy storage modulus change ratio (R) is defined by the following formula (1). ΔE’ The ratio is 1.5 to 20 times.
[0054] R ΔE’ =E' S / E' j (1)
[0055] In the formula, E' j The energy storage modulus of the aforementioned energy storage device separator measured at 160°C to 220°C before the crosslinking reaction of the aforementioned silane-modified polyolefin, and E' S The energy storage modulus of the aforementioned energy storage device separator, after crosslinking the aforementioned silane-modified polyolefin, was measured at 160°C to 220°C, and is E'. j or E' S The conditions for determining the energy storage modulus E' are specified by the following components (i) to (iv).
[0056] (i) Dynamic viscoelasticity was measured under the following conditions:
[0057] • Measuring apparatus used: RSA-G2 (manufactured by TA Instruments)
[0058] • Sample film thickness: 5 μm to 50 μm
[0059] • Measurement temperature range: -50~225℃
[0060] • Heating rate: 10℃ / min
[0061] • Measurement frequency: 1Hz
[0062] • Deformation mode: Linear tension mode
[0063] Initial static tensile load: 0.5 N
[0064] • Initial gap distance (at 25℃): 25mm
[0065] • Automatic strain adjustment: Enabled (range: amplitude value 0.05~25%, sinusoidal load 0.02~5N).
[0066] (ii) The aforementioned static tensile load refers to the midpoint between the maximum and minimum stress under each periodic motion, and the aforementioned sinusoidal load refers to the vibration stress centered on the aforementioned static tensile load.
[0067] (iii) The aforementioned sinusoidal stretching mode refers to measuring the aforementioned vibration stress while performing periodic motion with a fixed amplitude of 0.2%. Under the aforementioned sinusoidal stretching mode, the aforementioned vibration stress is measured by changing the gap distance and the aforementioned static tensile load in such a way that the difference between the aforementioned static tensile load and the aforementioned sinusoidal load is within 20%. When the aforementioned sinusoidal load is less than 0.02N, the aforementioned vibration stress is measured by increasing the aforementioned amplitude value in such a way that the aforementioned sinusoidal load is within 5N and the increase in the aforementioned amplitude value is within 25%.
[0068] (iv) Calculate the storage modulus E' based on the relationship between the obtained sinusoidal load and amplitude value and the following formula:
[0069] σ * =σ0·Exp[i(ωt+δ)]、
[0070] ε * =ε0·Exp(iωt),
[0071] σ * =E * ·ε *
[0072] E * =E'+iE”
[0073] (where σ is in the formula) * Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * E': complex modulus; E”: energy storage modulus; E”: loss modulus
[0074] Vibration stress: sinusoidal load / initial cross-sectional area
[0075] Static tensile load: The load at the point of minimum vibration stress (the point of minimum gap distance within each period) during each cycle.
[0076] Sine wave load: the difference between the measured vibration stress and the static tensile load. [6]
[0078] A separator for an energy storage device, comprising 5-40% by mass of a silane-modified polyolefin and 60-95% by mass of a polyolefin other than the aforementioned silane-modified polyolefin, wherein the loss modulus change ratio (R) is defined by the following formula (3). ΔE” The ratio is 1.5 to 20 times.
[0079] R ΔE” =E” S / E” j (3)
[0080] In the formula, E” j The loss modulus of the aforementioned energy storage device separator measured at 160°C to 220°C before the crosslinking reaction of the aforementioned silane-modified polyolefin, and E” S The loss modulus of the aforementioned energy storage device separator after crosslinking reaction of the aforementioned silane-modified polyolefin was measured at 160°C to 220°C, and is E”. j or E” S The conditions for determining the loss modulus E are specified by the following (i) to (iv).
[0081] (i) Dynamic viscoelasticity was measured under the following conditions:
[0082] • Measuring apparatus used: RSA-G2 (manufactured by TA Instruments)
[0083] • Sample film thickness: 5 μm to 50 μm
[0084] • Measurement temperature range: -50~225℃
[0085] • Heating rate: 10℃ / min
[0086] • Measurement frequency: 1Hz
[0087] • Deformation mode: Linear tension mode
[0088] Initial static tensile load: 0.5 N
[0089] • Initial gap distance (at 25℃): 25mm
[0090] • Automatic strain adjustment: Enabled (range: amplitude value 0.05~25%, sinusoidal load 0.02~5N).
[0091] (ii) The aforementioned static tensile load refers to the midpoint between the maximum and minimum stress under each periodic motion, and the aforementioned sinusoidal load refers to the vibration stress centered on the aforementioned static tensile load.
[0092] (iii) The aforementioned sinusoidal stretching mode refers to measuring the aforementioned vibration stress while performing periodic motion with a fixed amplitude of 0.2%. Under the aforementioned sinusoidal stretching mode, the aforementioned vibration stress is measured by changing the gap distance and the aforementioned static tensile load in such a way that the difference between the aforementioned static tensile load and the aforementioned sinusoidal load is within 20%. When the aforementioned sinusoidal load is less than 0.02N, the aforementioned vibration stress is measured by increasing the aforementioned amplitude value in such a way that the aforementioned sinusoidal load is within 5N and the increase in amplitude value is within 25%.
[0093] (iv) Calculate the loss modulus E” based on the relationship between the obtained sinusoidal load and amplitude value and the following formula:
[0094] σ * =σ0·Exp[i(ωt+δ)]、
[0095] ε * =ε0·Exp(iωt),
[0096] σ * =E * ·ε *
[0097] E * =E'+iE”
[0098] (where σ is in the formula) * Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * E': complex modulus; E”: energy storage modulus; E”: loss modulus
[0099] Vibration stress: sinusoidal load / initial cross-sectional area
[0100] Static tensile load: The load at the point of minimum vibration stress (the point of minimum gap distance within each period) during each cycle.
[0101] Sine wave load: the difference between the measured vibration stress and the static tensile load. [7]
[0103] A separator for an energy storage device is characterized in that, when the separator comes into contact with an electrolyte, a silane crosslinking reaction of a silane-modified polyolefin occurs. [8]
[0105] A separator for an energy storage device, comprising 5-40% by mass of a silane-modified polyolefin and 60-95% by mass of a polyolefin other than the aforementioned silane-modified polyolefin, wherein the mixed energy storage modulus ratio (R) is defined by the following formula (2). E’mixThe ratio is 1.5 to 20 times.
[0106] R E’mix =E' a / E'0 (2)
[0107] In the formula, E' a E'0 is the energy storage modulus of the separator used in the aforementioned energy storage device, measured at 160°C to 220°C, and E'0 is the energy storage modulus of the separator used in the energy storage device without the aforementioned silane-modified polyolefin, measured at 160°C to 220°C, and E'0 is... a The conditions for determining the energy storage modulus E' of E'0 are specified by the following (i) to (iv).
[0108] (i) Dynamic viscoelasticity was measured under the following conditions:
[0109] • Measuring apparatus used: RSA-G2 (manufactured by TA Instruments)
[0110] • Sample film thickness: 5 μm to 50 μm
[0111] • Measurement temperature range: -50~225℃
[0112] • Heating rate: 10℃ / min
[0113] • Measurement frequency: 1Hz
[0114] • Deformation mode: Linear tension mode
[0115] Initial static tensile load: 0.5 N
[0116] • Initial gap distance (at 25℃): 25mm
[0117] • Automatic strain adjustment: Enabled (range: amplitude value 0.05~25%, sinusoidal load 0.02~5N).
[0118] (ii) The aforementioned static tensile load refers to the midpoint between the maximum and minimum stress under each periodic motion, and the aforementioned sinusoidal load refers to the vibration stress centered on the aforementioned static tensile load.
[0119] (iii) The aforementioned sinusoidal stretching mode refers to measuring the aforementioned vibration stress while performing periodic motion with a fixed amplitude of 0.2%. Under the aforementioned sinusoidal stretching mode, the aforementioned vibration stress is measured by changing the gap distance and the aforementioned static tensile load in such a way that the difference between the aforementioned static tensile load and the aforementioned sinusoidal load is within 20%. When the aforementioned sinusoidal load is less than 0.02N, the aforementioned vibration stress is measured by increasing the aforementioned amplitude value in such a way that the aforementioned sinusoidal load is within 5N and the increase in the aforementioned amplitude value is within 25%.
[0120] (iv) Calculate the storage modulus E' based on the relationship between the obtained sinusoidal load and amplitude value and the following formula:
[0121] σ * =σ0·Exp[i(ωt+δ)]、
[0122] ε * =ε0·Exp(iωt),
[0123] σ * =E * ·ε *
[0124] E * =E'+iE”
[0125] (where σ is in the formula) * Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * E': complex modulus; E”: energy storage modulus; E”: loss modulus
[0126] Vibration stress: sinusoidal load / initial cross-sectional area
[0127] Static tensile load: The load at the point of minimum vibration stress (the point of minimum gap distance within each period) during each cycle.
[0128] Sine wave load: the difference between the measured vibration stress and the static tensile load. [9]
[0130] A separator for an energy storage device, comprising 5-40% by mass of a silane-modified polyolefin and 60-95% by mass of a polyolefin other than the aforementioned silane-modified polyolefin, wherein the mixed loss modulus ratio (R) is defined by the following formula (4). E”mix The ratio is 1.5 to 20.0 times.
[0131] R E”mix =E” a / E”0 (4)
[0132] In the formula, E” a E”0 is the loss modulus of the separator for the aforementioned energy storage device measured at 160°C to 220°C, and E”0 is the loss modulus of the separator for the energy storage device without the aforementioned silane-modified polyolefin measured at 160°C to 220°C, and E”0 is... a The conditions for determining the loss modulus E” of E”0 are specified by the following (i) to (iv).
[0133] (i) Dynamic viscoelasticity was measured under the following conditions:
[0134] • Measuring apparatus used: RSA-G2 (manufactured by TA Instruments)
[0135] • Sample film thickness: 5 μm to 50 μm
[0136] • Measurement temperature range: -50~225℃
[0137] • Heating rate: 10℃ / min
[0138] • Measurement frequency: 1Hz
[0139] • Deformation mode: Linear tension mode
[0140] Initial static tensile load: 0.5 N
[0141] • Initial gap distance (at 25℃): 25mm
[0142] • Automatic strain adjustment: Enabled (range: amplitude value 0.05~25%, sinusoidal load 0.02~5N).
[0143] (ii) The aforementioned static tensile load refers to the midpoint between the maximum and minimum stress under each periodic motion, and the aforementioned sinusoidal load refers to the vibration stress centered on the aforementioned static tensile load.
[0144] (iii) The aforementioned sinusoidal stretching mode refers to measuring the aforementioned vibration stress while performing periodic motion with a fixed amplitude of 0.2%. Under the aforementioned sinusoidal stretching mode, the aforementioned vibration stress is measured by changing the gap distance and the aforementioned static tensile load in such a way that the difference between the aforementioned static tensile load and the aforementioned sinusoidal load is within 20%. When the aforementioned sinusoidal load is less than 0.02N, the aforementioned vibration stress is measured by increasing the aforementioned amplitude value in such a way that the aforementioned sinusoidal load is within 5N and the increase in amplitude value is within 25%.
[0145] (iv) Calculate the loss modulus E” based on the relationship between the obtained sinusoidal load and amplitude value and the following formula:
[0146] σ * =σ0·Exp[i(ωt+δ)]、
[0147] ε * =ε0·Exp(iωt),
[0148] σ * =E * ·ε *
[0149] E * =E'+iE”
[0150] (where σ is in the formula) * Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * E': complex modulus; E”: energy storage modulus; E”: loss modulus
[0151] Vibration stress: sinusoidal load / initial cross-sectional area
[0152] Static tensile load: The load at the point of minimum vibration stress (the point of minimum gap distance within each period) during each cycle.
[0153] Sine wave load: the difference between the measured vibration stress and the static tensile load.
[10]
[0155] According to the separator for the energy storage device described in claim 8 or 9, wherein the separator for the energy storage device that does not contain the aforementioned silane-modified polyolefin is a microporous membrane made of silane-unmodified polyolefin with a gelation degree of 0% or more and 10% or less.
[11]
[0157] A separator for an energy storage device comprises 5-40% by mass of silane-modified polyolefin and 60-95% by mass of polyolefin other than the aforementioned silane-modified polyolefin. The transition temperature between the rubbery flat region and the crystalline melting flow region in the temperature change of the energy storage modulus of the aforementioned separator is 135°C to 150°C.
[12]
[0159] A separator for an energy storage device, the separator comprising a polyolefin microporous membrane.
[0160] In the solid viscoelasticity test of the aforementioned separator for energy storage devices at temperatures ranging from -50°C to 250°C,
[0161] The minimum energy storage modulus is 1.0 MPa to 10 MPa, and the maximum energy storage modulus is 100 MPa to 10,000 MPa.
[0162] The minimum loss modulus ranges from 0.1 MPa to 10 MPa, and the maximum loss modulus ranges from 10 MPa to 10,000 MPa.
[0163] The conditions for determining the aforementioned solid viscoelasticity using the aforementioned storage modulus and loss modulus are specified by the following (i) to (iv):
[0164] (i) Dynamic viscoelasticity was measured under the following conditions:
[0165] • Measuring apparatus used: RSA-G2 (manufactured by TA Instruments)
[0166] • Sample film thickness: 200μm~400μm (wherein, if the film thickness of a single sample is less than 200μm, multiple samples are stacked to make the total thickness within the range of 200μm~400μm for dynamic viscoelasticity determination.)
[0167] • Measurement temperature range: -50℃~250℃
[0168] • Heating rate: 10℃ / min
[0169] • Measurement frequency: 1Hz
[0170] • Deformation mode: Linear tension mode
[0171] Initial value of static tensile load: 0.2N
[0172] • Initial gap distance (at 25℃): 10mm
[0173] • Automatic strain adjustment: Disabled;
[0174] (ii) The aforementioned static tensile load refers to the midpoint between the maximum and minimum stress under each periodic motion, and the aforementioned sinusoidal load refers to the vibration stress centered on the aforementioned static tensile load.
[0175] (iii) The aforementioned sinusoidal stretching mode refers to measuring the aforementioned vibration stress while performing periodic motion with a fixed amplitude of 0.1%. Under the aforementioned sinusoidal stretching mode, the aforementioned vibration stress is measured by changing the gap distance and the aforementioned static tensile load in such a way that the difference between the aforementioned static tensile load and the aforementioned sinusoidal load is within 5%. When the aforementioned sinusoidal load is less than 0.1N, the aforementioned static tensile load is fixed at 0.1N to measure the aforementioned vibration stress.
[0176] (iv) Calculate the aforementioned energy storage modulus and loss modulus based on the obtained relationship between the sinusoidal load and the amplitude value, and the following formula:
[0177] σ * =σ0·Exp[i(ωt+δ)]、
[0178] ε * =ε0·Exp(iωt),
[0179] σ * =E * ·ε *
[0180] E * =E'+iE”
[0181] In the formula, σ * Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * E': complex modulus; E”: energy storage modulus; E”: loss modulus
[0182] Vibration stress: sinusoidal load / initial cross-sectional area
[0183] Static tensile load: The load at the point of minimum vibration stress (the point of minimum gap distance within each period) during each cycle.
[0184] Sine wave load: the difference between the measured vibration stress and the static tensile load.
[13]
[0186] A separator for an energy storage device comprising a polyolefin microporous membrane, wherein in a solid viscoelasticity test of the aforementioned separator from the membrane softening transition temperature to the membrane rupture temperature, the average storage modulus is 1.0 MPa to 12 MPa and the average loss modulus is 0.5 MPa to 10 MPa.
[14]
[0188] According to the separator for the energy storage device described in item 13, in the aforementioned solid viscoelasticity test, the membrane softening transition temperature is 140°C to 150°C, and the membrane rupture temperature is 180°C or higher.
[15]
[0190] The separator for an energy storage device according to any one of claims 12 to 14 comprises silane-modified polyolefin and polyolefins other than the aforementioned silane-modified polyolefin.
[16]
[0192] The separator for the energy storage device according to claim 15 comprises 5% to 40% by mass of silane-modified polyolefin and 60% to 95% by mass of polyolefin other than the aforementioned silane-modified polyolefin.
[17]
[0194] A separator for an energy storage device, characterized in that the separator comprises a polyolefin.
[0195] The aforementioned polyolefins have one or more functional groups, and
[0196] After being incorporated into an energy storage device, (1) a condensation reaction occurs between the aforementioned functional groups, or (2) the aforementioned functional groups react with the chemical substances inside the aforementioned energy storage device, or (3) the aforementioned functional groups react with other types of functional groups, thereby forming a cross-linked structure.
[18]
[0198] According to the separator for the energy storage device described in claim 17, the aforementioned chemical substance is any one of the electrolyte, electrolyte solution, electrode active material, additives or their decomposition products contained in the aforementioned energy storage device.
[19]
[0200] A separator for an energy storage device, the separator comprising a polyolefin having an amorphous cross-linked structure obtained by cross-linking the amorphous portion of the aforementioned polyolefin.
[20]
[0202] According to the separator for the energy storage device described in item 19, wherein the aforementioned separator for the energy storage device is defined by the hybrid energy storage modulus ratio (R) as shown in the following formula (1). E’X The ratio is 1.5 to 20 times.
[0203] R E’X =E' Z / E' Z0 (1)
[0204] In the formula, E' Z The energy storage modulus is the energy storage modulus measured in the temperature range of 160°C to 300°C after the cross-linking reaction of the aforementioned separator for the energy storage device is carried out within the energy storage device.
[0205] E' Z0 The energy storage modulus is measured in the temperature range of 160°C to 300°C before the aforementioned energy storage device is assembled into the aforementioned energy storage device using the separator. [twenty one]
[0207] According to the separator for the energy storage device described in item 19 or 20, wherein the aforementioned separator for the energy storage device is defined by the mixed loss modulus ratio (R) as shown in the following formula (3). E”X The ratio is 1.5 to 20 times.
[0208] R E”X =E” Z / E” Z0 (3)
[0209] In the formula, E” Z The loss modulus is the value measured in the temperature range of 160°C to 300°C after the crosslinking reaction of the aforementioned separator for the energy storage device is carried out within the energy storage device.
[0210] E” Z0 The loss modulus is measured in the temperature range of 160°C to 300°C before the aforementioned energy storage device is assembled into the aforementioned energy storage device using the separator. [twenty two]
[0212] The separator for an energy storage device according to any one of claims 19 to 21, wherein the aforementioned amorphous portion is selectively cross-linked. [twenty three]
[0214] According to any one of items 17 to 22, the separator for the energy storage device, wherein the aforementioned separator for the energy storage device is defined by the hybrid energy storage modulus ratio (R) as shown in the following formula (2). E’mix The ratio is 1.5 to 20 times.
[0215] R E’mix =E' / E'0 (2)
[0216] {In the formula, E' is the energy storage modulus measured at 160℃~300℃ when the separator for the aforementioned energy storage device has an amorphous cross-linked structure, and}
[0217] E'0 is the energy storage modulus of the aforementioned energy storage device separator without an amorphous cross-linked structure, measured at 160°C to 300°C. [twenty four]
[0219] According to any one of items 17 to 23, the separator for the energy storage device is defined by the following formula (4) for the mixed loss modulus ratio (R). E”mix The ratio is 1.5 to 20 times.
[0220] R E”mix =E” / E”0 (4)
[0221] {In the formula, E” is the loss modulus measured at 160℃~300℃ when the separator for the aforementioned energy storage device has an amorphous cross-linked structure, and}
[0222] E”0 is the loss modulus of the aforementioned energy storage device separator without an amorphous cross-linked structure, measured at 160°C to 300°C.
[25]
[0224] The separator for an energy storage device according to any one of claims 17 to 24, wherein the aforementioned polyolefin is polyethylene.
[26]
[0226] The separator for an energy storage device according to any one of claims 17 to 25, wherein the aforementioned polyolefin is a functionalized polyolefin or a polyolefin obtained by copolymerizing monomers having functional groups.
[27]
[0228] The separator for an energy storage device according to any one of claims 17 to 26, wherein the aforementioned crosslinking structure is formed by a reaction of any of the bonds selected from covalent bonds, hydrogen bonds, or coordination bonds.
[28]
[0230] According to item 27, the separator for an energy storage device, wherein the aforementioned reaction by means of a covalent bond is at least one selected from the group consisting of the following reactions (I) to (IV):
[0231] (I) Condensation reaction of multiple identical functional groups;
[0232] (II) Reactions between multiple different functional groups;
[0233] (III) Chain condensation reaction between functional groups and electrolyte; and
[0234] (IV) Reaction of functional groups with additives.
[29]
[0236] According to item 27, the separator for the energy storage device, wherein...
[0237] The aforementioned reaction involving coordinate bonds is the following reaction (V):
[0238] (V) A reaction in which multiple identical functional groups cross-link with metal ions via coordination bonds.
[30]
[0240] According to the separator for the energy storage device described in claim 28, the aforementioned reactions (I) and / or (II) are catalyzed and promoted by chemical substances inside the energy storage device.
[31]
[0242] According to the separator for the energy storage device described in item 28, the aforementioned reaction (I) is a condensation reaction of multiple silanol groups.
[32]
[0244] According to the separator for the energy storage device as described in claim 28, wherein the aforementioned reaction (IV) is a nucleophilic substitution reaction, nucleophilic addition reaction or ring-opening reaction of the compound Rx constituting the separator for the energy storage device and the compound Ry constituting the additive, wherein the aforementioned compound Rx has a functional group x and the aforementioned compound Ry has a connecting reaction unit y1.
[33]
[0246] According to the separator for the energy storage device described in item 32, wherein...
[0247] The aforementioned reaction (IV) is a nucleophilic substitution reaction.
[0248] The functional group x of the aforementioned compound Rx is selected from at least one of the groups consisting of -OH, -NH2, -NH-, -COOH, and -SH, and
[0249] The linking reaction unit y1 of the aforementioned compound Ry is at least two of the following groups: CH3SO2-, CF3SO2-, ArSO2-, CH3SO3-, CF3SO3-, ArSO3-, and monovalent groups represented by formulas (y1-1) to (y1-6) below.
[0250]
[0251] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0252]
[0253] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0254]
[0255] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0256]
[0257] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0258]
[0259] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0260]
[0261] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[34]
[0263] The separator for the energy storage device according to claim 32 or 33, wherein...
[0264] The aforementioned reaction (IV) is a nucleophilic substitution reaction.
[0265] The aforementioned compound Ry, in addition to the aforementioned connecting reaction unit y1, also has a chain-like unit y2, and
[0266] The aforementioned chain unit y2 is at least one of the group consisting of divalent groups selected from the following formulas (y2-1) to (y2-6):
[0267]
[0268] In the formula, m is an integer from 0 to 20, and n is an integer from 1 to 20.
[0269]
[0270] In the formula, n is an integer from 1 to 20.
[0271]
[0272] In the formula, n is an integer from 1 to 20.
[0273]
[0274] In the formula, n is an integer from 1 to 20.
[0275]
[0276] {In the formula, X is an alkylene or aryl group having 1 to 20 carbon atoms, and n is an integer from 1 to 20.}
[0277]
[0278] In the formula, X is an alkylene or aryl group having 1 to 20 carbon atoms.
[0279] And n is an integer from 1 to 20.
[35]
[0281] According to the separator for the energy storage device described in item 32, wherein...
[0282] The aforementioned reaction (IV) is a nucleophilic addition reaction.
[0283] The functional group x of the aforementioned compound Rx is selected from at least one of the groups consisting of -OH, -NH2, -NH-, -COOH, and -SH, and
[0284] The linking reaction unit y1 of the aforementioned compound Ry is at least one selected from the group consisting of the groups shown in formulas (Ay1-1) to (Ay1-6) below:
[0285]
[0286] {In the formula, R is a hydrogen atom or a monovalent organic group.}
[0287]
[36]
[0289] According to the separator for the energy storage device described in item 32, wherein...
[0290] The aforementioned reaction (IV) is a ring-opening reaction.
[0291] The functional group x of the aforementioned compound Rx is selected from at least one of the groups consisting of -OH, -NH2, -NH-, -COOH, and -SH, and
[0292] The connecting reactive unit y1 of the aforementioned compound Ry consists of at least two groups as shown in the following formula (ROy1-1):
[0293]
[0294] {In the formula, each X is independently a hydrogen atom or a monovalent substituent.}
[37]
[0296] According to the separator for the energy storage device described in item 29, in the following reaction (V), the aforementioned metal ion is selected from Zn. 2+ Mn 2+ Co 3+ Ni 2+ and Li + At least one of the groups.
[38]
[0298] A separator for an energy storage device comprises a silane-modified polyolefin, has a first porous layer (layer A) capable of forming a cross-linked structure and a second porous layer (layer B) comprising inorganic particles, and the heat shrinkage rate at 150°C after forming the aforementioned cross-linked structure is more than 0.02 times and less than 0.91 times the heat shrinkage rate at 150°C before forming the aforementioned cross-linked structure.
[39]
[0300] According to the separator for the energy storage device as described in claim 38, the aforementioned cross-linking structure in the aforementioned layer A is formed by an acid, alkali, swelling, or a compound generated within the energy storage device.
[40]
[0302] A separator for an energy storage device, comprising:
[0303] Microporous membranes containing silane-modified polyolefins, and
[0304] An inorganic porous layer comprising inorganic particles and a resin binder is disposed on at least one side of the aforementioned microporous membrane.
[41]
[0306] According to the separator for the energy storage device as described in claim 40, the content of the aforementioned inorganic particles in the aforementioned inorganic porous layer is 5% to 99% by weight.
[42]
[0308] According to the separator for the energy storage device as described in claim 40 or 41, the content of the aforementioned silane-modified polyolefin in the aforementioned microporous membrane is 0.5% to 40% by weight.
[43]
[0310] The separator for an energy storage device according to any one of claims 40 to 42, wherein the aforementioned inorganic particles are selected from at least one of the following: alumina (Al2O3), silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, cerium oxide, yttrium oxide, zinc oxide, iron oxide, silicon nitride, titanium nitride, boron nitride, silicon carbide, aluminum hydroxide (AlO(OH)), talc, kaolinite, dickite, perlite, halloysite, pyrophyllite, montmorillonite, sericite, mica, magnesia chlorite, bentonite, asbestos, zeolite, diatomite, quartz sand, and glass fiber.
[44]
[0312] The separator for an energy storage device according to any one of claims 40 to 43, wherein the glass transition temperature (Tg) of the aforementioned resin adhesive is -50°C to 100°C.
[45]
[0314] According to any one of claims 40 to 44, the separator for the energy storage device, when the aforementioned separator for the energy storage device comes into contact with the electrolyte, initiates the silane crosslinking reaction of the aforementioned silane-modified polyolefin.
[46]
[0316] The separator for the energy storage device according to any one of items 40 to 45, wherein...
[0317] When the aforementioned inorganic porous layer is removed from the separator of the aforementioned energy storage device for measurement, the change ratio of the energy storage modulus (R) is defined by the following formula (1A). △E’ The ratio is 1.5 to 20 times.
[0318] R △E’ =E' S / E' j (1A)
[0319] In the formula, E' j The energy storage modulus of the aforementioned energy storage device separator measured at 160°C to 220°C before the crosslinking reaction of the aforementioned silane-modified polyolefin, and E' SThe energy storage modulus of the separator for the aforementioned energy storage device, after crosslinking the aforementioned silane-modified polyolefin, was measured at 160°C to 220°C.
[0320] and / or the loss modulus change ratio (R) defined by the following formula (1B) △E The ratio is 1.5 to 20 times:
[0321] R △E” =E” S / E” j (1B)
[0322] In the formula, E” j The loss modulus of the aforementioned energy storage device separator measured at 160°C to 220°C before the crosslinking reaction of the aforementioned silane-modified polyolefin, and E” S The loss modulus of the aforementioned energy storage device separator after crosslinking the aforementioned silane-modified polyolefin was measured at 160°C to 220°C.
[47]
[0324] The separator for the energy storage device according to any one of items 40 to 46, wherein...
[0325] When the aforementioned inorganic porous layer is removed from the separator of the aforementioned energy storage device for measurement, the hybrid energy storage modulus ratio (R) defined by the following formula (2A) is... E’mix The ratio is 1.5 to 20 times.
[0326] R E’mix =E' / E'0 (2A)
[0327] {In the formula, E' is the energy storage modulus of the aforementioned separator for energy storage devices measured at 160℃~220℃, and E'0 is the energy storage modulus of the separator for energy storage devices without the aforementioned silane-modified polyolefin measured at 160℃~220℃.}
[0328] and / or the mixed loss modulus ratio (R) defined by the following formula (2B) E”mix The ratio is 1.5 to 20 times.
[0329] R E”mix =E” / E”0 (2B)
[0330] {In the formula, E” is the loss modulus of the aforementioned separator for energy storage devices measured at 160℃~220℃, and E”0 is the loss modulus of the separator for energy storage devices without the aforementioned silane-modified polyolefin measured at 160℃~220℃.}
[48]
[0332] According to any one of items 40 to 47, the transition temperature between the rubbery flat region and the crystalline melting flow region in the temperature change of the energy storage modulus of the aforementioned energy storage device separator is 135°C to 150°C.
[49]
[0334] An energy storage device includes electrodes, a separator for an energy storage device as described in any one of claims 1 to 48, and a non-aqueous electrolyte.
[50]
[0336] An energy storage device includes a separator comprising polyethylene and an electrolyte or additive, wherein functionalized polyethylene or functionalized graft copolymer polyethylene reacts with a chemical substance contained in the electrolyte or the additive to form a cross-linked structure.
[51]
[0338] A method for manufacturing a separator for an energy storage device, comprising the method for manufacturing a separator for an energy storage device as described in any one of claims 1 to 50, including the following steps:
[0339] (1) Sheet forming process: The mixture of silane-modified polyolefin, polyethylene and plasticizer is extruded, cooled and solidified to form a sheet, thus obtaining a sheet;
[0340] (2) Stretching process: stretching the aforementioned sheet along at least one uniaxial direction to obtain a stretched material;
[0341] (3) A porous body forming process, wherein the plasticizer is extracted from the aforementioned stretched material in the presence of an extraction solvent, thereby porousening the aforementioned stretched material to form a porous body; and
[0342] (4) Heat treatment process, the aforementioned porous body is subjected to heat treatment.
[52]
[0344] A method for manufacturing a separator for an energy storage device includes the following steps:
[0345] (1) Sheet forming process: silane-modified polyolefin, polyethylene and plasticizer are extruded into sheets using an extruder, cooled and solidified, and processed into sheet-shaped bodies;
[0346] (2) Stretching process: The aforementioned sheet-shaped body is biaxially stretched at a magnification ratio of 20 times or more and 250 times or less to form a stretched object;
[0347] (3) Porous body forming process: extracting the plasticizer from the aforementioned stretched material to form a porous body;
[0348] (4) Heat treatment process: The aforementioned porous body is subjected to heat treatment, and stretched and relaxed along the width direction to obtain a heat-treated porous body.
[0349] (8B) Coating process, forming an inorganic porous layer containing inorganic particles and resin binder on at least one side of the aforementioned heat-treated porous body to form a silane crosslinking precursor;
[0350] (9) Assembly process: The electrode and the aforementioned silane crosslinking precursor laminate or its winding, as well as the non-aqueous electrolyte, are housed in the outer shell, so that the aforementioned silane crosslinking precursor comes into contact with the aforementioned non-aqueous electrolyte.
[53]
[0352] An energy storage device assembly kit, comprising the following two elements:
[0353] (1) A housing containing an electrode and a separator for an energy storage device as described in any one of items 1 to 48; and
[0354] (2) A container that contains non-aqueous electrolyte.
[54]
[0356] According to the energy storage device assembly kit of claim 53, the aforementioned non-aqueous electrolyte contains a fluorine (F)-containing lithium salt.
[55]
[0358] The energy storage device assembly kit according to claim 53 or 54, wherein the aforementioned non-aqueous electrolyte comprises lithium hexafluorophosphate (LiPF6).
[56]
[0360] The energy storage device assembly kit according to any one of claims 53 to 55, wherein the aforementioned non-aqueous electrolyte is an acid solution and / or an alkaline solution.
[57]
[0362] A method for manufacturing an energy storage device includes the following steps;
[0363] The process of preparing the energy storage device assembly kit as described in any one of items 53 to 56, and
[0364] The process of initiating the silane crosslinking reaction of silane-modified polyolefin by contacting the aforementioned energy storage device separator in element (1) of the aforementioned energy storage device assembly kit with the aforementioned non-aqueous electrolyte in element (2).
[58]
[0366] The method for manufacturing the energy storage device according to claim 57 further includes the following steps:
[0367] The process of connecting lead terminals to the aforementioned electrodes of element (1), and
[0368] The process involves performing at least one charge-discharge cycle.
[59]
[0370] A method for manufacturing an energy storage device, which is a method for manufacturing an energy storage device using a separator comprising a polyolefin.
[0371] The aforementioned polyolefin contains one or more functional groups, and the method includes the following crosslinking steps:
[0372] (1) to cause a condensation reaction between the aforementioned functional groups, or (2) to cause the aforementioned functional groups to react with the chemical substances inside the aforementioned energy storage device, or (3) to cause the aforementioned functional groups to react with other types of functional groups, thereby forming a cross-linked structure.
[60]
[0374] According to the method for manufacturing the energy storage device described in claim 59, the aforementioned crosslinking process is carried out at a temperature of 5°C to 90°C.
[0375] The effects of the invention
[0376] According to the present invention, it is possible to provide an energy storage device and its assembly kit that can take into account both the low-temperature shut-off function and the high-temperature rupture-resistant film of the separator for the energy storage device, and also suppress the generation of unmelted resin aggregates in its manufacturing process, thereby contributing to productivity and economy, and thus having good cycle characteristics and high safety.
[0377] Furthermore, according to the present invention, the cross-linking structure can be formed without being present during or immediately after the film-forming process. This suppresses the increase in internal stress of the separator and deformation of the energy storage device after fabrication, and / or allows the separator to acquire a cross-linking structure even without the use of high energy sources such as light irradiation or heating, reducing uneven cross-linking. Moreover, according to the present invention, the cross-linking structure is formed not only inside the separator but also between the separator and the electrode or between the separator and the solid electrolyte interface (SEI). This improves the strength between the multiple components of the energy storage device, suppresses gaps between the electrode and the separator caused by the expansion and contraction of the electrode during charging and discharging of the energy storage device, and significantly improves long-term cycle stability. Attached Figure Description
[0378] Figure 1 This is an example of a graph used to illustrate the relationship between temperature and storage modulus, comparing the storage modulus of a standard membrane and a cross-linked membrane in the temperature range of -50℃ to 225℃, showing the transition temperature between the rubbery flat region and the crystalline melting flow region.
[0379] Figure 2 This is an example of a graph used to illustrate the relationship between temperature and loss modulus, comparing the loss modulus of a standard film and a cross-linked film within a temperature range of -50°C to 225°C, showing the transition temperature between the rubbery flat region and the crystalline melting flow region.
[0380] Figure 3 This is a graph showing the relationship between temperature and resistance of an energy storage device having the separator obtained in Embodiment I-1.
[0381] Figure 4 These are graphs used to illustrate the relationship between temperature, gap distance, energy storage modulus and loss modulus in the viscoelasticity measurement of separators for energy storage devices, and exemplify graph (a) of Example II-1 and graph (b) of Comparative Example II-1.
[0382] Figure 5 This is a graph used to determine the membrane softening transition temperature based on the first derivative of temperature, gap distance, and gap displacement in the viscoelasticity measurement of separators for energy storage devices, and exemplifies the graph (a) of Example II-1 and the graph (b) of Comparative Example II-1.
[0383] Figure 6 This is a schematic diagram illustrating a higher-order structure of a crystalline polymer, which consists of crystalline lamellar (crystalline) parts, amorphous parts, and intermediate layers between them.
[0384] Figure 7 This is a schematic diagram used to illustrate the crystal growth of polyolefin molecules.
[0385] Figure 8 This is a strain-crystal subdivision ratio plot showing the changes in X-ray crystal structure during tensile fracture testing of a membrane according to one embodiment of the present invention.
[0386] Figure 9 This is an example of a graph used to illustrate the relationship between temperature and storage modulus, comparing the storage modulus of a standard membrane and a cross-linked membrane in the temperature range of -50°C to 310°C, showing the transition temperature between the rubbery flat region and the crystalline melting flow region.
[0387] Figure 10 This is an example of a graph used to illustrate the relationship between temperature and loss modulus, comparing the loss modulus of a standard film and a cross-linked film within a temperature range of -50°C to 310°C, showing the transition temperature between the rubbery flat region and the crystalline melting flow region.
[0388] Figure 11 It is a silane-modified polyolefin raw material 1 obtained using polyolefins. 1 H-NMR spectrum (a) and 13 C-NMR spectrum (b).
[0389] Figure 12 It is silane-modified polyolefin raw material 2 obtained using polyolefin. 1 H-NMR spectrum (a) and 13 C-NMR spectrum (b).
[0390] Figure 13 This is the pre-crosslinking state of the separator obtained in Example I-1. 1 H-NMR spectrum (a) and 13 C-NMR spectrum (b). Detailed Implementation
[0391] The specific embodiments of the present invention (hereinafter referred to as "embodiments") will be described in detail below. It should be noted that the present invention is not limited to the following embodiments, and various modifications can be made within the scope of its spirit.
[0392] In this specification, "~" refers to the values at both ends of the range as the upper and lower limits. Furthermore, in this specification, the upper and lower limits of a numerical range can be combined arbitrarily. For example, a preferred upper limit of a numerical range can be combined with a more preferred lower limit, and vice versa.
[0393] It should be noted that in this specification, "on" and "formed on the surface of" do not mean that the positional relationship of each component is limited to "directly above". For example, the descriptions "layer B formed on layer A" and "layer B formed on the surface of layer A" do not exclude the inclusion of any layer between layer A and layer B that does not belong to either of them.
[0394] The characteristics of the microporous membrane described below can be measured after removing the layers other than the microporous membrane (e.g., inorganic porous layers) from the separator of the energy storage device.
[0395] <Separator for energy storage devices>
[0396] One aspect of this invention is a separator for an energy storage device (hereinafter also referred to as "separator"). Since separators need to possess both insulation and ion permeability, they generally include paper, nonwoven fabrics made of polyolefins, or microporous membranes made of resins, which are insulating materials with porous structures. Particularly in lithium-ion batteries, microporous membranes made of polyolefins, capable of constructing separators with resistance to oxidation-reduction degradation and a dense and uniform porous structure, are preferred.
[0397] Here, a microporous membrane refers to a membrane (thin film) formed from a porous body, and its average pore size is preferably 10 nm or more and 500 nm or less, more preferably 30 nm or more and 100 nm or less.
[0398] If the energy storage device includes a separator, the separator can be removed from the energy storage device.
[0399] <First, Second, Third, Fourth and Fifth Implementation Methods>
[0400] The separator of the first embodiment comprises a silane-modified polyolefin, and other polyolefins may also be included, depending on preference. When the separator of the first embodiment comes into contact with the electrolyte, a silane crosslinking reaction of the silane-modified polyolefin contained in the separator begins. Since the separator of the first embodiment can undergo crosslinking of the silane-modified polyolefin when in contact with the electrolyte, the timing of the crosslinking can be controlled. Therefore, the crosslinking reaction can be carried out in the manufacturing process of the energy storage device without it occurring in the manufacturing process of the separator.
[0401] The separator of the second embodiment is characterized in that a silane crosslinking reaction of the silane-modified polyolefin occurs upon contact with the electrolyte. In the second embodiment, regardless of whether the separator contains silane-modified polyolefin, the location of the residual silane-modified polyolefin, or whether the silane crosslinking reaction occurs initially, sequentially, or continuously upon contact with the electrolyte, it is acceptable as long as the silane crosslinking reaction is observed upon contact with the electrolyte. Through the silane crosslinking reaction of the silane-modified polyolefin that occurs upon contact with the electrolyte by the separator of the second embodiment, the crosslinking time point can be controlled regardless of the manufacturing or usage process of the separator.
[0402] The separators of the first and second embodiments can promote cross-linking reactions when electrolyte is injected into the outer casing containing the separator, thus avoiding manufacturing defects in their manufacturing process and achieving safety and high output of the energy storage device in the manufacturing process of the energy storage device. From the perspective of the components contained in the separator and the timing of the cross-linking reaction, it is preferable to start the silane cross-linking reaction of the silane-modified polyolefin when the separator is mixed or in contact with the electrolyte.
[0403] The separator in the third embodiment comprises 5-40% by mass of silane-modified polyolefin and 60-95% by mass of polyolefin other than the aforementioned silane-modified polyolefin. Regarding the viscoelasticity measurement described in the examples (Version 1), the storage modulus change ratio (R) is defined by the following formula (1). ΔE’ The ratio is 1.5 to 20 times.
[0404] R ΔE’ =E' S / E' j (1)
[0405] In the formula, E' j The energy storage modulus of the separator for an energy storage device measured at 160℃~220℃ before crosslinking reaction of silane-modified polyolefin, and E' S The energy storage modulus of a separator for an energy storage device after crosslinking a silane-modified polyolefin was measured at 160℃~220℃.
[0406] and / or the loss modulus change ratio (R) defined by the following equation (3) ΔE”The ratio is 1.5 to 20 times.
[0407] R ΔE” =E” S / E” j (3)
[0408] In the formula, E” j The loss modulus of the aforementioned energy storage device separator measured at 160°C to 220°C before the crosslinking reaction of the aforementioned silane-modified polyolefin, and E” S The loss modulus of the aforementioned energy storage device separator after crosslinking the aforementioned silane-modified polyolefin was measured at 160°C to 220°C.
[0409] The third implementation method involves changing the energy storage modulus ratio (R) ΔE’ ) and / or loss modulus change ratio (R ΔE” Within a range of 1.5 to 20 times, it can achieve a balance between shutdown function and high-temperature rupture resistance. Storage modulus change ratio (R...) ΔE’ ) and / or loss modulus change ratio (R ΔE” The preferred ratio is 2 to 18 times. It should be noted that E' j and E' S and E” j and E” S These are the average values of the storage modulus or loss modulus measured within the set temperature range of the measuring device, with 160–220°C as the widest temperature range. Furthermore, when the separator is a laminated membrane, only the porous membrane containing silane-modified polyolefin is taken from the laminated membrane to measure the storage modulus E'. j and E' S and loss modulus E” j and E” S .
[0410] The separator in the fourth embodiment comprises 5-40% by mass of silane-modified polyolefin and 60-95% by mass of polyolefin other than the aforementioned silane-modified polyolefin. Regarding the viscoelasticity determination (version 1) described in the examples, the mixed storage modulus ratio (R) is defined by the following formula (2). E’mix The ratio is 1.5 to 20 times.
[0411] R E’mix =E' a / E'0 (2)
[0412] In the formula, E' a E'0 is the energy storage modulus of a separator for an energy storage device measured at 160℃ to 220℃, where E'0 is the energy storage modulus of a separator for an energy storage device without silane-modified polyolefin measured at 160℃ to 220℃.
[0413] and / or the mixed loss modulus ratio (R) defined by the following equation (4) E”mix The ratio is 1.5 to 20.0 times.
[0414] R E”mix =E” a / E”0 (4)
[0415] In the formula, E” a E”0 is the loss modulus of the separator for the aforementioned energy storage device measured at 160°C to 220°C, and E”0 is the loss modulus of the separator for the energy storage device without the aforementioned silane-modified polyolefin measured at 160°C to 220°C.
[0416] In the fourth embodiment, by making the hybrid energy storage modulus ratio (R... E’mix ) and / or the ratio of mixed loss modulus (R E”mix Within a range of 1.5 to 20.0 times, it can achieve a balance between shutdown function and high-temperature burst resistance. Hybrid storage modulus ratio (R...) E’mix ) and / or the ratio of mixed loss modulus (R E”mix The preferred ratio is 2 to 18 times. It should be noted that E' a and E'0 and E” a E' and E'' are the average values of the storage modulus or loss modulus measured within the set temperature range of the measuring device, with 160–220°C as the widest temperature range. Furthermore, when the separator is a laminated membrane, only the porous membrane containing silane-modified polyolefin is taken from the laminated membrane to measure the storage modulus E'. a and E'0 and loss modulus E” a And E”0.
[0417] The separator in the fifth embodiment comprises 5-40% by mass of silane-modified polyolefin and 60-95% by mass of polyolefin other than the aforementioned silane-modified polyolefin. Regarding the viscoelasticity measurement (version 1) described in the examples, the transition temperature between the rubbery flat region and the crystalline molten flow region in the temperature change of its storage modulus or loss modulus is 135°C to 150°C. The fifth embodiment achieves a balance between shut-off function and high-temperature rupture resistance by keeping the transition temperature between the rubbery flat region and the crystalline molten flow region within the range of 135°C to 150°C. The transition temperature between the rubbery flat region and the crystalline molten flow region is preferably 137°C to 147°C, more preferably 140°C to 145°C, and even more preferably 140°C to 143°C. It should be noted that when the separator is in the form of a laminated film, only the porous membrane containing the silane-modified polyolefin is taken from the laminate to measure the transition temperature between the rubbery flat region and the crystalline molten flow region.
[0418] <Sixth and Seventh Implementation Methods>
[0419] The separator of the sixth embodiment comprises a polyolefin having one or more functional groups. After being housed in a storage device, (1) a condensation reaction occurs between the functional groups of the polyolefin, or (2) the functional groups of the polyolefin react with chemical substances inside the storage device, or (3) the functional groups of the polyolefin react with other types of functional groups, thereby forming a cross-linked structure. It is believed that the functional groups contained in the polyolefin constituting the separator do not enter the crystalline portion of the polyolefin, but cross-link in the amorphous portion. Therefore, after the separator of the sixth embodiment is housed in a storage device, it forms a cross-linked structure by utilizing the surrounding environment or chemical substances inside the storage device, thereby suppressing the increase of internal stress or the deformation of the manufactured storage device.
[0420] On the other hand, if the battery undergoes a cross-linking reaction and processes such as winding / slitting before being housed in the energy storage device, the effects of stresses such as tension generated during these processes may remain. In this case, if these stresses are released after the energy storage device is assembled, it is believed that they may cause deformation or stress concentration in the electrode windings, leading to breakage, and therefore this is not preferred.
[0421] In the sixth embodiment, (1) the condensation reaction between the functional groups of the polyolefin can be, for example, a reaction of two or more functional groups A contained in the polyolefin via covalent bonds. (3) the reaction of the functional groups of the polyolefin with other types of functional groups can be, for example, a reaction of functional group A and functional group B contained in the polyolefin via covalent bonds.
[0422] Furthermore, in the reaction of the functional groups of the polyolefin with the chemical substances inside the energy storage device (2), for example, functional group A contained in the polyolefin can form covalent or coordinate bonds with any of the electrolyte, electrolyte solution, electrode active material, additives, or their decomposition products contained in the energy storage device. Moreover, according to reaction (2), cross-linked structures are formed not only inside the separator, but also between the separator and the electrode or between the separator and the solid electrolyte interface (SEI), which can improve the strength between the multiple components of the energy storage device.
[0423] The separator in the seventh embodiment comprises a polyolefin and has an amorphous cross-linked structure obtained by cross-linking the amorphous portion of the polyolefin. It is considered that the functional groups contained in the polyolefin constituting the separator do not enter the crystalline portion of the polyolefin, but are cross-linked in the amorphous portion. Therefore, compared with conventional cross-linked separators where the crystalline portion and its surrounding area are easily cross-linked, the separator of the seventh embodiment can suppress the increase of internal stress or the deformation of the manufactured energy storage device while maintaining both the shut-off function and the high-temperature rupture resistance of the film, thereby ensuring the safety of the energy storage device. From the same perspective, the amorphous portion of the polyolefin contained in the separator of the seventh embodiment is preferably selectively cross-linked, and more preferably significantly cross-linked compared to the crystalline portion.
[0424] The crosslinking reaction mechanism and crosslinking structure of the seventh embodiment described above are not yet clear, but the inventors have made the following considerations.
[0425] (1) Crystal structure in microporous membranes made of high-density polyethylene
[0426] Polyolefin resins, such as high-density polyethylene, etc. Figure 6 As shown, these are generally crystalline polymers with a higher-order structure consisting of crystalline lamellar (crystalline) portions, amorphous portions, and intermediate layers between them. In the crystalline portions and the intermediate layers between the crystalline and amorphous portions, the polymer chains have low mobility and are difficult to cut; however, relaxation phenomena can be observed in solid viscoelasticity measurements in the 0–120°C region. On the other hand, the polymer chains in the amorphous portions have very high mobility, and this has been observed in solid viscoelasticity measurements in the -150–-100°C region. This is closely related to free radical relaxation, free radical transfer reactions, cross-linking reactions, etc., which will be discussed later.
[0427] Furthermore, the polyolefin molecules that make up the crystal are not singular, such as... Figure 7 As an example, multiple polymer chains form small lamellae, which then aggregate to form crystals. This phenomenon is difficult to observe directly. In recent years, simulations have been used to advance research and clarify this phenomenon. It should be noted that, here, "crystal" refers to the smallest crystalline unit measured through X-ray structural analysis, a unit whose size can be calculated as a microcrystal. Thus, although it refers to the crystalline part (the interior of the lamellae), it is predicted that there exists a portion within the crystal that is unconstrained and has slightly higher mobility.
[0428] (2) Crosslinking reaction mechanism based on electron beams
[0429] Next, the reaction mechanism of electron beam crosslinking (hereinafter referred to as EB crosslinking) of polymers is as follows: (i) irradiation by electron beams ranging from tens to hundreds of kGy, (ii) electron beams passing through the reactant (polymer) and generating secondary electrons, (iii) hydrogen abstraction reaction and free radical generation in the polymer chain based on secondary electrons, (iv) abstraction of adjacent hydrogen and movement of active sites based on free radicals, and (v) crosslinking reaction or polyene formation based on recombination between free radicals. Regarding the free radicals generated in the crystalline region, due to poor mobility, they persist for a long time, and impurities cannot enter the crystal, resulting in a low probability of reaction and extinction. This type of free radical is called a stable radical, which persists for several months. Its lifetime was determined by ESR measurement. As a result, the crosslinking reaction within the crystal is considered poor. However, the free radicals generated in the slightly unconstrained molecular chains inside the crystal or in the surrounding crystalline-amorphous intermediate layer have a slightly longer lifetime. These types of free radicals are called persistent radicals, and they are thought to undergo cross-linking reactions between molecular chains with a high probability in a dynamic environment. On the other hand, due to their extremely high mobility, the free radicals generated in amorphous regions have short lifespans, and it is believed that not only cross-linking reactions between molecular chains, but also polyene reactions within a single molecular chain occur with a high probability.
[0430] As mentioned above, it can be inferred that, in the microscopic field of crystal, the cross-linking reaction based on EB cross-linking exists locally inside or around the crystal.
[0431] (3) Cross-linking reaction mechanism based on chemical reaction
[0432] In the seventh embodiment of the present invention, it is preferable to use the functional groups in the polyolefin resin and the chemical substances contained in the energy storage device, or the chemical substances contained in the energy storage device, as catalysts.
[0433] As previously mentioned, polyolefin resins contain both crystalline and amorphous portions. However, due to steric hindrance, the aforementioned functional groups are locally present in the amorphous portions and not within the crystalline portions. This is well known; units such as methyl groups, which are slightly present in polyethylene chains, can sometimes enter the crystals, but grafts larger than ethyl groups do not (Non-Patent Document 2). Therefore, crosslinking points based on reactions different from electron beam crosslinking are only locally present in the amorphous portions.
[0434] (4) The relationship between the differences in cross-linking structures and their effects
[0435] As described above, in the crosslinking reaction based on the internal chemical reaction of the battery used in the seventh embodiment of the present invention, the morphology of the reaction products is different. In the research up to the present invention, in order to clarify the crosslinking structure and understand the changes in the physical properties of the microporous membrane accompanying the structural changes, the following experiments were conducted to elucidate the phenomena.
[0436] First, the mechanical properties of the membrane based on tensile fracture tests were investigated. Furthermore, while conducting the tensile fracture tests, changes in the crystal structure were analyzed using in-situ X-ray structural analysis. The results showed that, for example… Figure 8 As shown, taking the uncrosslinked or chemically crosslinked (before) film as a baseline, the crystalline segmentation of the EB-crosslinked film is suppressed as strain increases. This is because crosslinking occurs selectively within or around the crystalline segment. Consequently, Young's modulus and tensile strength are significantly improved, exhibiting high mechanical strength. On the other hand, no difference in crystalline segmentation is observed in the chemically crosslinked film before and after the crosslinking reaction, suggesting that the amorphous segment is selectively crosslinked. Furthermore, there is no change in mechanical strength before and after the crosslinking reaction.
[0437] Next, the behavior of both during crystal melting was studied through melting / melt-break characteristic tests. The results showed that the melting temperature of the EB-crosslinked film increased significantly, with the melt-break temperature exceeding 200°C. On the other hand, it was confirmed that the melting temperature of the chemically crosslinked film did not change before and after crosslinking treatment, but the melt-break temperature increased to over 200°C. Therefore, it is believed that in the melting (closing) characteristics generated by crystal melting, the EB-crosslinked film, due to crosslinking around the crystal portion, exhibits an increase in melting temperature and a decrease in melting rate. Conversely, the chemically crosslinked film, lacking a crosslinked structure in the crystal portion, does not cause changes in its closing characteristics. Furthermore, in the high-temperature region around 200°C, since both films possess a crosslinked structure after crystal melting, the resin as a whole can be stabilized in a gel state, resulting in good melt-break characteristics.
[0438] The above understanding is summarized in the table below.
[0439] [Table 1]
[0440]
[0441] From the perspective of forming an amorphous cross-linked structure, taking into account both the shut-off function and the high-temperature rupture-resistant film properties, the separator in the seventh embodiment, regarding the viscoelasticity measurement (version 2) described in the examples, is defined by the following formula (1) as the mixed storage modulus ratio (R). E’X ):
[0442] R E’X =E' Z / E'Z0 (1)
[0443] In the formula, E' Z The energy storage modulus is the energy storage modulus measured in the temperature range of 160°C to 300°C after the cross-linking reaction of the aforementioned separator for the energy storage device is carried out within the energy storage device.
[0444] E' Z0 The energy storage modulus is measured in the temperature range of 160°C to 300°C before the aforementioned energy storage device is assembled into the aforementioned energy storage device using the separator.
[0445] and / or the mixed loss modulus ratio (R) defined by the following equation (3) E”X ):
[0446] R E”X =E” Z / E” Z0 (3)
[0447] In the formula, E” Z The loss modulus is the value measured in the temperature range of 160°C to 300°C after the crosslinking reaction of the aforementioned separator for the energy storage device is carried out within the energy storage device.
[0448] E” Z0 The loss modulus is measured in the temperature range of 160°C to 300°C before the aforementioned energy storage device is assembled into the aforementioned energy storage device using the separator.
[0449] Preferably, it is 1.5 to 20 times, more preferably 3 to 18 times. It should be noted that E' Z and E' Z0 and E” Z and E” Z0 These are the average values of the storage modulus or loss modulus measured within the set temperature range of the measuring device, with the widest temperature range being 160°C to 300°C. Furthermore, when the separator is a laminated membrane, the storage modulus E' is measured by removing only the porous polyolefin membrane from the laminated membrane. Z and E' Z0 and loss modulus E” Z and E” Z0 .
[0450] From the perspective of forming an amorphous cross-linked structure, taking into account both the shut-off function and the high-temperature rupture-resistant film, the separators in the sixth and seventh embodiments, regarding the viscoelasticity measurement (version 2) described in the examples, are defined by the following formula (2) as the mixed storage modulus ratio (R). E’mix ):
[0451] R E’mix =E' / E'0 (2)
[0452] In the formula, E' is the energy storage modulus of the separator for an energy storage device with an amorphous cross-linked structure, measured at 160℃~300℃, and
[0453] E'0 is the energy storage modulus of a separator in an energy storage device without an amorphous cross-linked structure, measured at temperatures ranging from 160°C to 300°C.
[0454] and / or the mixed loss modulus ratio (R) defined by the following equation (4) E”mix ):
[0455] R E”mix =E” / E”0 (4)
[0456] {In the formula, E” is the loss modulus measured at 160℃~300℃ when the separator for the aforementioned energy storage device has an amorphous cross-linked structure, and}
[0457] E”0 is the loss modulus of the aforementioned energy storage device separator without an amorphous cross-linked structure, measured at 160°C to 300°C.
[0458] Preferably, the ratio is 1.5 to 20 times, more preferably 3 to 19 times, and even more preferably 5 to 18 times. It should be noted that E' and E'0, and E” and E”0 are the average values of the storage modulus or loss modulus measured within the set temperature range of the measuring device when the widest temperature range is set to 160°C to 300°C. Furthermore, when the separator is a laminated membrane, only the porous polyolefin membrane is removed from the laminated membrane to measure the storage modulus E' and E'0, and the loss modulus E” and E”0.
[0459] <Eighth Implementation Method>
[0460] [Viscoelastic behavior (viscoelasticity measurement described in the examples, version 3)]
[0461] The separator in the eighth embodiment comprises a polyolefin microporous membrane, and regarding the viscoelasticity measurement (version 3) described in the examples, the minimum value of the storage modulus (E') in the solid viscoelasticity measurement at a temperature of -50°C to 250°C is... min The maximum value of E' is 1.0MPa to 10MPa. max The range is 100 MPa to 10,000 MPa, and / or the minimum value of the loss modulus (E”). min The maximum value of E” is 0.1MPa to 10MPa. max The range is 10 MPa to 10,000 MPa. If 1.0 MPa ≤ E' min ≤10MPa and 100MPa≤E' max≤10,000MPa, and / or 0.1MPa≤E” min ≤10MPa and 10MPa≤E” max Within the range of ≤10,000 MPa, there is a tendency to balance the closing function of the separator and its resistance to high-temperature membrane rupture, and manufacturing defects can be avoided in the manufacturing process of the separator or the energy storage device, thus achieving the stability and safety of the energy storage device. From these perspectives, 1.1 MPa ≤ E' is preferred. min ≤9.0MPa and / or 150MPa≤E' max ≤9,500MPa, more preferably 1.2MPa≤E' min ≤8.0MPa and / or 233MPa≤E' max ≤9,000MPa. Furthermore, 0.2MPa≤E” is preferred. min ≤9.0MPa and / or 56MPa≤E” max ≤9,000MPa, more preferably 0.4MPa≤E” min ≤8.0MPa and / or 74MPa≤E” max ≤8,000MPa.
[0462] In the solid viscoelasticity determination (version 3), the average E'(E') is measured from the membrane softening transition temperature of the separator containing the polyolefin microporous membrane to the membrane rupture temperature. ave Preferably, the pressure is 1.0 MPa to 12 MPa, more preferably 1.2 MPa to 10 MPa, and even more preferably 1.8 MPa to 8.2 MPa, and / or the average pressure E (E) is... ave The pressure is preferably 0.5 MPa to 10 MPa, more preferably 0.8 MPa to 8.2 MPa or 0.9 MPa to 3.2 MPa. If E' and / or E” are within the above-mentioned ranges at the temperatures from the membrane softening transition temperature to the membrane rupture temperature, there is a tendency for the cycle stability and safety of the energy storage device equipped with the separator to be improved.
[0463] In the solid viscoelasticity test (version 3), considering both the shut-off function and high-temperature membrane rupture resistance, the membrane softening transition temperature of the separator containing the polyolefin microporous membrane is preferably 140°C to 150°C, more preferably 141°C to 149°C or 146°C to 149°C, and / or the membrane rupture temperature is preferably 180°C or higher, more preferably 190°C or higher, 200°C or higher, 210°C or higher, 220°C or higher, 230°C or higher, or 240°C or higher, and even more preferably 250°C or higher. There is no upper limit to the membrane rupture temperature; in this technical field, it should be understood that membrane rupture can occur even at temperatures above 250°C.
[0464] The conditions used to measure E' and E” in the solid viscoelasticity measurement of the separator (version 3) are described in the examples. When the separator is in the form of a laminated membrane, only the polyolefin microporous membrane is removed from the laminated membrane, and the E' and E” of the removed polyolefin microporous membrane are measured. Furthermore, when the thickness of a single polyolefin microporous membrane is less than 200 μm, dynamic viscoelasticity measurements (version 3) are performed by stacking multiple polyolefin microporous membranes or folding a single polyolefin microporous membrane to achieve a total thickness in the range of 200 μm to 400 μm.
[0465] The separator in the first to eighth embodiments, from the perspective of balancing the shut-off function at lower temperatures and the membrane-breaking property at higher temperatures, and improving the cycle characteristics and safety of the energy storage device, may include: a microporous membrane; and an inorganic porous layer comprising inorganic particles and a resin binder disposed on at least one surface of the microporous membrane. The separator may be formed by using a microporous membrane as a substrate and composite the substrate with an inorganic coating layer.
[0466] <Ninth Implementation Method>
[0467] The separator in the ninth embodiment includes:
[0468] Microporous membranes containing silane-modified polyolefins; and
[0469] An inorganic porous layer comprising inorganic particles and a resin binder is disposed on at least one side of the surface of a microporous membrane.
[0470] The separator in the ninth embodiment may, as desired, include layers other than microporous membranes and inorganic porous layers.
[0471] In the ninth embodiment, the combination of a microporous membrane containing silane-modified polyolefin and an inorganic porous layer tends to balance shut-off function at temperatures below 150°C and membrane rupture at higher temperatures, thereby improving the cycle characteristics of the energy storage device and battery puncture safety. It is speculated that since the silane-modified polyolefin in the microporous membrane is silane-crosslinked, once silane crosslinking occurs, the viscosity of the resin in the microporous membrane may increase. Therefore, at abnormally high temperatures in the energy storage device including the separator of the ninth embodiment, if compressive force is applied between multiple electrodes, the crosslinked high-viscosity resin is less likely to flow into the inorganic layer (i.e., less likely to integrate), thus sufficiently ensuring the gap between the electrodes and suppressing battery short circuits.
[0472] In the ninth embodiment, the silane crosslinking reaction of the silane-modified polyolefin preferably begins when the separator comes into contact with the electrolyte. More preferably, the silane crosslinking reaction is observed when the separator comes into contact with the electrolyte, regardless of whether it begins initially, occurs sequentially, or occurs continuously. By allowing the silane crosslinking reaction of the silane-modified polyolefin to occur when the separator comes into contact with the electrolyte, not only can the crosslinking time of the separator be controlled, preventing production defects in the separator manufacturing process, but also safety and high output can be achieved in the manufacturing process of the energy storage device. Furthermore, by bringing the separator into contact with the electrolyte, crosslinking reactions other than the silane crosslinking reaction can be initiated.
[0473] Regarding the viscoelasticity measurement (version 1) described in the examples of the ninth embodiment, when the measurement is performed after removing the inorganic porous layer from the separator, the storage modulus change ratio (R) defined by the following formula (1A) is preferably used. △E’ The ratio is 1.5 to 20 times.
[0474] R △E’ =E' S / E' j (1A)
[0475] In the formula, E' j The energy storage modulus of the separator for an energy storage device measured at 160℃~220℃ before crosslinking reaction of silane-modified polyolefin, and E' S The energy storage modulus of the aforementioned energy storage device separator, after crosslinking with silane-modified polyolefin, was measured at 160°C to 220°C.
[0476] And / or preferably the loss modulus change ratio (R) defined by the following formula (1B). △E The ratio is 1.5 to 20 times:
[0477] R △E” =E” S / E” j (1B)
[0478] In the formula, E” j The loss modulus of the separator for a storage device measured at 160℃~220℃ before crosslinking reaction of silane-modified polyolefin, and E” S The loss modulus of a separator for an energy storage device after crosslinking a silane-modified polyolefin was measured at 160°C–220°C.
[0479] By changing the energy storage modulus ratio (R) △E’ ) and / or loss modulus change ratio (R △E” Within the range of 1.5 to 20 times, it is easy to balance the shut-off function and the high-temperature rupture resistance of the membrane. Storage modulus change ratio (R)ΔE’ ) and / or loss modulus change ratio (R ΔE” More preferably, it is 2 to 18 times. It should be noted that E' j and E' S and E” j and E” S These are the average values of the storage modulus or loss modulus measured within the set temperature range of the measuring device, with 160–220°C as the widest temperature range. Furthermore, when the separator is a laminated membrane or a composite membrane of a microporous membrane and an inorganic porous layer, the storage modulus E' of the silane-modified polyolefin-containing microporous membrane is measured by extracting only the silane-modified polyolefin-containing microporous membrane from the laminated or composite membrane. j and E' S and loss modulus E” j and E” S .
[0480] Regarding the viscoelasticity measurement (version 1) described in the examples of the ninth embodiment, when the measurement is performed after removing the inorganic porous layer from the separator, the hybrid storage modulus ratio (R) defined by the following formula (2A) is preferably used. E’mix The ratio is 1.5 to 20 times.
[0481] R E’mix =E' / E'0 (2A)
[0482] {In the formula, E' is the energy storage modulus of the separator used in the energy storage device measured at 160℃~220℃, and E'0 is the energy storage modulus of the separator used in the energy storage device without silane-modified polyolefin measured at 160℃~220℃.}
[0483] And / or preferably the hybrid loss modulus ratio (R) defined by the following formula (2B). E”mix The ratio is 1.5 to 20 times.
[0484] R E”mix =E” / E”0 (2B)
[0485] {In the formula, E” is the loss modulus of the separator for energy storage devices measured at 160℃~220℃, and E”0 is the loss modulus of the separator for energy storage devices without silane-modified polyolefin measured at 160℃~220℃.}
[0486] By making the hybrid energy storage modulus ratio (R) E’mix ) and / or the ratio of mixed loss modulus (R E”mix Within the range of 1.5 to 20 times, it is easy to balance shut-off function and high-temperature burst resistance. Hybrid storage modulus ratio (R...) E’mix ) and / or the ratio of mixed loss modulus (R E”mixMore preferably, it is 2 to 18 times. It should be noted that E' and E'0, and E” and E”0 are the average values of the storage modulus or loss modulus measured within the set temperature range of the measuring device when the widest temperature range is set to 160 to 220°C. Furthermore, when the separator is in the form of a laminated membrane or a composite membrane of a microporous membrane and an inorganic porous layer, only the silane-modified polyolefin-containing microporous membrane is taken from the laminated membrane or composite membrane to measure the storage modulus E' and E'0 and the loss modulus E” and E”0 of the silane-modified polyolefin-containing microporous membrane. It should be noted that separators for energy storage devices without silane-modified polyolefin are described in detail in the example items.
[0487] From the perspective of balancing the sealing function and the high-temperature rupture-resistant membrane properties, the transition temperature between the rubber-like flat region and the crystalline molten flow region in the separator of the ninth embodiment is preferably 135°C to 150°C during the temperature change of its storage modulus. The transition temperature between the rubber-like flat region and the crystalline molten flow region is preferably 137°C to 147°C, more preferably 140°C to 145°C, and even more preferably 140°C to 143°C. It should be noted that when the separator is in the form of a laminated membrane or a composite membrane of a microporous membrane and an inorganic porous layer, only the microporous membrane containing silane-modified polyolefin is taken from the laminate or composite membrane to determine the transition temperature of the microporous membrane containing silane-modified polyolefin.
[0488] <Tenth Implementation Method>
[0489] The separator for the energy storage device (hereinafter also simply referred to as the "separator") according to the tenth embodiment includes a first porous layer (layer A) comprising a silane-modified polyolefin capable of forming a cross-linked structure, and a second porous layer (layer B) comprising inorganic particles. Layer A and layer B are each a single layer or multiple layers. Layer B is formed only on one side or on both sides of layer A.
[0490] In a lithium battery (LIB), a representative example of an energy storage device, lithium (Li) ions reciprocate between the positive and negative electrodes. Therefore, by placing a separator comprising layers A and B between the positive and negative electrodes, Li ions can move at a relatively high speed between the electrodes while avoiding contact between them.
[0491] (Thickness ratio)
[0492] Layer A functions as a cross-linked microporous membrane, while layer B functions as an inorganic porous layer formed on the microporous membrane.
[0493] Here, the ratio (TA / TB) of the thickness of layer A to the thickness of layer B is preferably 0.22 or more and 14 or less. If the ratio (TA / TB) is 0.22 or more, the presence ratio of layer A in the separator can be sufficiently ensured, and the function provided by layer A can be performed. On the other hand, if the ratio (TA / TB) is 14 or less, the presence ratio of layer B in the separator can be sufficiently ensured, and the function provided by layer B can be performed.
[0494] By making layers A and B have specific structures, and further setting their ratio (TA / TB) within the aforementioned range, a separator can be provided that improves the cycle characteristics and safety of the energy storage device. Such a separator can be suitably used, for example, as a constituent material of a battery for mobile device or automotive applications.
[0495] From the perspective of the above-mentioned effects, the ratio (TA / TB) is preferably 0.8 or more, more preferably 1.0 or more. On the other hand, the ratio (TA / TB) is preferably 5.5 or less, more preferably 3.2 or less.
[0496] The ratio (TA / TB) can be set to less than 2.5, less than 2.0, or less than 1.0. In this case, the thickness of layer A (TA) is less than 2.5 times or less than the thickness of layer B (TB), making it easy to thin the layer A, or even the separator.
[0497] The total thickness (TA+TB) of layers A and B is preferably 3.0 μm or more and 22 μm or less. If the total thickness (TA+TB) is 3.0 μm or more, there is a tendency for the membrane strength of the separator to increase. On the other hand, if the total thickness (TA+TB) is 22 μm or less, there is a tendency for the ion permeability of the separator to increase.
[0498] From the perspective of the above-mentioned effects, the total thickness (TA+TB) is more preferably 3.5 μm or more, and even more preferably 4.0 μm or more. On the other hand, the total thickness (TA+TB) is more preferably 20 μm or less, and even more preferably 18 μm or less.
[0499] The total thickness (TA+TB) can be set to less than 11 μm, less than 10 μm, or less than 8 μm, for example. Even with such a thin-film separator, improvements in the cycle characteristics and safety of the energy storage device can be achieved as long as it is within the scope of this invention.
[0500] The ratio (TA / TB) and total thickness (TA+TB) can be determined using the methods described in the Examples section, and can also be controlled by adjusting the thickness (TA) and / or the thickness (TB). Layers A and B will be explained later.
[0501] (Shutdown temperature and melt fracture temperature)
[0502] Regarding layer A, under pressure of 0.1 MPa or higher and 10.0 MPa or lower (preferably 10 MPa pressure), the shut-off temperature (sometimes called melting temperature) measured based on resistance is 130°C to 160°C, and the melt rupture temperature (sometimes called film rupture temperature) is preferably 200°C or higher.
[0503] If the aforementioned shut-off temperature is 130°C or higher, unnecessary shut-off can be avoided during the normal operation of the energy storage device, ensuring sufficient output characteristics of the energy storage device. On the other hand, if the aforementioned shut-off temperature is 160°C or lower, the shut-off function can be appropriately applied in case of abnormal operation of the energy storage device.
[0504] Furthermore, if the aforementioned shut-off temperature is above 200°C, it can stop the abnormal reaction of the energy storage device before it reaches the ultra-high temperature region, and can also prevent the separator from melting and breaking during the abnormal reaction of the energy storage device.
[0505] In other words, by ensuring that the shut-off temperature and melt-break temperature meet the aforementioned conditions, it is possible to create a separator for an energy storage device that provides excellent heat resistance, closed-cell characteristics (shut-off function), and melt-break characteristics (melt-break function). Furthermore, the separator itself must also maintain mechanical properties and ion permeability. Therefore, by using a separator that meets the aforementioned conditions for shut-off temperature and melt-break temperature, the energy storage device can achieve improved cycle characteristics and safety.
[0506] From the perspective of the above-mentioned effects, the shut-off temperature is preferably above 130°C, more preferably above 135°C, and even more preferably above 136°C. On the other hand, the shut-off temperature is preferably below 150°C, more preferably below 148°C, and even more preferably below 146°C.
[0507] Similarly, from the perspective of the above-mentioned effects, the melt fracture temperature is preferably 175°C or higher, more preferably 178°C or higher, and even more preferably 180°C or higher. On the other hand, the melt fracture temperature is preferably 230°C or lower, more preferably 225°C or lower, and even more preferably 220°C or lower.
[0508] It should be noted that, regarding the melt fracture temperature, even if it is impossible to accurately measure the range above 200°C, as long as the temperature is above 200°C, the condition of "melt fracture temperature above 200°C" is met.
[0509] In this specification, "shutdown temperature" and "melt fracture temperature" refer to values obtained based on resistance measurements under the aforementioned pressure. That is, while applying the aforementioned pressure to a laminate including a positive electrode, a separator, and a negative electrode, the temperature of the laminate is increased, and the shut-off temperature and melt fracture temperature are derived based on the resulting increase in AC resistance (AC resistance between electrodes). In the tenth embodiment, the temperature at which the AC resistance first exceeds a predetermined reference value (e.g., 1000Ω) is set as the shut-off temperature, and the temperature at which further heating continues and the AC resistance decreases from the aforementioned reference value to below the aforementioned reference value (e.g., 1000Ω) is set as the melt fracture temperature.
[0510] Pressurization of the laminate can be achieved using hydraulic jacks, but is not limited to them; any known pressurization method other than hydraulic jacks can be used. Furthermore, heating of the laminate can be achieved using aluminum heaters, but is not limited to them; any known heating method other than aluminum heaters can be used.
[0511] The aforementioned shut-off temperature and melt fracture temperature can be determined by the methods described in the Examples section. In addition, they can be controlled by adjusting the composition or manufacturing method of layer A.
[0512] (Heat shrinkage rate at 150℃)
[0513] In layer A, the thermal shrinkage rate (T2) at 150°C after forming its cross-linked structure is 0.02 times or more and 0.91 times or less than the thermal shrinkage rate (T1) at 150°C before forming the cross-linked structure. In other words, the ratio (T2 / T1) of the thermal shrinkage rate (T2) at 150°C after forming the cross-linked structure to the thermal shrinkage rate (T1) at 150°C before forming the cross-linked structure is 0.02 or more and 0.91 or less. The larger of the thermal shrinkage rate in the mechanical direction (MD) and the thermal shrinkage rate in the width direction (TD) of layer A is used here.
[0514] Because layer A can form a cross-linked structure based on silane-modified polyolefins, we can focus on the change in thermal shrinkage rate before and after cross-linking.
[0515] If the ratio (T2 / T1) is 0.02 or higher, short circuits can be effectively suppressed, thereby reliably preventing the overall temperature rise of the energy storage device and the resulting smoke and potential fire. On the other hand, if the ratio (T2 / T1) is 0.91 or lower, it can be determined that the cross-linking reaction in layer A has been successfully and sufficiently carried out. That is, if the ratio (T2 / T1) is within the above range, a separator for an energy storage device can be provided that improves the cycle characteristics and safety of the energy storage device.
[0516] Therefore, from the perspective of the above-mentioned effects, the ratio (T2 / T1) is preferably 0.03 or more, more preferably 0.05 or more, and even more preferably 0.07 or more. On the other hand, the ratio (T2 / T1) is preferably 0.7 or less, more preferably 0.5 or less, and even more preferably 0.4 or less.
[0517] It should be noted that the heat shrinkage rate (T1) at 150°C before the cross-linking structure is formed is preferably 70% or less, and more preferably 60% or less.
[0518] Furthermore, the heat shrinkage rate (T2) at 150°C after forming the cross-linked structure is preferably 60% or less, more preferably 50% or less. However, by forming the cross-linked structure, there is a tendency for the heat shrinkage rate to decrease compared to before forming the cross-linked structure, so the heat shrinkage rate (T2) is generally less than the heat shrinkage rate (T1).
[0519] The heat shrinkage rate at 150°C can be determined by the method described in the Examples section. In addition, it can be controlled by adjusting the composition or manufacturing method of layer A.
[0520] The spacers in the various embodiments described above are interchangeable or can be combined with each other. The spacers in the ninth or tenth embodiment described above may, as desired, include layers other than microporous membranes and inorganic porous layers. The constituent elements of the spacers in the first to tenth embodiments will be described below.
[0521] [Microporous membrane]
[0522] Microporous membranes can be formed from polyolefins or modified polyolefins.
[0523] The microporous membrane comprises silane-modified polyolefins, and may also contain other polyolefins as desired. Due to the silane crosslinking properties of the silane-modified polyolefins, the microporous membrane can undergo a crosslinking reaction during the manufacturing process of the separator.
[0524] The polyolefin included in the microporous membrane is not particularly limited, and examples include homopolymers of ethylene or propylene, or copolymers formed from at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, and norbornene. Among these, high-density polyethylene (homopolymer) or low-density polyethylene is preferred from the perspective of heat setting at higher temperatures (sometimes abbreviated as "HS") without clogging the pores, and high-density polyethylene (homopolymer) is more preferred. It should be noted that one type of polyolefin may be used alone, or two or more types may be used in combination.
[0525] From the perspective of resistance to redox degradation and a dense and uniform porous structure, microporous membranes are preferably manufactured using silane-modified polyolefins and ultra-high molecular weight polyethylene (UHMWPE) as raw materials. Generally, the weight-average molecular weight of UHMWPE is known to be 1,000,000 or higher. More preferably, in the manufacture of microporous membranes or separators, the weight ratio of silane-modified polyolefin to UHMWPE (silane-modified polyolefin weight / UHMWPE weight) is 0.05 / 0.95 to 0.40 / 0.60.
[0526] The content of polyolefin contained in the microporous membrane is preferably 50% by weight or more and 100% by weight or less, preferably 70% by weight or more and 100% by weight or less, and more preferably 80% by weight or more and 100% by weight or less. Furthermore, the microporous membrane preferably contains polyolefin with a weight-average molecular weight of 100,000 or more and less than 1,000,000 (preferably at a proportion of 40% by weight or more, more preferably 80% by weight or more relative to the total polyolefin content). The weight-average molecular weight of the polyolefin is more preferably 120,000 or more and less than 950,000, and even more preferably 130,000 or more and less than 930,000. By using polyolefin with a weight-average molecular weight of 100,000 or more and less than 1,000,000, there is a tendency to maintain safety, particularly in heating safety tests, where early polymer shrinkage is less likely to occur during heating tests of energy storage devices. By adjusting the weight-average molecular weight of the microporous membrane to less than 1,000,000, it is possible to suppress forming defects (film texture) during extrusion, known as melt fracture. On the other hand, by adjusting the weight-average molecular weight of the microporous membrane to 100,000 or more, it is possible to suppress the transfer of depressions when the microporous membrane is wound onto a core (wound core).
[0527] Regarding the viscosity-average molecular weight of the microporous membrane when the inorganic porous layer is removed and without crosslinking treatment, from the viewpoint that no polymer powder caused by frictional shear is generated during the roll transport of the separator, it is preferably 100,000 or more and 1,200,000 or less, more preferably 150,000 or more and 800,000 or less.
[0528] The thickness of the microporous membrane is preferably 1.0 μm or more, more preferably 2.0 μm or more, and even more preferably 3.0 μm or more, 4.0 μm or more, or 4.5 μm or more. By making the thickness of the microporous membrane 1.0 μm or more, there is a tendency to further improve the membrane strength. Furthermore, the thickness of the microporous membrane is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less, 22 μm or less, or 19 μm or less. By making the thickness of the microporous membrane 500 μm or less, there is a tendency to further improve the ion permeability. The thickness of the microporous membrane can be measured by the method described in the examples.
[0529] When the microporous membrane is used as a separator in high-capacity lithium-ion secondary batteries in recent years, the membrane thickness is preferably 25 μm or less, more preferably 22 μm or less or 20 μm or less, even more preferably 18 μm or less, and particularly preferably 16 μm or less. In this case, by making the membrane thickness of the microporous membrane 25 μm or less, there is a tendency to further improve the permeability. In this case, the lower limit value of the membrane thickness of the microporous membrane can be 1.0 μm or more, 3.0 μm or more, 4.0 μm or more, 6.0 μm or more, or 7.5 μm or more.
[0530] From the perspective of the high-temperature rupture resistance of the separator in a storage device and the safety of the storage device, the microporous membrane used as the separator is preferably 180°C to 220°C, more preferably 180°C to 200°C, during thermomechanical analysis (TMA). Generally, in the event of an unexpected runaway reaction causing the storage device to heat up, the separator made of polyolefin melts at a low temperature (e.g., below 150°C), stopping the movement of Li ions and the associated discharge inside or outside the storage device. Then, the storage device is cooled naturally by external air or refrigerant, preventing the ignition of the electrolyte or the decomposition of the electrolyte, thus ensuring safety. However, the runaway reaction occurring within the aforementioned storage device does not stop due to the separator melting; it continues to heat up, causing the separator to melt and rupture, compromising the device's safety. Therefore, it is important that the separator does not melt and rupture until the entire storage device has been sufficiently cooled. Furthermore, in ultra-high temperature regions exceeding 220°C, the decomposition reaction of the electrolyte or electrolyte solution proceeds rapidly. The decomposition products trigger a corrosion reaction on the electrodes, further generating heat and potentially leading to an explosion. In this situation, the separator can prevent corrosion by melting and breaking the membrane, allowing active material to penetrate into both electrodes.
[0531] [First porous layer (Layer A)]
[0532] Layer A comprises a silane-modified polyolefin, which can form a cross-linked structure. From the perspective of ensuring resistance to redox degradation and ensuring a dense and uniform porous structure, layer A preferably also comprises polyethylene as a polyolefin different from the silane-modified polyolefin. It should be noted that layer A may contain components other than silane-modified polyolefin and polyethylene.
[0533] Examples of polyolefins constituting silane-modified polyolefins in layer A include homopolymers of ethylene or propylene; copolymers formed from at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, and norbornene. Among these, from the perspective of avoiding pore blockage while allowing for heat setting at higher temperatures, homopolymers of ethylene (polyethylene) are preferred as polyolefins, high-density polyethylene and / or low-density polyethylene are more preferred, and high-density polyethylene is even more preferred. One type of polyolefin may be used alone or in combination of two or more types.
[0534] Layer A may contain polymers (other polymers) that are not either silane-modified polyolefins or polyethylene, to the extent that they do not excessively impede the effects brought about by the present invention.
[0535] The weight-average molecular weight of the entire A layer is preferably 100,000 or more and 1,200,000 or less, more preferably 150,000 or more and 800,000 or less.
[0536] (Thickness of layer A)
[0537] The thickness (TA) of layer A is preferably 1 μm or more, more preferably 2 μm or more, and even more preferably 3 μm or more. If the thickness (TA) is 1 μm or more, there is a tendency for the film strength to be further improved. On the other hand, the thickness (TA) is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less. If the thickness (TA) is 500 μm or less, there is a tendency for the ion permeability to be further improved. It should be noted that the thickness (TA) can be set to, for example, 1.00 μm or more, 2.00 μm or more, or 3.00 μm or more.
[0538] When the separator is a LIB separator, the thickness (TA) is preferably less than 22 μm, more preferably less than 21 μm, and even more preferably less than 20.5 μm. When the separator is a LIB separator, the upper limit of the thickness (TA) can be set to less than 13 μm or less than 8.5 μm. If the thickness (TA) is less than 25 μm, there is a tendency for further increased permeability. It should be noted that the thickness (TA) can be set, for example, to less than 22.00 μm, less than 21.00 μm, less than 20.00 μm, less than 13.00 μm, or less than 8.50 μm. The lower limit of the thickness (TA) can be the same as described above.
[0539] The thickness (TA) can be measured by the method described in the Examples section, and can also be controlled by changing the stretching ratio of layer A, etc.
[0540] When layer A is a single layer, the thickness of layer A is considered as the thickness (TA). When layer A is a multi-layered structure, the total thickness of the multiple layers of layer A is considered as the thickness (TA).
[0541] (Temperature of layer A)
[0542] The rupture temperature of layer A, as determined by thermomechanical analysis (TMA), is preferably above 180°C and below 220°C.
[0543] Even if an unexpected runaway reaction causes abnormal heating of the energy storage device, the movement of Li ions and the associated discharge, whether inside or outside the energy storage device, can be stopped by the closing function of the separator. Then, the entire energy storage device can be cooled using a refrigerant, ensuring safety. On the other hand, by keeping the film rupture temperature within the aforementioned range, even if the entire energy storage device is not sufficiently cooled, or in the event of reaching ultra-high temperature regions, the separator can easily suppress further heating by melting and rupturing the film, penetrating the two electrodes, and coating the active material.
[0544] The film breaking temperature can be determined by the method described in the Examples section. In addition, it can be controlled during the manufacturing process by changing the stretching temperature and / or stretching ratio.
[0545] (Porosity of the microporous membrane or layer A)
[0546] The porosity of the microporous membrane or A layer is preferably 20% or more, more preferably 25% or more, and even more preferably 28%, 30%, 32%, or 35% or more. If the porosity is 20% or more, there is a tendency to further improve the ability to follow the rapid movement of Li ions. On the other hand, the porosity is preferably 90% or less, more preferably 80% or less, and even more preferably 60% or less. If the porosity is 90% or less, there is a tendency to further improve the membrane strength and further suppress self-discharge.
[0547] Porosity can be determined by the methods described in the Examples section, and can also be controlled during the manufacturing process by changing the stretching temperature and / or stretching ratio.
[0548] (Air permeability of the microporous membrane or layer A)
[0549] The preferred air permeability for the microporous membrane or A layer is 1 second / 100cm. 3 The above is preferred to be 50 seconds per 100cm. 3 The above is further optimized to 55 seconds per 100cm. 3 The above, and even more preferably 70 seconds or more, 90 seconds or more, or 110 seconds or more. If the air permeability is 1 second / 100cm... 3 The above suggests a tendency to further improve the balance between membrane thickness, porosity, and average pore size. On the other hand, the preferred air permeability is 400 seconds / 100 cm². 3 Below, more preferably 300 seconds or less / 100cm 3 Further optimized to 270 seconds per 100cm 3 Below. If the air permeability is 400 seconds / 100cm. 3 The following shows a tendency for further increases in ion permeability.
[0550] Air permeability can be measured by the methods described in the Examples section. In addition, it can be controlled during the manufacturing process by changing the stretching temperature and / or stretch ratio.
[0551] (Puncture strength of microporous membrane or layer A)
[0552] The puncture strength of the microporous membrane or A layer is preferably 200 gf / 20 μm or more, and more preferably 300 gf / 20 μm or more. If the puncture strength is 200 gf / 20 μm or more, even if active material or the like detaches during the winding of the separator and electrode laminate, membrane rupture caused by the detached active material or the like is easily suppressed. Furthermore, the possibility of short circuits due to the expansion and contraction of the electrodes accompanying charging and discharging is easily reduced. On the other hand, the puncture strength is preferably 4000 gf / 20 μm or less, and more preferably 3800 gf / 20 μm or less. If the puncture strength is 3500 gf / 20 μm or less, thermal shrinkage during heating is easily reduced.
[0553] Puncture strength can be determined by the method described in the Examples section. In addition, it can be controlled in the manufacturing process by changing the stretching temperature and / or stretching ratio.
[0554] [Tensile strength of microporous membrane or layer A]
[0555] The tensile strength of the microporous membrane or A layer is preferably 1000 kgf / cm² in both the MD (length direction, mechanical direction, or processing direction of the membrane or A layer) and TD (width direction orthogonal to MD, the direction of the membrane or A layer). 2 The above, more preferably 1050 kgf / cm 2 The above is further optimized to 1100 kgf / cm². 2 The above. By achieving a tensile strength of 1000 kgf / cm. 2 The above features a tendency to further suppress breakage during slitting or winding of the energy storage device, and to further suppress short circuits caused by foreign objects within the energy storage device. On the other hand, the tensile strength is preferably 5000 kgf / cm². 2 The following is more preferably 4500 kgf / cm² 2 The following is a further preferred value: 4000 kgf / cm² 2 The following is an example of achieving a tensile strength of 5000 kgf / cm. 2 The following results in the microporous membrane or A layer relaxing early and reducing contractile force during heating tests, which tends to improve safety.
[0556] [Tensive modulus of elasticity of microporous membrane or layer A]
[0557] The tensile modulus of the microporous membrane or A-layer is preferably 120 N / cm or less in both the MD and TD directions, more preferably 100 N / cm or less, and even more preferably 90 N / cm or less. A tensile modulus of 120 N / cm or less indicates that the separator used in lithium-ion secondary batteries is not extremely oriented. In heating tests, for example, when the blocking agent such as polyethylene melts and shrinks, stress relaxation occurs in the polyethylene in the early stage. This suppresses the shrinkage of the separator within the battery and easily prevents short circuits between electrodes (i.e., it can improve the safety of the separator during heating). This low tensile modulus can be easily achieved by including polyethylene with a weight-average molecular weight of 500,000 or less in the polyolefin forming the microporous membrane or A-layer. On the other hand, there is no particular limitation on the lower limit of the tensile modulus, but it is preferably 10 N / cm or more, more preferably 30 N / cm or more, and even more preferably 50 N / cm or more. The tensile modulus can be appropriately adjusted by adjusting the degree of stretching during the manufacturing process or by relaxing it after stretching as needed.
[0558] <Polyolefins>
[0559] The polyolefin is not particularly limited, and examples include homopolymers of ethylene or propylene, or copolymers formed from at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, and norbornene. Among these, high-density polyethylene or low-density polyethylene is preferred from the viewpoint that heat setting at higher temperatures (sometimes abbreviated as "HS") can be performed without clogging pores. It should be noted that a single polyolefin may be used, or two or more may be used in combination.
[0560] Furthermore, the separator preferably comprises a polyolefin with a weight-average molecular weight (Mw) of less than 2,000,000, and more preferably, it comprises at least 40% by mass and more preferably at least 80% by mass relative to the total polyolefin. By using a polyolefin with a Mw of less than 2,000,000, there is a tendency to relax the early shrinkage of the polymer during heating tests of the energy storage device, and especially to maintain safety during heating safety tests. It should be noted that, compared to using a polyolefin with a Mw of 1,000,000 or more, the elastic modulus in the thickness direction of the resulting microporous membrane tends to be smaller when using a polyolefin with a Mw of less than 2,000,000, thus resulting in a microporous membrane with an uneven texture that is easier to transfer to the core. The weight-average molecular weight of the polyolefin microporous membrane constituting the separator is preferably 100,000 or more and 2,000,000 or less, more preferably 150,000 or more and 1,500,000 or less.
[0561] (Polyolefins having one or more functional groups)
[0562] From the perspective of cross-linking structure formation, resistance to redox degradation, and dense and uniform porous structure, the separator, as a polyolefin having one or more functional groups, preferably includes functional group-modified polyolefins or polyolefins obtained by copolymerizing monomers having functional groups. It should be noted that, in this specification, functional group-modified polyolefins refer to substances obtained by attaching functional groups after the manufacture of a polyolefin. The functional groups are attached to the polyolefin backbone or can be introduced into the comonomer, preferably participating in the selective cross-linking of the amorphous portion of the polyolefin. For example, they can be at least one group selected from the group consisting of carboxyl, hydroxyl, carbonyl, polymerizable unsaturated hydrocarbon, isocyanate, epoxy, silanol, hydrazide, carbodiimide, oxazoline, acetoacetyl, aziridinyl, ester, active ester, carbonate, azide, chain or cyclic hydrocarbon containing heteroatoms, amino, mercapto, metal chelate, and halogen-containing groups.
[0563] From the perspective of the strength, ion permeability, resistance to redox degradation, and dense and uniform porous structure of the separator, the separator preferably comprises both a polyolefin having one or more functional groups and unmodified silane polyethylene. When using a combination of a polyolefin having one or more functional groups and unmodified silane polyethylene, the mass ratio of the polyolefin having one or more functional groups to the unmodified silane polyethylene in the separator (mass of polyolefin having one or more functional groups / mass of unmodified silane polyethylene) is preferably 0.05 / 0.95 to 0.80 / 0.20.
[0564] (Cross-linked structure)
[0565] The cross-linked structure of the separator contributes to both its shut-off function and high-temperature rupture resistance, as well as the safety of the energy storage device. It is preferable that the cross-linking is formed in the amorphous portion of the polyolefin contained in the separator. The cross-linked structure can be formed, for example, through a reaction utilizing any of the following bonds: covalent bonds, hydrogen bonds, or coordination bonds. Among these, the reaction utilizing covalent bonds is preferably at least one selected from the group consisting of reactions (I) to (IV) below:
[0566] (I) Condensation reaction of multiple identical functional groups
[0567] (II) Reactions between multiple different functional groups
[0568] (III) Chain condensation reaction between functional groups and electrolyte
[0569] (IV) Chain condensation reaction of functional groups with additives.
[0570] Furthermore, the reaction utilizing coordinate bonds is preferably the following reaction (V):
[0571] (V) A reaction in which multiple identical functional groups cross-link with dissolved metal ions via coordination bonds.
[0572] Reaction (I)
[0573] The first functional group of the separator is denoted as A. The following is a schematic diagram of the principle of reaction (I) and a specific example.
[0574]
[0575] When the functional group A used for reaction (I) is a silanol group, the polyolefin contained in the separator is preferably silane-grafted modified. The silane-grafted modified polyolefin is composed of a polyolefin main chain with an alkoxysilyl group as a graft on the main chain. It should be noted that the alkoxide salts that replace the aforementioned alkoxysilyl group can be, for example, methanol salts, ethanol salts, butoxide salts, etc. For example, in the above formula, R can be methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, etc. Furthermore, the main chain and the graft are connected by covalent bonds, and structures such as alkyl, ether, glycol, or ester can be used. Considering the manufacturing process of the separator in this embodiment, in the stage before the crosslinking treatment step, the silicon to carbon ratio (Si / C) of the silane-grafted modified polyolefin is preferably 0.2 to 1.8%, more preferably 0.5 to 1.7%.
[0576] The preferred density of the silane-grafted modified polyolefin is 0.90–0.96 g / cm³. 3 Furthermore, the melt mass flow rate (MFR) at 190°C is 0.2–5 g / min. From the perspective of suppressing resin aggregate formation during the manufacturing process of the separator and maintaining silane crosslinking until contact with the electrolyte, silane-grafted modified polyolefins are preferably masterbatch resins that do not contain dehydration condensation catalysts. Dehydration condensation catalysts are known to also function as catalysts for the siloxane bond formation reaction of alkoxysilyl-containing resins. In this specification, the substance obtained by pre-adding a dehydration condensation catalyst (e.g., an organometallic catalyst) to an alkoxysilyl-containing resin or other compounded resin and mixing it in a continuous process of resin compounding using an extruder is referred to as masterbatch resin.
[0577] Reaction (II)
[0578] The first functional group of the separator is denoted as A, and the second functional group is denoted as B. The following is a schematic diagram of the principle of reaction (II) and a specific example.
[0579] Schematic diagram of the principle of reaction (II)
[0580]
[0581] Examples of combinations of functional groups A and B:
[0582] Hydroxyl and carboxyl groups (esterification);
[0583] Carbonyl group condensed with alkyl group (aldehyde-alcohol condensation);
[0584] Halogens and carboxyl groups (intramolecular condensation);
[0585] Alkoxy groups react with alkyl groups (Claisen reaction);
[0586] Carbonyl group reacts with acid anhydride group (Perkin reaction);
[0587] Amino and halogen;
[0588] The isocyanate group reacts with the hydroxyl group (to form a carbamate bond); and
[0589] (oxazoline) and hydroxyl, etc.
[0590]
[0591] Reactions (I) and (II) can be catalyzed, for example, by chemical substances within the energy storage device assembled by the separator. These chemical substances can be, for example, any of the electrolyte, electrolyte solution, electrode active materials, additives, or their decomposition products contained in the energy storage device.
[0592] Reaction (III)
[0593] The first functional group of the separator is denoted as A, and the electrolyte is denoted as Sol. The following is a schematic diagram of the principle of reaction (III) and a specific example.
[0594] Schematic diagram of reaction (III)
[0595]
[0596] Example of functional group A:
[0597] Hydroxyl, carboxyl, amino, carbonyl, ether, isocyanate, etc.
[0598] Examples of electrolytes:
[0599] Electrolytes: LiPF6, LiBF4, LiN(SO2CF3)2, LiSO3CF3, LiBC4O8 (LiBOB), etc.
[0600] Non-aqueous solvents: ethylene carbonate, methyl ethyl carbonate, or mixtures thereof, etc.
[0601]
[0602]
[0603] Reaction (IV)
[0604] The first functional group of the separator is denoted as A, the second functional group introduced as desired is denoted as B, and the additive is denoted as Add. The following is a schematic diagram of the principle of reaction (IV).
[0605]
[0606] From the perspective of forming covalent bonds indicated by dashed lines in the above schematic diagram, reaction (IV) is preferably a nucleophilic substitution reaction, nucleophilic addition reaction, or ring-opening reaction between compound Rx constituting the separator and compound Ry constituting the additive (Add). Compound Rx can be a polyolefin contained in the separator, such as polyethylene or polypropylene, and preferably the polyolefin is modified by functional group x, for example by at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH, and -SH.
[0607] Since multiple compounds Rx are crosslinked via compound Ry as an additive, compound Ry preferably has two or more linking reaction units y1. These multiple linking reaction units y1 can be any structure or group, can be substituted or unsubstituted, can contain heteroatoms or inorganic substances, and can be the same or different from each other, as long as they can undergo nucleophilic substitution, nucleophilic addition, or ring-opening reactions with the functional group x of compound Rx. Furthermore, when compound Ry has a chain structure, the multiple linking reaction units y1 can each independently be a terminal group, introduced into the main chain, or a side chain or side group.
[0608] In the case of reaction (IV) being a nucleophilic substitution reaction, as an example only, the functional group x of compound Rx will be regarded as a nucleophilic group and the linking reaction unit y1 of compound Ry will be regarded as a leaving group. However, in this embodiment, both functional group x and linking reaction unit y1 can form leaving groups according to their nucleophilicity.
[0609] From the perspective of nucleophiles, the functional group x of compound Rx is preferably an oxygen-based nucleophile, a nitrogen-based nucleophile, or a thiophanate-based nucleophile. Examples of oxygen-based nucleophiles include hydroxyl, alkoxy, ether, and carboxyl groups, with -OH and -COOH being preferred. Examples of nitrogen-based nucleophiles include ammonium, primary amino, and secondary amino groups, with -NH2 and -NH- being preferred. Examples of thiophanate-based nucleophiles include -SH and thioether groups, with -SH being preferred.
[0610] In the case that reaction (IV) is a nucleophilic substitution reaction, from the perspective of the leaving group, the linking reaction unit y1 of compound Ry is preferably an alkyl sulfonyl group such as CH3SO2- or CH3CH2SO2-; an aryl sulfonyl group (-ArSO2-); a haloalkyl sulfonyl group such as CF3SO2- or CCl3SO2-; an alkyl sulfonate group such as CH3SO3- or CH3CH2SO3-; an aryl sulfonate group (ArSO3-); a haloalkyl sulfonate group such as CF3SO3- or CCl3SO3-; and a heterocyclic group, which can be used alone or in various combinations. Examples of heteroatoms included in the heterocycle include nitrogen atoms, oxygen atoms, and sulfur atoms, among which nitrogen atoms are preferred from the perspective of leaving property. The leaving group containing a nitrogen atom in the heterocycle is preferably a monovalent group as shown in formulas (y1-1) to (y1-6) below:
[0611]
[0612] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0613]
[0614] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0615]
[0616] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0617]
[0618] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0619]
[0620] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0621]
[0622] {In the formula, X is a hydrogen atom or a monovalent substituent.}
[0623] In formulas (y1-1) to (y1-6), X is a hydrogen atom or a monovalent substituent. Examples of monovalent substituents include alkyl groups, haloalkyl groups, alkoxy groups, and halogen atoms.
[0624] When reaction (IV) is a nucleophilic substitution reaction and compound Ry has a chain structure, compound Ry preferably has at least one of the following groups selected from the group consisting of divalent groups shown in formulas (y2-1) to (y2-6) as the chain unit y2, in addition to the reaction unit y1:
[0625]
[0626] In the formula, m is an integer from 0 to 20, and n is an integer from 1 to 20.
[0627]
[0628] In the formula, n is an integer from 1 to 20.
[0629]
[0630] In the formula, n is an integer from 1 to 20.
[0631]
[0632] In the formula, n is an integer from 1 to 20.
[0633]
[0634] {In the formula, X is an alkylene or aryl group having 1 to 20 carbon atoms, and n is an integer from 1 to 20.}
[0635]
[0636] {In the formula, X is an alkylene or aryl group with 1 to 20 carbon atoms, and n is an integer from 1 to 20.}
[0637] Furthermore, in the case where the compound Ry contains multiple chain units y2, they can be the same or different from each other, and their arrangement can be block or random.
[0638] In formula (y2-1), m is an integer from 0 to 20, and from the perspective of cross-linking networks, it is preferably 1 to 18. In formulas (y2-1) to (y2-6), n is an integer from 1 to 20, and from the perspective of cross-linking networks, it is preferably 2 to 19 or 3 to 16. In formulas (y2-5) to (y2-6), X is an alkylene or aryl group having 1 to 20 carbon atoms, and from the perspective of the stability of the chain structure, it is preferably methylene, ethylene, n-propylene, n-butylene, n-hexylene, n-heptylene, n-octylene, n-dodecylene, o-phenylene, m-phenylene, or p-phenylene.
[0639] Regarding the case where reaction (IV) is a nucleophilic substitution reaction, the preferred combination of functional group x of compound Rx with linking reaction unit y1 and chain unit y2 of compound Ry is shown in Tables 2 to 4 below.
[0640] [Table 2]
[0641]
[0642] [Table 3]
[0643]
[0644] [Table 4]
[0645]
[0646] As a specific example of a nucleophilic substitution reaction, the following shows a polyolefin with functional group x being -NH2, additive (compound Ry) linking reaction unit y1 having a backbone derived from succinimide, and chain unit y2 having -(O-C2H5). n - Schematic diagram of the reaction principle at time.
[0647]
[0648] As a specific example of a nucleophilic substitution reaction, the following diagram illustrates the reaction principle when the functional groups x of the polyolefin are -SH and -NH2, the linking reaction unit y1 of the additive (compound Ry) is a nitrogen-containing cyclic skeleton, and the chain unit y2 is an ortho-phenylene.
[0649]
[0650] In the case of a nucleophilic addition reaction (IV), the functional group x of compound Rx can undergo an addition reaction with the connecting reaction unit y1 of compound Ry. In the nucleophilic addition reaction, the functional group x of compound Rx is preferably an oxygen-based nucleophile, a nitrogen-based nucleophile, or a thio-based nucleophile. Examples of oxygen-based nucleophiles include hydroxyl, alkoxy, ether, and carboxyl groups, with -OH and -COOH being preferred. Examples of nitrogen-based nucleophiles include ammonium, primary amino, and secondary amino groups, with -NH2 and -NH- being preferred. Examples of thio-based nucleophiles include -SH and thioether groups, with -SH being preferred.
[0651] In a nucleophilic addition reaction, the linking reaction unit y1 of compound Ry is preferably selected from at least one group consisting of the groups shown in formulas (Ay1-1) to (Ay1-6) from the perspective of addition reactivity or availability of starting materials:
[0652]
[0653] {In the formula, R is a hydrogen atom or a monovalent organic group.}
[0654]
[0655]
[0656] In formula (Ay1-4), R is a hydrogen atom or a monovalent organic group, preferably a hydrogen atom or a C atom. 1~20 Alkyl, alicyclic or aromatic groups, more preferably hydrogen atoms, methyl, ethyl, cyclohexyl or phenyl.
[0657] Regarding the case where reaction (IV) is a nucleophilic addition reaction, preferred combinations of functional group x of compound Rx and linking reaction unit y1 of compound Ry are shown in Tables 5 and 6 below.
[0658] [Table 5]
[0659]
[0660] [Table 6]
[0661]
[0662] As a specific example of a nucleophilic addition reaction, the following diagram illustrates the reaction principle when the functional group x of the separator is -OH and the connecting reaction unit y1 of the additive (compound Ry) is -NCO.
[0663]
[0664] When reaction (IV) is a ring-opening reaction, the functional group x of compound Rx and the linking reaction unit y1 of compound Ry can undergo a ring-opening reaction. From the perspective of the availability of raw materials, it is preferable that the ring structure on the linking reaction unit y1 side is open. From the same perspective, the linking reaction unit y1 is more preferably an epoxy group, and compound Ry is more preferably having at least two epoxy groups, and even more preferably a diepoxide compound.
[0665] When reaction (IV) is a ring-opening reaction, the functional group x of compound Rx is preferably at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH and -SH, and / or the linking reaction unit y1 of compound Ry is preferably at least two groups as shown in the following formula (ROy1-1):
[0666]
[0667] {In the formula, each X is independently a hydrogen atom or a monovalent substituent.}
[0668] In formula (ROy1-1), each of the multiple X's is independently a hydrogen atom or a monovalent substituent, preferably a hydrogen atom or a C'. 1~20 Alkyl, alicyclic, or aromatic groups, more preferably hydrogen atoms, methyl, ethyl, cyclohexyl, or phenyl. Regarding the epoxy ring-opening reaction, preferred combinations of functional group x of compound Rx and the linking reactive unit y1 of compound Ry are shown in Table 7 below.
[0669] [Table 7]
[0670]
[0671] Reaction (V)
[0672] The first functional group of the separator is denoted as A, and the metal ion is denoted as M. n+ The following is a schematic diagram of the reaction (V) and an example of functional group A.
[0673]
[0674] In the above schematic diagram, metal ion M n+ Preferably, it is a metal ion dissolved from the energy storage device (hereinafter also referred to as dissolved metal ions), for example, it can be selected from Zn. 2+ Mn 2+ Co 3+ Ni 2+ and Li + At least one of the groups must be present. The following example illustrates functional group A as -COO. - Coordinate key at time.
[0675]
[0676] The following shows a case where functional group A is -COOH and the dissolved metal ion is Zn. 2+ The specific schematic diagram of the reaction (V) at that time.
[0677]
[0678] In the above schematic diagram, hydrofluoric acid (HF) may be derived, for example, from any of the electrolyte, electrolyte solution, electrode active material, additives, or their decomposition products or hygroscopic substances contained in the energy storage device, depending on the charge and discharge cycle of the energy storage device.
[0679] <Silane-modified polyolefins>
[0680] Silane-modified polyolefins consist of a polyolefin backbone with alkoxysilyl groups grafted onto it. Silane-modified polyolefins can be obtained by grafting alkoxysilyl groups onto the backbone of unmodified silane polyolefins.
[0681] It is presumed that alkoxysilyl groups are converted to silanol groups via water-based hydrolysis, followed by cross-linking to form siloxane bonds (see the formula below; the ratio of T1, T2, and T3 structures is arbitrary). Examples of alkoxides substituted with alkoxysilyl groups include methanol salts, ethanol salts, butanol salts, etc. In the formula below, R can be represented by: methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, etc.
[0682]
[0683] The main chain and the graft are connected by covalent bonds. Examples of structures that form these covalent bonds include alkyl groups, ethers, glycols, and esters. In the stage prior to the crosslinking reaction, the silanol units in silane-modified polyolefins are modified to a content of less than 2% relative to the ethylidene units in the main chain.
[0684] The preferred density of the silane-grafted modified polyolefin is 0.90–0.96 g / cm³. 3 Furthermore, the melt mass flow rate (MFR) at 190℃ is 0.2–5 g / min.
[0685] From the perspective of effectively utilizing the effects brought about by the present invention, the amount of silane-modified polyolefin, based on the total amount of the microporous membrane or A layer, is preferably 0.5% by mass or more or 3% by mass or more, more preferably 4% by mass or more, and even more preferably 5% by mass or more or 6% by mass or more. From the perspective of the cycleability and safety of the energy storage device, the amount of silane-modified polyolefin, based on the total amount of the microporous membrane, is preferably 40% by mass or less, more preferably 38% by mass or less. Furthermore, the amount of silane-modified polyolefin, based on the total amount of the A layer, can be set to 30% by mass or more or 50% by mass or more, and even more preferably 100% by mass.
[0686] The cross-linked structure in the microporous membrane or A layer is preferably formed by a compound generated within the energy storage device.
[0687] That is, in the manufacturing process of the energy storage device, when the separator comes into contact with a non-aqueous electrolyte, a cross-linked structure with oligomeric siloxane bonds is preferably formed by the swelling of the microporous membrane or A layer and / or by compounds generated within the energy storage device. This cross-linked structure is obtained by actively promoting the cross-linking reaction in the manufacturing process of the energy storage device, rather than actively promoting it in the manufacturing process of the separator, thus maintaining the self-cross-linking property of the separator until it is contained within the energy storage device.
[0688] From the perspective of suppressing the formation of resin aggregates during the manufacturing process of the separator and maintaining silane crosslinking until contact with the electrolyte, silane-modified polyolefins are preferably not masterbatch resins containing dehydration condensation catalysts. Dehydration condensation catalysts are also known to function as catalysts for the siloxane bond formation reaction of alkoxysilyl-containing resins. In this specification, the substance obtained by adding a dehydration condensation catalyst (e.g., an organometallic catalyst) to an alkoxysilyl-containing resin or other compounded resin in advance and mixing it in a continuous process having a resin compounding step using an extruder is referred to as masterbatch resin.
[0689] (Polyethylene)
[0690] In this specification, polyethylene (polyethylene further contained in the microporous membrane or A layer as a polyolefin different from the silane-modified polyolefin) refers to polyethylene as a homopolymer polymer of polyethylene with a weight average molecular weight of 100,000 or more and 10,000,000 or less, or a copolymer copolymer polymer containing alkane units.
[0691] When the microporous membrane or layer A further comprises polyethylene as a polyolefin different from the silane-modified polyolefin, its content, based on the total amount of silane-modified polyolefin and polyethylene, is preferably 20% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more. If the polyethylene content is 20% by mass or more, there is a tendency to easily ensure resistance to redox degradation and also to ensure a dense and uniform porous structure.
[0692] On the other hand, the polyethylene content is preferably 97% by mass or less, more preferably 96% by mass or less, and even more preferably 95% by mass or less. If the polyethylene content is 97% by mass or less, the content of silane-modified polyolefin in the microporous membrane or A layer can be ensured.
[0693] (Detection method for silane-modified polyolefins contained in separators)
[0694] When the silane-modified polyolefin contained in the separator is cross-linked, it is insoluble or has insufficient solubility in organic solvents, making it sometimes difficult to directly determine the content of silane-modified polyolefin from the separator. In such cases, as a sample pretreatment, methyl orthoformate, which does not cause side reactions, is used to decompose the siloxane bonds into methoxysilanols, followed by solution NMR determination, thereby detecting the silane-modified polyolefin contained in the separator. The pretreatment experiment can be performed according to Japanese Patent Nos. 3529854 and 3529858.
[0695] Specifically, the detection method for silane-modified polyolefins contained in the separator can effectively utilize the silane-modified polyolefins used as raw materials in the manufacture of the separator. 1 H or 13 NMR identification of C. The following is... 1 H and 13 An example of a method for determining C by NMR will be illustrated.
[0696] ( 1 (NMR determination of H)
[0697] The sample was dissolved in o-dichlorobenzene-d4 at 140℃ to obtain a proton resonance frequency of 600MHz. 1 H-NMR spectrum. 1 The determination conditions for H-NMR are as follows.
[0698] Device: AVANCE NEO 600 manufactured by Bruker
[0699] Sample tube diameter: 5mmφ
[0700] Solvent: o-dichlorobenzene-d4
[0701] Measurement temperature: 130℃
[0702] Pulse angle: 30°
[0703] Pulse wait time: 1 sec
[0704] Total number of times: 1000 or more
[0705] Sample concentration: 1 wt / vol%
[0706] ( 13 (NMR determination of C)
[0707] The sample was dissolved in o-dichlorobenzene-d4 at 140 °C to obtain 13 C-NMR spectra. 13 The C-NMR measurement conditions are as follows.
[0708] Device: AVANCE NEO 600 manufactured by Bruker
[0709] Sample tube diameter: 5mmφ
[0710] Solvent: o-dichlorobenzene-d4
[0711] Measurement temperature: 130℃
[0712] Pulse angle: 30°
[0713] Pulse wait time: 5 seconds
[0714] Total number of times: 10,000 or more
[0715] Sample concentration: 10 wt / vol%
[0716] Figure 11 and 12 It uses two types of polyolefins, silane-modified polyolefin raw materials 1 and 2. 1 H and 13 The C-NMR spectra of raw materials 1 and 2 are different, and their respective melt index (MI), C3 grafting amount, C4 grafting amount and / or silanol modification amount are different.
[0717] Figure 11 of 1 H and 13 The C-NMR measurement conditions are as follows.
[0718] ( 1 (H-NMR measurement conditions)
[0719] Device: Bruker Avance NEO 600
[0720] Observation kernel: 1 H
[0721] Observation frequency: 600MHz
[0722] Pulse program: zg30
[0723] Pulse wait time: 1 sec
[0724] Total number of times: 1024
[0725] Measurement temperature: 130℃
[0726] Chemical shift reference: 7.219 ppm (o-DCBz)
[0727] Solvent: o-dichlorobenzene-d4
[0728] Sample concentration: 1 wt / vol%
[0729] Sample tube: 5mmφ
[0730] ( 13 C-NMR measurement conditions)
[0731] Device: Bruker Avance NEO 600
[0732] Observation kernel: 13 C
[0733] Observation frequency: 150.91MHz
[0734] Pulse program: zgpg30
[0735] Pulse wait time: 5 seconds
[0736] Total number of times: 24,000 or 12,800
[0737] Measurement temperature: 130℃
[0738] Chemical shift reference: 132.39 ppm (o-DCBz)
[0739] Solvent: o-dichlorobenzene-d4
[0740] Sample concentration: 10 wt / vol%
[0741] Sample tube: 5mmφ
[0742] Figure 12 of 1 H and 13 The C-NMR measurement conditions are as follows.
[0743] ( 1 (H-NMR measurement conditions)
[0744] Device: Bruker Avance NEO 600
[0745] Observation kernel: 1 H
[0746] Observation frequency: 600MHz
[0747] Pulse program: zg30
[0748] Pulse wait time: 1 sec
[0749] Total number of times: 1024
[0750] Measurement temperature: 130℃
[0751] Chemical shift reference: 7.219 ppm (o-DCBz)
[0752] Solvent: o-dichlorobenzene-d4
[0753] Sample concentration: 1 wt / vol%
[0754] Sample tube: 5mmφ
[0755] ( 13 C-NMR measurement conditions)
[0756] Device: Bruker Avance NEO 600
[0757] Observation kernel: 13 C
[0758] Observation frequency: 150.91MHz
[0759] Pulse program: zgpg30
[0760] Pulse wait time: 5 seconds
[0761] Total number of times: 12800
[0762] Measurement temperature: 130℃
[0763] Chemical shift reference: 132.39 ppm (o-DCBz)
[0764] Solvent: o-dichlorobenzene-d4
[0765] Sample concentration: 10 wt / vol%
[0766] Sample tube: 5mmφ
[0767] Figure 13 It is used in Embodiment I-1 described later. Figure 11 The separator shown is in its pre-crosslinking state, made from silane-modified polyolefin raw material 1. 1 H and 13 C-NMR spectrum. Figure 13 of 1 H and 13 The C-NMR measurement conditions are as follows.
[0768] ( 1 (H-NMR measurement conditions)
[0769] Device: Bruker Avance NEO 600
[0770] Observation kernel: 1 H
[0771] Observation frequency: 600MHz
[0772] Pulse program: zg30
[0773] Pulse wait time: 1 sec
[0774] Total number of times: 1024
[0775] Measurement temperature: 130℃
[0776] Chemical shift reference: 7.219 ppm (o-DCBz)
[0777] Solvent: o-dichlorobenzene-d4
[0778] Sample concentration: 1 wt / vol%
[0779] Sample tube: 5mmφ
[0780] ( 13 C-NMR measurement conditions)
[0781] Device: Bruker Avance NEO 600
[0782] Observation kernel: 13 C
[0783] Observation frequency: 150.91MHz
[0784] Pulse program: zgpg30
[0785] Pulse wait time: 5 seconds
[0786] Total number of times: 24,000 or 12,800
[0787] Measurement temperature: 130℃
[0788] Chemical shift reference: 132.39 ppm (o-DCBz)
[0789] Solvent: o-dichlorobenzene-d4
[0790] Sample concentration: 10 wt / vol%
[0791] Sample tube: 5mmφ
[0792] Furthermore, for cross-linked separators, after the pretreatment described above, they can be separated by... Figure 13 The same NMR measurements were performed (not shown).
[0793] like Figures 11-13 As shown, through 1 H and / or 13 NMR determination of C can confirm the amount of silane unit modification and alkyl modification in silane-modified polyolefins in polyolefin raw materials. Furthermore, in the separator, the presence of (-CH) groups in the silane-modified polyolefin can be identified. 2 -Si: 1 H, 0.69ppm,t; 13 C, 6.11 ppm, s).
[0794] [Combination of microporous membranes and inorganic porous layers]
[0795] The combination of a microporous membrane containing silane-modified polyolefins with an inorganic porous layer tends to balance shut-off function at temperatures below 150°C and membrane rupture resistance at higher temperatures, while also improving the cycle characteristics of the energy storage device and the safety of battery penetration. It is speculated that because the silane-modified polyolefins in the microporous membrane are silane-crosslinked, silane crosslinking can sometimes increase the viscosity of the resin in the microporous membrane. Therefore, at abnormally high temperatures in the energy storage device including separators, if compressive forces are applied between multiple electrodes, the highly viscous resin that has undergone crosslinking is unlikely to flow into the inorganic layer (i.e., it is difficult to integrate), thus ensuring sufficient spacing between the electrodes and suppressing battery short circuits.
[0796] [Inorganic porous layer]
[0797] The inorganic porous layer is a layer containing inorganic particles and a resin binder, and may further contain a dispersant to disperse the inorganic particles in the binder resin, as desired.
[0798] The thickness of the inorganic porous layer is preferably 0.5 μm to 10 μm, 0.5 μm to 7 μm, 0.5 μm to 5 μm, or 0.5 μm to 4 μm, from the perspective of ion permeability of the separator and charge / discharge capacity or cycle stability of the energy storage device. The thickness of the inorganic porous layer can be determined by the method described in the examples.
[0799] [Second porous layer (layer B)]
[0800] Layer B comprises inorganic particles. Layer B may further comprise a resin binder. When Layer B comprises inorganic particles and a resin binder, Layer B can be the inorganic porous layer described above. It should be noted that Layer B may contain components other than inorganic particles and a resin binder.
[0801] (Thickness of layer B)
[0802] The thickness (TB) of layer B is preferably 0.2 μm or more, more preferably 0.5 μm or more. If the thickness (TB) is 0.5 μm or more, there is a tendency for further improvement in mechanical strength. On the other hand, the thickness (TB) is preferably less than 22 μm, more preferably 20 μm or less, and even more preferably 15 μm or less. If the thickness (TB) is 30 μm or less, the volume occupied by the separator in the energy storage device is reduced, thus becoming advantageous in terms of increasing the capacity of the energy storage device. Furthermore, this is also preferable from the perspective of preventing excessive increase in the permeability of the separator. It should be noted that the thickness (TB) can be set, for example, to 0.50 μm or more, 0.80 μm or more, or 1.00 μm or more, and can also be set to less than 22.00 μm, 20.00 μm or less, or 15.00 μm or less.
[0803] The thickness (TB) can be measured by the method described in the Examples section. In addition, it can be controlled by changing the amount of coating liquid (slurry) used to form layer B.
[0804] When layer B is a single layer, the thickness of layer B is considered as the aforementioned "thickness (TB)". When layer B is multi-layered, the total thickness of the multi-layered layer B is considered as the aforementioned "thickness (TB)".
[0805] Furthermore, when layer B is disposed on both one side and the other side of layer A, the total thickness of layer B disposed on one side and layer B disposed on the other side shall be regarded as the aforementioned “thickness (TB)”.
[0806] (Inorganic particles)
[0807] Examples of inorganic particles include: inorganic oxides (oxide-based ceramics) such as alumina (Al₂O₃), silicon dioxide, titanium dioxide, zirconium oxide, magnesium oxide, cerium oxide, yttrium oxide, zinc oxide, and iron oxide; inorganic nitrides (nitride-based ceramics) such as silicon nitrides, titanium nitrides, and boron nitrides; ceramics such as silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, aluminum hydroxide, aluminum hydroxide oxide (AlO(OH)), potassium titanate, talc, kaolinite, dickite, pearl clay, halloysite, pyrophyllite, montmorillonite, sericite, mica, magnesia chlorite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and quartz sand; and glass fiber. These can be used individually or in combination of two or more.
[0808] The amount of inorganic particles, based on the total amount of the inorganic porous layer or B layer, is preferably 5% by mass or more, or 20% by mass or more, and more preferably 30% by mass or more, from the perspective of ensuring heat resistance. The amount of inorganic particles, based on the total amount of the inorganic porous layer or B layer, can be set to 50% by mass or more, more than 80% by mass, or 85% by mass or more. On the other hand, the amount of inorganic particles is preferably 99.9% by mass or less, more preferably 99.5% by mass or less, or 99% by mass or less.
[0809] It should be noted that the amount of inorganic particles can be set to, for example, 20.00% or more by mass, 30.00% or more by mass, 50.00% or more by mass, more than 80.00% or 85.00% by mass, or on the other hand, it can be set to 99.90% or less by mass or 99.50% or less by mass.
[0810] The shapes of inorganic particles can be listed as: flaky, scaly, needle-like, columnar, spherical, polyhedral, spindle-shaped, and block-shaped. Various inorganic particles with these shapes can be used in combination.
[0811] The number-average particle size of the inorganic particles is, for example, 0.01 μm or more, 0.1 μm or more, or 0.3 μm or more, preferably 0.5 μm or more. On the other hand, the number-average particle size is, for example, 10.0 μm or less, 9.0 μm or less, or 6.0 μm or less, preferably 2.5 μm or less, more preferably 2.0 μm or less, and even more preferably 1.5 μm or less. From the perspective of improving safety during short circuits, it is preferable to adjust the number-average particle size of the inorganic particles to the above-mentioned range. As a method for adjusting the number-average particle size of the inorganic particles, methods such as pulverizing the inorganic particles using a suitable pulverizing device such as a ball mill, bead mill, or jet mill can be listed.
[0812] Regarding the particle size distribution of inorganic particles, the minimum particle size is preferably 0.02 μm or more, more preferably 0.05 μm or more, and even more preferably 0.1 μm or more. The maximum particle size is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 7 μm or less. Furthermore, the ratio of the maximum particle size to the average particle size is preferably 50 or less, more preferably 30 or less, and even more preferably 20 or less. From the perspective of suppressing thermal shrinkage at high temperatures, it is preferable to adjust the particle size distribution of inorganic particles to the above-mentioned range. In addition, multiple particle size peaks may exist between the maximum and minimum particle sizes. It should be noted that, as methods for adjusting the particle size distribution of inorganic particles, examples include: methods of pulverizing and adjusting inorganic fillers to the desired particle size distribution using a ball mill, bead mill, jet mill, etc., and methods of mixing multiple fillers having multiple particle size distributions after preparation.
[0813] (Resin adhesive)
[0814] The resin binder contains a resin that binds inorganic particles together. The glass transition temperature (Tg) of the resin binder, from the perspective of ensuring adhesion to inorganic particles and stability of the inorganic porous layer or B layer in the manufacturing process of the separator, the manufacturing process of the energy storage device, or the charge-discharge process, is preferably -50°C to 100°C, more preferably -35°C to 95°C.
[0815] The glass transition temperature is determined based on the DSC curve obtained from differential scanning calorimetry (DSC). Specifically, the glass transition temperature can be taken as the temperature at the intersection of the straight line obtained by extending the baseline of the low-temperature side of the DSC curve towards the high-temperature side and the tangent at the inflection point of the step-like change portion of the glass transition. More specifically, it can be determined according to the method described in the examples. Furthermore, "glass transition" refers to the heat change that occurs on the endothermic side during DSC, accompanying the change in the state of the polymer used as the test piece. This heat change is observed as a step-like change in the shape of the DSC curve. "Step-like change" refers to the portion of the DSC curve from the previous low-temperature side baseline to the new high-temperature side baseline. It should be noted that the combination of step-like change and peaks is also included in the step-like change. Furthermore, "inflection point" refers to the point where the slope of the DSC curve in the step-like change portion reaches its maximum. In addition, in the step-like change portion, if the upper side is the exothermic side, it can also be expressed as the point where the upward convex curve changes to the downward convex curve. A "peak" refers to the portion of a DSC curve from the baseline on the low-temperature side to the point where it returns to the same baseline. The "baseline" represents the temperature range in which the test specimen does not undergo transformation or reaction.
[0816] As resin adhesives, examples include 1) to 7). These can be used alone or in combination of two or more.
[0817] 1) Polyolefins: such as polyethylene, polypropylene, ethylene propylene rubber and their modifiers;
[0818] 2) Conjugated diene polymers: such as styrene-butadiene copolymers and their hydrides, acrylonitrile-butadiene copolymers and their hydrides, acrylonitrile-butadiene-styrene copolymers and their hydrides;
[0819] 3) Acrylic polymers: such as methacrylate-acrylate copolymers, styrene-acrylate copolymers, and acrylonitrile-acrylate copolymers;
[0820] 4) Polyvinyl alcohol resins: such as polyvinyl alcohol and polyvinyl acetate;
[0821] 5) Fluorinated resins: such as PVdF, polytetrafluoroethylene, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene copolymer and ethylene-tetrafluoroethylene copolymer;
[0822] 6) Cellulose derivatives: such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose; and
[0823] 7) Resins with a melting point and / or glass transition temperature of 180°C or higher, or polymers that do not have a melting point but have a decomposition temperature of 200°C or higher: for example, polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide and polyester.
[0824] These types of resin binders can be obtained from desired monomers using known manufacturing methods such as emulsion polymerization or solution polymerization. In the polymerization process, there are no limitations on the polymerization temperature, the polymerization pressure, the method of monomer addition, or the additives used (polymerization initiators, molecular weight regulators, and pH adjusters, etc.).
[0825] The amount of resin binder is based on the total amount of the inorganic porous layer or B layer, for example, 0.5% by mass or more or 1.0% by mass or more, and on the other hand, for example, 50% by mass or less or 30% by mass or less. Furthermore, as mentioned above, regarding the B layer, the resin binder is an optional component; therefore, the amount of resin binder contained in the B layer, based on the total amount of the B layer, can be set to less than 20% by mass, less than 15% by mass, or 0% by mass. If the amount of resin binder contained in the B layer is reduced, the margin for the presence of the aforementioned inorganic particles in the B layer can be increased accordingly.
[0826] (Dispersant)
[0827] Dispersants are substances that adsorb onto the surface of inorganic particles in slurries used to form inorganic porous layers or B-layers, stabilizing the inorganic particles through electrostatic rebound or other means. Examples include polycarboxylate salts, sulfonates, polyoxyethers, and surfactants. In addition to the above-mentioned components, the inorganic porous layer or B-layer may further contain other components commonly added and blended in water-based coatings, within the effective range described above. These other components are not particularly limited and may include, for example, thickeners, film-forming aids, plasticizers, crosslinking agents, antifreeze agents, defoamers, dyes, preservatives, UV absorbers, and light stabilizers. These other components may be used individually or in combination of two or more.
[0828] (additive)
[0829] The microporous membrane, inorganic porous layer, A layer, and / or B layer may contain known additives as needed. Examples of additives include: organometallic catalysts (dehydration condensation catalysts); plasticizers; antioxidants such as phenols, phosphorus compounds, and sulfur compounds; metal soaps such as calcium stearate and zinc stearate; thickeners; film-forming aids; crosslinking agents; antifreeze agents; defoamers; preservatives; ultraviolet absorbers; light stabilizers; antistatic agents; antifogging agents; dyes; and coloring pigments.
[0830] In addition, layer B may contain a crosslinking agent. This crosslinking agent may contain reactive groups that are reactive with the aforementioned inorganic particles.
[0831] <Properties of the separator>
[0832] When the separator is used in a high-capacity lithium-ion secondary battery, the overall film thickness of the separator is preferably 25 μm or less, more preferably 22 μm or less or 20 μm or less, even more preferably 18 μm or less, and particularly preferably 16 μm or less. By making the film thickness of the separator 25 μm or less, there is a tendency to further improve ion permeability. The lower limit value of the overall film thickness of the separator can be, for example, 1.0 μm or more, 3.0 μm or more, 4.0 μm or more, 6.0 μm or more, or 7.5 μm or more.
[0833] The air permeability of the separator is preferably 50 seconds / 100cm. 3 ~400 seconds / 100cm 3 More preferably 75 seconds per 100cm 3 ~275 seconds / 100cm 3 Further optimized to 100 seconds / 100cm 3 ~200 seconds / 100cm 3 If the separator is 50 seconds / 100cm 3 The above air permeability provides moderate mechanical strength; for example, 400 seconds / 100cm. 3 The following air permeability improves battery performance from a permeability perspective, and is therefore preferred.
[0834] [Energy Storage Device Assembly Kit]
[0835] Another aspect of the present invention provides a storage device assembly kit including the separator for the storage device described above. The storage device assembly kit comprises the following two elements:
[0836] (A) A housing containing the electrodes and the separators for the energy storage devices described above; and
[0837] (B) A container containing a non-aqueous electrolyte.
[0838] When assembling a battery storage device, a cross-linked structure can be formed within the separator by contacting the separator in element (A) with the non-aqueous electrolyte in element (B), by contacting the electrolyte with the laminate or winding within the housing, and / or by continuously performing charge-discharge cycles on the assembled battery storage device, thereby forming a battery storage device that balances safety and output.
[0839] While not wishing to impose theoretical constraints, it can be assumed that when the electrolyte or electrolyte solution comes into contact with the electrodes, and / or during the charging and discharging of the energy storage device, substances that catalyze the cross-linking reaction, or substances with functional groups that form part of the cross-linking structure, are present in the electrolyte solution, on the inner surface of the outer casing, or on the electrode surface. These substances dissolve in the electrolyte solution and uniformly swell and diffuse into the amorphous portions of the polyolefin, thereby uniformly promoting the cross-linking reaction of the laminated or wound body containing spacers. The substances catalyzing the cross-linking reaction can be in the form of an acid solution or a membrane. In the case of an electrolyte containing lithium hexafluorophosphate (LiPF6), these can be hydrogen fluoride (HF) or fluorinated organic compounds derived from hydrogen fluoride (HF). Substances with functional groups that form part of the cross-linking structure can be, for example, compounds having functional groups A and / or B as described above, the electrolyte itself, various additives, etc.
[0840] From the perspective of promoting the cross-linking reaction of the separator, the non-aqueous electrolyte contained in element (2) can be a fluorine (F)-containing lithium salt such as LiPF6 that produces HF, an electrolyte with non-shared electron pairs such as LiN(SO2CF3)2 and LiSO3CF3, or LiBF4, LiBC4O8 (LiBOB).
[0841] From the perspective of promoting the cross-linking reaction of the separator, the energy storage device assembly kit may be equipped with other containers, such as those containing catalysts for promoting the cross-linking reaction, mixtures of organometallic catalysts and water, acid solutions, alkaline solutions, etc., as accessories (or elements (C)).
[0842] [Electronic Storage Device]
[0843] The separator described above can be used in an energy storage device. The energy storage device includes a positive electrode, a negative electrode, a separator of this embodiment disposed between the positive and negative electrodes, an electrolyte, and additives as desired. Once the separator is housed in the device casing, the functionalized polyethylene or functionalized graft copolymer polyethylene reacts with chemicals contained in the electrolyte or additives to form a cross-linked structure, thus creating a cross-linked structure in the manufactured energy storage device. The functionalized polyethylene or functionalized graft copolymer polyethylene is not limited and can be derived from polyolefin raw materials of microporous membranes or from polyolefins modified during the manufacturing process of microporous membranes.
[0844] Specific examples of energy storage devices include: lithium batteries, lithium secondary batteries, lithium-ion secondary batteries, sodium secondary batteries, sodium-ion secondary batteries, magnesium secondary batteries, magnesium-ion secondary batteries, calcium secondary batteries, calcium-ion secondary batteries, aluminum secondary batteries, aluminum-ion secondary batteries, nickel-metal hydride batteries, nickel-cadmium batteries, double-layer capacitors, lithium-ion capacitors, redox flow batteries, lithium-sulfur batteries, lithium-air batteries, and zinc-air batteries. From a practical standpoint, lithium batteries, lithium secondary batteries, lithium-ion secondary batteries, nickel-metal hydride batteries, or lithium-ion capacitors are preferred, with lithium batteries or lithium-ion secondary batteries being more preferred.
[0845] Additives may include dehydration condensation catalysts, metallic soaps such as calcium stearate or zinc stearate, ultraviolet absorbers, light stabilizers, antistatic agents, antifogging agents, and coloring pigments.
[0846] [Lithium-ion rechargeable battery]
[0847] Lithium-ion secondary batteries are rechargeable batteries that use lithium transition metal oxides such as lithium cobalt oxide and lithium cobalt composite oxide as the positive electrode, carbon materials such as graphite and lead oxide as the negative electrode, and organic solvents containing lithium salts such as LiPF6 as the electrolyte. Regarding energy storage device assembly kits, the electrolytes described above can also be used for lithium-ion secondary batteries.
[0848] During the charging / discharging of a lithium-ion secondary battery, ionized lithium reciprocates between the electrodes. Furthermore, it is necessary to allow the aforementioned ionized lithium to move between the electrodes at a relatively high speed while suppressing contact between them; therefore, a separator is placed between the electrodes.
[0849] <Manufacturing Method of Separators for Energy Storage Devices>
[0850] Another aspect of the present invention is a method for manufacturing a separator for an energy storage device. The method for manufacturing the separator may include, for example, a step of manufacturing a microporous membrane or an A layer, and, depending on preference, a step of manufacturing an inorganic porous layer on the microporous membrane, or a step of manufacturing a B layer on the A layer. Unless otherwise specified, the materials used in the method for manufacturing the separator may be those described in the first to tenth embodiments.
[0851] <Eleventh Implementation Method>
[0852] As a method for manufacturing the separator according to the eleventh embodiment, the following description focuses on the case of a microporous membrane (flat membrane), but it is not intended to exclude forms other than flat membranes. The method for manufacturing the microporous membrane according to the eleventh embodiment includes the following steps:
[0853] (1) Sheet forming process;
[0854] (2) Stretching process;
[0855] (3) The porous body forming process; and
[0856] (4) Heat treatment process.
[0857] Layer A, as described above, can also be formed by performing processes (1) to (4).
[0858] The method for manufacturing the separator according to the eleventh embodiment may, as desired, include the following steps in addition to steps (1) to (4):
[0859] (8B) Coating process, forming an inorganic porous layer containing inorganic particles and resin binder on at least one side of the aforementioned heat-treated porous body to form a silane crosslinking precursor;
[0860] (9) Assembly process: The electrode and the aforementioned silane crosslinking precursor laminate or its winding, as well as the non-aqueous electrolyte, are housed in the outer shell, so that the aforementioned silane crosslinking precursor comes into contact with the aforementioned non-aqueous electrolyte.
[0861] In the eleventh embodiment, after coating the microporous membrane that maintains the crosslinking of silane with an inorganic porous layer in step (8B), the separator in the energy storage device is brought into contact with the electrolyte in step (9). Therefore, the stress resistance of the energy storage device and the separator therein is improved, thereby enabling the cycle stability and safety of the energy storage device.
[0862] The method for manufacturing a microporous membrane according to the eleventh embodiment may, as desired, include a mixing process before the sheet forming process (1) and / or a winding / slitting process after the heat treatment process (3). From the perspective of maintaining silane crosslinking until contact with the electrolyte, it is preferable not to include a silane crosslinking treatment process. The silane crosslinking treatment process is generally a process in which the workpiece containing silane-modified polyolefin is contacted with a mixture containing an organometallic catalyst and water, or immersed in an alkaline or acidic solution to perform a silane dehydration condensation reaction to form oligomeric siloxane bonds.
[0863] The metal in an organometallic catalyst can be, for example, at least one selected from the group consisting of scandium, titanium, vanadium, copper, zinc, aluminum, zirconium, palladium, gallium, tin, and lead. Examples of organometallic catalysts include dibutyltin dilaurate, dibutyltin diacetate, and dibutyltin dioctanoate, which are known to overwhelmingly accelerate reaction rates based on the reaction mechanism proposed by Weij et al. (FW van der Weij: Macromol. Chem., 181, 2541, 1980.). Furthermore, in recent years, to avoid the environmental and human health hazards caused by organotin compounds, it is known that the Lewis function of copper and / or titanium chelate complexes, when combined with organic bases, can promote the formation of siloxane bonds between alkoxysilyl groups in a similar manner to organotin complexes.
[0864] The alkaline solution has a pH greater than 7 and may contain, for example, alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkali metal phosphates, ammonia, amine compounds, etc. Among these, from the perspective of the safety of the energy storage device and the crosslinking properties of silane, alkali metal hydroxides or alkaline earth metal hydroxides are preferred, alkali metal hydroxides are more preferred, and sodium hydroxide is even more preferred.
[0865] The acid solution has a pH less than 7 and may contain inorganic or organic acids. Preferred acids are hydrochloric acid, sulfuric acid, carboxylic acids, or phosphoric acid.
[0866] The mixing process uses a mixer. In this embodiment, silane-modified polyolefins, plasticizers or inorganic materials as desired, can be mixed with other polyolefins. From the perspective of suppressing the formation of resin aggregates in the manufacturing process and maintaining the crosslinking properties of silanes until contact with the electrolyte, it is preferable not to add masterbatch resins containing dehydration condensation catalysts to the mixture.
[0867] There are no particular limitations on the plasticizer used; examples include organic compounds that can form a homogeneous solution with polyolefins at temperatures below their boiling points. More specifically, examples include: decahydronaphthalene, xylene, dioctyl phthalate, dibutyl phthalate, stearyl alcohol, oleyl alcohol, decanol, nonanol, diphenyl ether, n-decane, n-dodecane, paraffin oil, etc. Among these, paraffin oil and dioctyl phthalate are preferred. A single plasticizer can be used, or two or more can be used in combination. The proportion of plasticizer is not particularly limited, but from the perspective of the porosity of the resulting microporous membrane, the polyolefin and silane-modified polyolefin are preferably 20% by mass or more relative to the total mass, and from the perspective of the viscosity during melt mixing, preferably 90% by mass or less.
[0868] The sheet forming process involves extruding, cooling, and solidifying the resulting compound, or a mixture of silane-grafted modified polyolefin, polyethylene, and plasticizer, into a sheet shape to obtain a sheet. There are no particular limitations on the sheet forming method; for example, methods that solidify the molten compound and extruded material through compression cooling can be cited. As for cooling methods, examples include: direct contact with cooling media such as cold air or cooling water; contact with rollers and / or presses cooled by refrigerant, etc. The method of contact with rollers and / or presses cooled by refrigerant is preferred in terms of excellent film thickness control.
[0869] From the perspective of resin aggregates in the separator or the maximum internal heating rate, in the sheet forming process, the mass ratio of silane-modified polyolefin to polyethylene (mass of silane-modified polyolefin / mass of polyethylene) is preferably 0.05 / 0.95 to 0.4 / 0.6, more preferably 0.06 / 0.94 to 0.38 / 0.62.
[0870] From the perspective of suppressing thermal runaway and improving safety during battery failure while having low-temperature shut-off below 150°C and high-temperature rupture resistance at 180-220°C, it is preferable that the silane-modified polyolefin in the sheet forming process is not a masterbatch resin containing a dehydration condensation catalyst that crosslinks the silane-modified polyolefin before the sheet forming process.
[0871] The stretching process involves extracting plasticizers and / or inorganic materials from the resulting sheet as needed and further stretching the sheet along one or more axes. Examples of sheet stretching methods include: MD uniaxial stretching based on a roll stretcher, TD uniaxial stretching based on a spreader, successive biaxial stretching based on a combination of a roll stretcher and a spreader or a spreader and a spreader, and simultaneous biaxial stretching based on a simultaneous biaxial spreader or blow molding. From the perspective of obtaining a more uniform film, simultaneous biaxial stretching is preferred. The total areal ratio is preferably 8 times or more, more preferably 15 times or more, and even more preferably 20 times or more or 30 times or more, from the perspective of balancing film thickness uniformity, elongation, porosity, and average pore size. By making the total areal ratio 8 times or more, there is a tendency to easily obtain sheets with high strength and good thickness distribution. Furthermore, from the perspective of preventing breakage, this areal ratio can be 250 times or less.
[0872] The porous body formation process involves extracting plasticizers from the stretched material after the stretching process and porousifying the stretched material. The extraction method for the plasticizer is not particularly limited; examples include immersing the stretched material in an extraction solvent and spraying the stretched material with the extraction solvent. The extraction solvent is also not particularly limited; however, solvents that are poor solvents for polyolefins but good solvents for plasticizers and / or inorganic materials, and whose boiling point is lower than the melting point of polyolefins, are preferred. Such extraction solvents are not particularly limited; examples include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as dichloromethane, 1,1,1-trichloroethane, and fluorocarbons; alcohols such as ethanol and isopropanol; ketones such as acetone and 2-butanone; and alkaline solutions. One extraction solvent can be used alone, or two or more can be used in combination.
[0873] The heat treatment process is a further step after the stretching process, where plasticizers are extracted from the sheet as needed, and the film is further heat-treated to obtain a microporous membrane. There are no particular limitations on the heat treatment method; examples include heat setting methods such as stretching and relaxation operations using a spreader and / or a roll stretching machine. The relaxation operation refers to a reduction operation performed along the mechanical direction (MD) and / or width direction (TD) of the membrane at a specified temperature and relaxation rate. The relaxation rate is the value obtained by dividing the MD dimension of the membrane after the relaxation operation by the MD dimension of the membrane before the operation, or by dividing the TD dimension of the membrane after the relaxation operation by the TD dimension of the membrane before the operation, or, in the case of relaxation along both the MD and TD directions, by multiplying the relaxation rate of the MD by the relaxation rate of the TD.
[0874] [Coating process for inorganic porous layers]
[0875] The inorganic porous layer coating process (8B) is a process of forming an inorganic porous layer comprising inorganic particles and a resin binder on at least one side of the surface of the microporous membrane obtained above. The coating process (8B) can be performed while maintaining the silane crosslinking property of the silane-modified polyolefin.
[0876] The B layer described above can also be formed by performing a coating process (8B). Known manufacturing methods can be used as methods for forming the B layer. Examples of methods for producing a laminate including the A layer and the B layer include: coating the A layer with a slurry containing inorganic particles; co-extruding the raw materials for the B layer and the A layer; and bonding the A layer and the B layer together after they have been separately manufactured.
[0877] Inorganic porous layers can be formed, for example, by coating a slurry comprising inorganic particles, a resin binder, water or an aqueous solvent (e.g., a mixture of water and alcohol), and a dispersant as desired, onto at least one side of the surface of a microporous membrane. The inorganic particles, resin binder, and dispersant can be as described in the first to tenth embodiments.
[0878] As a solvent contained in the slurry, a solvent that can uniformly and stably disperse or dissolve inorganic particles is preferred. Examples of such solvents include: N-methylpyrrolidone (NMP), N,N-dimethylformamide, N,N-dimethylacetamide, water, ethanol, toluene, hot xylene, dichloromethane, and hexane.
[0879] Methods for preparing slurries containing inorganic particles include, for example, mechanical stirring methods based on ball mills, bead mills, planetary ball mills, vibratory ball mills, sand mills, colloid mills, grinding mills, roller mills, high-speed impeller dispersers, dispersers, homogenizers, high-speed impact mills, ultrasonic dispersers, stirring blades, etc.
[0880] Examples of coating methods for slurries containing inorganic particles include: photogravure coating, small-diameter photogravure coating, reverse roller coating, transfer roller coating, mating coating, dip coating, knife coating, air knife coating, doctor blade coating, bar coating, extrusion coating, cast coating, die coating, screen printing, and spray coating.
[0881] Methods for removing solvent from the coating film include: drying at a temperature below the melting point of the material constituting the microporous film, and drying under reduced pressure at low temperature. Furthermore, a portion of the solvent may remain if it does not significantly affect the characteristics of the apparatus.
[0882] [Winding / Slitting Process]
[0883] The winding process is the process of cutting and winding the obtained microporous membrane or microporous membrane coated with an inorganic porous layer onto a specified core as needed.
[0884] [Energy Storage Device Assembly Process]
[0885] The assembly process of the energy storage device is as follows: a separator precursor (hereinafter also referred to as the silane crosslinking precursor) that maintains the crosslinking properties of silane and electrodes are laminated to form a laminate; the laminate is further wound to form a wound body as desired; the laminate or wound body and a non-aqueous electrolyte are housed in the outer casing, so that the silane crosslinking precursor comes into contact with the non-aqueous electrolyte. Through the energy storage device assembly process, membrane loss of the microporous membrane can be suppressed, its morphology maintained, and the permeation of polyolefin resin from the microporous membrane into the inorganic porous layer can be suppressed, thereby improving the stress resistance of the energy storage device or separator.
[0886] The silane-modified polyolefin is cross-linked during or after the energy storage device assembly process (9), thus enabling the safety of the energy storage device to be improved by initiating a silane cross-linking reaction of the separator after the energy storage device is manufactured, while being compatible with existing energy storage device manufacturing processes.
[0887] In the assembly process of an energy storage device, from the perspective of electrolyte handling, it is preferable to house the laminate or winding body in the outer casing and then inject a non-aqueous electrolyte into the outer casing, or to inject electrolyte into the outer casing and then house the laminate or winding body in the outer casing.
[0888] From the perspective of promoting the cross-linking reaction of the separator, the electrolyte for non-aqueous electrolytes can be lithium salts containing fluorine (F) such as LiPF6 that produce hydrogen fluoride (HF), electrolytes with non-shared electron pairs such as LiN(SO2CF3)2 and LiSO3CF3, or LiBF4, LiBC4O8 (LiBOB), etc.
[0889] While not wishing to impose theoretical constraints, it is presumed that the methoxysilane grafted portion, due to trace amounts of moisture contained within the energy storage device (moisture contained in components such as electrodes, separators, and electrolytes), transforms into silanol, undergoing a cross-linking reaction and changing into siloxane bonds. Furthermore, it can be assumed that once the electrolyte or electrolyte comes into contact with the electrodes, substances that catalyze the silane cross-linking reaction are generated in the electrolyte or on the electrode surface. These substances dissolve in the electrolyte and uniformly swell and diffuse into the amorphous portions of the polyolefin containing the silane-modified grafted portion, thereby uniformly promoting the cross-linking reaction of the laminated or wound body containing the separator. The substances catalyzing the silane cross-linking reaction can be in the form of an acid solution or a membrane. In the case where the electrolyte contains lithium hexafluorophosphate (LiPF6), these substances can be HF generated from the reaction of LiPF6 with moisture, or fluorinated organic compounds derived from HF.
[0890] From the perspective of the efficiency of the silane crosslinking reaction, it is preferable to house the laminated or wound body and the non-aqueous electrolyte within the casing of the energy storage device, and then connect lead terminals to the electrodes for at least one charge-discharge cycle. It can be considered that through charge-discharge cycles, substances that catalyze the silane crosslinking reaction are generated in the electrolyte or on the electrode surface, thereby realizing the silane crosslinking reaction. Cyclic charge-discharge can be performed using known methods and apparatus, specifically the methods described in the examples.
[0891] [Manufacturing method for energy storage devices]
[0892] Another aspect of the present invention is a method for manufacturing an energy storage device.
[0893] <Twelfth Implementation Method>
[0894] The method for manufacturing an energy storage device according to the twelfth embodiment includes the following steps;
[0895] (I) The process of preparing the energy storage device assembly kit described above;
[0896] (II) A process of initiating the silane crosslinking reaction of silane-modified polyolefin by contacting the separator in element (1) of the energy storage device assembly kit with the non-aqueous electrolyte in element (2).
[0897] (III) The process of connecting lead terminals to the electrodes of element (1) as desired; and
[0898] (IV) As desired, perform at least one cycle of charge and discharge.
[0899] Steps (I) to (IV) can be performed by methods known in the art, except for using the separator for the energy storage device of this embodiment. Furthermore, in steps (I) to (IV), positive electrode, negative electrode, electrolyte, casing and charging / discharging device known in the art can be used.
[0900] For step (I), a longitudinally elongated separator with a width of 10–500 mm (preferably 80–500 mm) and a length of 200–4000 m (preferably 1000–4000 m) can be manufactured. Next, in step (I), a wound body is obtained by stacking the separators in the order of positive electrode-separator-negative electrode-separator or negative electrode-separator-positive electrode-separator and winding them into a circular or flat spiral. In steps (II) and (III), an energy storage device can be manufactured by further injecting a non-aqueous electrolyte into a device container (e.g., a battery container) after accommodating the wound body. Alternatively, an energy storage device can be manufactured by inserting a wound body made by folding electrodes and separators into a device container (e.g., an aluminum film) and injecting a non-aqueous electrolyte.
[0901] At this point, the wound body can be pressed. Specifically, the separator and the electrode having a current collector and an active material layer formed on at least one side of the current collector can be overlapped and pressed.
[0902] Regarding the pressing temperature, a temperature that effectively exhibits adhesion is preferably 20°C or higher. Furthermore, from the perspective of suppressing clogging or thermal shrinkage of the pores in the separators caused by hot pressing, the pressing temperature is preferably lower than the melting point of the material contained in the microporous membrane, more preferably 120°C or lower. From the perspective of suppressing clogging of the pores in the separators, the pressing pressure is preferably 20 MPa or lower. Regarding the pressing time, when using roller pressing, it can be less than 1 second or several hours of surface pressing; from a productivity perspective, 2 hours or lower is preferred.
[0903] By performing the above manufacturing process, it is possible to suppress the press-back during the pressing and forming of the winding body composed of electrodes and separators. Therefore, it is preferable to suppress the decrease in yield during the device assembly process and shorten the production process time.
[0904] From the perspective of reliably performing the silane crosslinking reaction of the separator after step (II), steps (III) and (IV) are preferred. It is believed that through charge-discharge cycles, substances that catalyze the silane crosslinking reaction are generated in the electrolyte or on the electrode surface, thereby realizing the silane crosslinking reaction.
[0905] For example, in the manufacturing method of the separator, if the manufacturing method of layer A described above does not include the silane crosslinking process, the crosslinking reaction can be actively promoted by contacting the separator with a non-aqueous electrolyte. While it is not intended to be theoretically restrictive, it is presumed that the silane-modified grafted portion will be converted into silanols due to the trace amounts of moisture contained within the energy storage device (slightly contained in the electrodes, separators, non-aqueous electrolyte, etc.), undergoing a crosslinking reaction and changing into siloxane bonds. Furthermore, it is believed that once the non-aqueous electrolyte comes into contact with the electrode, a substance that catalyzes the silane crosslinking reaction is generated in the non-aqueous electrolyte or on the electrode surface. It is believed that this substance, which catalyzes the silane crosslinking reaction, dissolves in the non-aqueous electrolyte and uniformly swells and diffuses into the amorphous portions of the polyolefin present in the silane-modified grafted portion, thereby uniformly promoting the crosslinking reaction of the laminate or winding containing the separator.
[0906] The catalyst for the silane crosslinking reaction can be in the form of an acid solution or a membrane. When the electrolyte contains lithium hexafluorophosphate (LiPF6), LiPF6 reacts with water, and the resulting hydrogen fluoride (HF) or fluorinated organic compounds derived from hydrogen fluoride (HF) are considered to be the catalysts for the silane crosslinking reaction (compounds generated within the energy storage device).
[0907] <Thirteenth Implementation Method>
[0908] The thirteenth embodiment is a method for manufacturing an energy storage device using a separator containing a polyolefin having one or more functional groups, and includes the following steps:
[0909] (1) A crosslinking process in which functional groups undergo a condensation reaction, or (2) a reaction between functional groups and chemical substances inside an energy storage device, or (3) a reaction between functional groups of polyolefins and other types of functional groups, thereby forming a crosslinking structure.
[0910] The crosslinking process can be carried out in the same way as the reaction that forms the crosslinking structure of the separator described above. Furthermore, since the crosslinking process can be carried out using the compounds inside the energy storage device and the environment around the device, excessive conditions such as electron beams and high temperatures above 100°C are not required, and mild conditions such as temperatures of 5°C to 90°C and / or ambient atmosphere can be used.
[0911] By incorporating a crosslinking process into the manufacturing process of the energy storage device, the formation of the crosslinking structure can be omitted during or immediately after the film-forming process of the separator. This can relax or eliminate stress and strain after the energy storage device is manufactured, and / or impart a crosslinking structure to the separator even without using high energy such as light irradiation or heating, thereby reducing uneven crosslinking, the generation of unmelted resin aggregates, and environmental burden.
[0912] In the crosslinking process, by (2) reacting the functional groups with the chemical substances inside the energy storage device, or by (3) reacting the functional groups of the polyolefin with other types of functional groups, a crosslinking structure is formed not only inside the separator, but also between the separator and the electrode or between the separator and the solid electrolyte interface (SEI), which can improve the strength between multiple components of the energy storage device.
[0913] The separator described above cross-links with silane-modified polyolefins when in contact with the electrolyte. Therefore, it can initiate a silane cross-linking reaction after the energy storage device is manufactured, while being suitable for existing energy storage device manufacturing processes, thereby improving the safety of the energy storage device.
[0914] Example
[0915] Examples and comparative examples are given to illustrate the present invention in more detail, but the present invention is not limited to the following examples as long as it does not depart from its spirit. It should be noted that the physical properties in the examples were determined by the following methods.
[0916] <Weight-average molecular weight>
[0917] Using a Waters ALC / GPC 150C (trademark) chromatogram, standard polystyrene was measured under the following conditions to create a calibration curve. Additionally, for the following polymers, chromatograms were measured under the same conditions, and the weight-average molecular weight of each polymer was calculated based on the calibration curve using the following method.
[0918] Chromatographic columns: 2 GMH6-HT (trademark) columns + 2 GMH6-HTL (trademark) columns manufactured by Tosoh Corporation
[0919] Mobile phase: o-dichlorobenzene
[0920] Detector: Differential refractometer
[0921] Flow rate: 1.0 ml / min
[0922] Column temperature: 140℃
[0923] Sample concentration: 0.1 wt%
[0924] (Weight-average molecular weight of polyethylene)
[0925] The molecular weight distribution curve of polyethylene is obtained by multiplying each molecular weight component in the obtained calibration curve by 0.43 (Q factor of polyethylene / Q factor of polystyrene = 17.7 / 41.3), and the weight-average molecular weight is calculated.
[0926] (Weight-average molecular weight of the resin composition)
[0927] The Q factor value of the polyolefin with the largest mass fraction is used, and the weight-average molecular weight is calculated in the same manner as for polyethylene.
[0928] <Viscosity-average molecular weight (Mv)>
[0929] Based on ASTM-D4020, determine the intrinsic viscosity [η] of polyethylene at 135°C in decahydronaphthalene solvent. Calculate the Mv of polyethylene using the following formula.
[0930] [η] = 6.77 × 10 -4 Mv 0.67
[0931] Melt mass flow rate (MFR) (g / 10min)
[0932] The MFR value is determined by the weight of the resin extruded for 10 minutes at 190°C and under a load of 2.16 kg using a melt flow rate tester (MELT INDEXER F-F01) manufactured by Toyo Seiki Co., Ltd.
[0933] <Determination of Glass Transition Temperature>
[0934] Take an appropriate amount of the aqueous dispersion containing the resin sample (solid content = 38-42% by weight, pH = 9.0) into an aluminum dish and dry it in a hot air dryer at 130°C for 30 minutes to obtain a dried film. Fill approximately 17 mg of this dried film into an aluminum container for analysis, and obtain the DSC curve and DSC profile under a nitrogen atmosphere using a DSC apparatus (manufactured by Shimadzu Corporation, model "DSC6220"). The analysis conditions are as described below.
[0935] The first heating stage: Start at 70℃ and increase the temperature at a rate of 15℃ per minute. Maintain the temperature at 110℃ for 5 minutes.
[0936] The second cooling procedure: starting from 110℃, the temperature drops at a rate of 40℃ per minute. After reaching -50℃, maintain this temperature for 5 minutes.
[0937] The third temperature ramp-up program: Starting from -50°C, the temperature is increased to 130°C at a rate of 15°C per minute. DSC and DDSC data are obtained during this third temperature ramp-up.
[0938] The intersection of the baseline (the straight line obtained by extending the baseline of the obtained DSC curve towards the high temperature side) and the tangent at the inflection point (the point where the upper convex curve changes into the lower convex curve) is taken as the glass transition temperature (Tg).
[0939] <Film thickness (μm)>
[0940] The film thickness of the microporous membrane or separator is measured with KBM (trademark), a micro-thickness gauge manufactured by Toyo Seiki Seisaku-sho, Ltd., at a room temperature of 23±2°C and a relative humidity of 60%. Specifically, the film thickness is measured at 5 points at substantially equal intervals along the entire width in the TD direction, and the average value thereof is obtained. The thickness of the inorganic porous layer can be calculated by subtracting the thickness of the microporous membrane from the thickness of the separator composed of the microporous membrane and the inorganic porous layer.
[0941] <Thickness of layer A (TA), and thickness of layer B (TB)>
[0942] The thickness of layer A (TA) is measured with KBM (trademark), a micro-thickness gauge manufactured by Toyo Seiki Seisaku-sho, Ltd., at a room temperature of 23±2°C and a relative humidity of 60%. Specifically, the film thickness is measured at 5 points at substantially equal intervals along the entire width in the TD direction, and the average value thereof is obtained. In addition, the thickness of the laminate including layer A and layer B is obtained by the same method. Then, the thickness of layer B (TB) is obtained by subtracting the thickness of layer A (TA) from the thickness of the obtained laminate.
[0943] The thickness of the obtained laminate is regarded as the total thickness of layer A and layer B (TA+TB). In addition, the thickness ratio (TA / TB) is obtained by dividing the thickness (TA) by the thickness (TB).
[0944] <Porosity (%)>
[0945] (i) Calculated from the density of the mixed composition
[0946] A square test sample of 10 cm × 10 cm is cut from the microporous membrane, and its volume (cm 3 ) and mass (g) are obtained, and the porosity is calculated by the following formula based on these values and the density (g / cm 3 ). It should be noted that the density of the mixed composition adopts a value calculated and obtained according to the respective densities and mixing ratios of the raw materials used.
[0947] Porosity (%) = (Volume - Mass / Density of mixed composition) / Volume × 100
[0948] (ii) Calculated from the membrane density
[0949] Alternatively, the porosity of the microporous membrane is calculated from the volume, mass and membrane density (g / cm 3 ) by the following formula.
[0950] Porosity (%) = (Volume - Mass / Membrane density) / Volume × 100
[0951] It should be noted that in the present invention, the membrane density refers to a value measured according to the D) density gradient tube method described in JIS K7112 (1999).
[0952] (iii) Porosity of layer A
[0953] A 10 cm × 10 cm square sample is cut from layer A, and its volume (cm 3 ) and mass (g) are determined. Based on these values and the density (g / cm 3 ), the porosity is calculated using the following formula. The density of the mixed composition is a value calculated and determined based on the respective densities and mixing ratios of the raw materials used.
[0954] Porosity (%) = (volume - mass / density of mixed composition) / volume × 100
[0955] <Air permeability (sec / 100 cm 3 )>
[0956] In accordance with JIS P-8117 (2009), the air permeability of the sample or layer A is measured using a GURLEY-type permeability tester G-B2 (trademark) manufactured by Toyo Seiki Seisaku-sho, Ltd.
[0957] <Puncture Strength of Layer A>
[0958] Layer A is fixed with a sample holder having an opening with a diameter of 11.3 mm using a hand-held compression tester KES-G5 (model) manufactured by KATO TECH Co., Ltd. Next, a puncture test is performed on the central portion of the fixed layer A using a needle with a tip curvature radius of 0.5 mm at a puncture speed of 2 mm / sec in an atmosphere at 25°C, thereby measuring the maximum puncture load. The maximum puncture load is converted into a value corresponding to a thickness of 20 µm, and this value is taken as the puncture strength (gf / 20µm). When the thermoplastic polymer is only present on one side of the substrate, the needle may be punctured from the side where the thermoplastic polymer is present.
[0959] <Quantification of Resin Agglomerates in Separators
[0960] Resin agglomerates in a separator are defined as opaque regions having an area of 100 µm in length × 100 µm in width or more when the separator obtained through the film-forming process in the examples and comparative examples described below is observed with a transmission optical microscope. In observation using a transmission optical microscope, the number of resin agglomerates per 1000 m 2 of separator area is counted.
[0961] <Storage Modulus, Loss Modulus and Transition Temperature (version 1)>
[0962] By using a dynamic viscoelasticity measuring device to measure the dynamic viscoelasticity of the separator, the storage modulus (E'), loss modulus (E”), and the transition temperature between the rubbery flat region and the crystalline molten flow region can be calculated. The storage modulus change ratio (R) is also calculated. ΔE’ According to the following formula (1), the hybrid energy storage modulus ratio (R) E’mix According to the following formula (2), the change ratio of loss modulus (R) ΔE” According to the following formula (3), the mixed loss modulus ratio (R) E”mix ) Calculate according to the following formula (4). It should be noted that the measurement conditions are as follows (i) to (iv).
[0963] (i) Dynamic viscoelasticity was measured under the following conditions:
[0964] Atmosphere: Nitrogen
[0965] • Measuring apparatus used: RSA-G2 (manufactured by TA Instruments)
[0966] • Sample film thickness: 5 μm to 50 μm
[0967] • Measurement temperature range: -50~225℃
[0968] • Heating rate: 10℃ / min
[0969] • Measurement frequency: 1 Hz
[0970] • Deformation mode: Linear tension mode
[0971] Initial static tensile load: 0.5 N
[0972] • Initial gap distance (at 25℃): 25mm
[0973] • Automatic strain adjustment: Enabled (range: amplitude value 0.05~25%, sinusoidal load 0.02~5N).
[0974] (ii) Static tensile load refers to the midpoint between the maximum and minimum stress under each periodic motion, and sinusoidal load refers to the vibration stress centered on the static tensile load.
[0975] (iii) The sinusoidal tensile mode refers to measuring vibration stress while performing periodic motion with a fixed amplitude of 0.2%. In this mode, the vibration stress is measured by changing the gap distance and the static tensile load in a manner where the difference between the static tensile load and the sinusoidal load is within 20%. It should be noted that when the sinusoidal load is below 0.02N, the vibration stress is measured by increasing the amplitude value by a sinusoidal load of within 5N and an increase in amplitude value of within 25%.
[0976] (iv) Calculate the storage modulus and loss modulus based on the obtained relationship between the sinusoidal load and the amplitude value, and the following formula:
[0977] σ * =σ0·Exp[i(ωt+δ)]、
[0978] ε * =ε0·Exp(iωt),
[0979] σ * =E * ·ε *
[0980] E * =E'+iE”
[0981] In the formula, σ * Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * E': complex modulus; E”: energy storage modulus; E”: loss modulus
[0982] Vibration stress: sinusoidal load / initial cross-sectional area
[0983] Static tensile load: The load at the point of minimum vibration stress (the point of minimum gap distance within each period) during each cycle.
[0984] Sine wave load: the difference between the measured vibration stress and the static tensile load.
[0985] E' S and E' j and E” S and E” j The average value of each storage modulus or loss modulus at 160℃~220℃ is obtained from dynamic viscoelastic measurement data. E' a and E'0 and E” a E”0 uses the average value of each storage modulus or loss modulus at 160℃~220℃ from the dynamic viscoelastic measurement data.
[0986] R ΔE’ =E'S / E' j (1) Comparison before and after battery insertion
[0987] R E’mix =E' a / E'0 (2) Comparison of silane crosslinking with and without
[0988] R ΔE” =E” S / E” j (3) Comparison before and after battery insertion
[0989] R E”mix =E” a / E”0 (4) Comparison of silane crosslinking with and without
[0990] An example of a graph used to illustrate the relationship between temperature and energy storage modulus is shown below. Figure 1 .like Figure 1 As shown, comparing the energy storage modulus of a standard membrane (excluding silane-modified polyolefin separators for energy storage devices) and a cross-linked membrane within a temperature range of -50℃ to 225℃ demonstrates that... Figure 1 The transition temperature between the rubbery flat region and the crystalline melting and flow region was confirmed. It should be noted that the transition temperature is the temperature at the intersection of the straight line obtained by extending the baseline from the high-temperature side to the low-temperature side and the tangent line drawn at the inflection point of the curve in the crystalline melting and change region.
[0991] An example of a graph illustrating the relationship between temperature and loss modulus is shown below. Figure 2 . Figure 2 In the comparison of the loss modulus of a standard membrane (a separator for an energy storage device without silane-modified polyolefin) and a cross-linked membrane within a temperature range of -50℃ to 220℃, it is shown that... Figure 1 The transition temperature was determined using the same method. In this technical field, the storage modulus and loss modulus can be interchanged according to the following formula:
[0992] tanδ=E” / E'
[0993] {In the formula, tanδ represents the loss tangent, E' represents the energy storage modulus, and E” represents the loss modulus.}
[0994] It should be noted that the hybrid energy storage modulus ratio (R) E’mix ) or mixed loss modulus ratio (R E”mix In the determination of E', a microporous membrane made of silane-unmodified polyolefin with a gelation degree of approximately 0% was used as a separator for an energy storage device without silane-modified polyolefin. Furthermore, regarding E' a 、E'0、E” aE”0, in the case where no fracture of the sample is observed at 160℃~220℃ (elastic modulus decreases sharply), is calculated based on the average value from 160℃~220℃. In the case where the sample fractures at 160℃~220℃, it is calculated based on the average value from 160℃ to the temperature at the fracture point. For example Figure 1 and 2 The standard membrane shown broke at 207°C.
[0995] <Storage modulus, loss modulus, and transition temperature (version 2)>
[0996] By using a dynamic viscoelasticity measuring device to measure the dynamic viscoelasticity of the separator, the storage modulus (E'), loss modulus (E”), and the transition temperature between the rubbery flat region and the crystalline molten flow region can be calculated. The storage modulus change ratio (R) is also calculated. ΔE’X According to the following formula (1), the hybrid energy storage modulus ratio (R) E’mix According to the following formula (2), the mixed loss modulus ratio (R) E”X According to the following formula (3), the mixed loss modulus ratio (R) E”mix The values are calculated according to the following formula (4). It should be noted that, regarding the measurement conditions, a TA Instruments-manufactured RSA-G2 dynamic viscoelasticity measuring device was used, the measurement frequency was 1 Hz, the strain was 0.2%, and the temperature range was -50℃ to 310℃ under a nitrogen atmosphere. For other conditions, the storage modulus and loss modulus were measured according to version 1 above. Z and E' Z0 and E” Z and E” Z0 The average values of each storage modulus or loss modulus at 160℃ to 300℃ are used from the dynamic viscoelastic measurement data. E' and E'0, as well as E” and E”0, are the average values of each storage modulus or loss modulus at 160℃ to 300℃ from the dynamic viscoelastic measurement data.
[0997] R ΔE’X =E' Z / E' Z0 (1) Comparison before and after battery insertion
[0998] R E’mix =E' / E'0 (2) Comparison of the presence and absence of amorphous cross-linked structures
[0999] R E”X =E” Z / E” Z0 (3) Comparison before and after battery insertion
[1000] R E”mix=E” / E”0 (4) Comparison of the presence and absence of amorphous cross-linked structures
[1001] An example of a graph used to illustrate the relationship between temperature and energy storage modulus is shown below. Figure 9 .like Figure 9 As shown, by comparing the energy storage modulus of a standard membrane (a separator for energy storage devices without amorphous cross-linked structures) and a cross-linked membrane within a temperature range of -50℃ to 310℃, it can be seen that... Figure 9 The transition temperature between the rubbery flat region and the crystalline melting and flow region was confirmed. It should be noted that the transition temperature is the temperature at the intersection of the straight line obtained by extending the baseline from the high-temperature side to the low-temperature side and the tangent line drawn at the inflection point of the curve in the crystalline melting and change region.
[1002] An example of a graph illustrating the relationship between temperature and loss modulus is shown below. Figure 10 .exist Figure 10 In the comparison of the loss modulus of a standard membrane (a separator for an energy storage device without silane-modified polyolefin) and a cross-linked membrane within a temperature range of -50℃ to 310℃, it is shown that by comparing with Figure 9 The transition temperature was determined using the same method. In this technical field, the storage modulus and loss modulus can be interchanged according to the following formula:
[1003] tanδ=E” / E'
[1004] {In the formula, tanδ represents the loss tangent, E' represents the energy storage modulus, and E” represents the loss modulus.}
[1005] It should be noted that the hybrid energy storage modulus ratio (R) E’mix ) or mixed loss modulus ratio (R E”mix In the determination of E', a microporous membrane made of polyolefin with a gelation degree of approximately 0% was used as a separator for an energy storage device without amorphous cross-linked structure. Furthermore, regarding E', E'0, E”, and E”0, in cases where no fracture of the sample was observed at 160℃ to 300℃ (elastic modulus decreased sharply), the values were calculated based on the average values from 160℃ to 300℃; in cases where fracture occurred at 160℃ to 300℃, the values were calculated based on the average values from 160℃ to the fracture point. For example, Tables 11 and 12, and... Figure 9 and Figure 10 The standard membrane shown broke at 210°C.
[1006] In this specification, the separator for an energy storage device that does not have an amorphous cross-linked structure can be a separator manufactured from any one of the following groups: polyethylene: X (viscosity average molecular weight 100,000 to 400,000), PE: Y (viscosity average molecular weight 400,000 to 800,000), and PE: Z (viscosity average molecular weight 800,000 to 9,000,000), or two or three of the following groups: X, Y, and Z, mixed in any proportion. It should be noted that polyolefins consisting only of a hydrocarbon backbone, such as low-density polyethylene: LDPE, linear low-density polyethylene: LLDPE, polypropylene: PP, and olefin-based thermoplastic elastomers, can be added to the mixed composition. More specifically, the separator for an energy storage device that does not have an amorphous cross-linked structure can refer to a microporous membrane made of polyolefin with a change rate of solid content (hereinafter referred to as "degree of gelation") of less than 10% before and after heating in a decahydronaphthalene solution at 160°C. It should be noted that when measuring the degree of gelation, the solid content refers only to the resin and does not include inorganic substances or other materials.
[1007] On the other hand, the degree of gelation of the polyolefin microporous membrane having amorphous cross-linked structures such as silane cross-linking structure is preferably 30% or more, and more preferably 70% or more.
[1008] <Storage modulus, loss modulus, membrane softening transition temperature, and membrane fracture temperature (version 3)>
[1009] By using a dynamic viscoelasticity measuring device to measure the solid viscoelasticity of the separator, the storage modulus (E'), loss modulus (E”), and film softening transition temperature can be calculated. It should be noted that the conditions for the solid viscoelasticity measurement are as follows (i) to (iv).
[1010] (i) Dynamic viscoelasticity was measured under the following conditions:
[1011] • Measuring apparatus used: RSA-G2 (manufactured by TA Instruments)
[1012] • Sample film thickness: 200μm~400μm (wherein, if the film thickness of a single sample is less than 200μm, multiple samples are stacked to achieve a total thickness in the range of 200μm~400μm for dynamic viscoelasticity determination.)
[1013] • Measurement temperature range: -50℃~250℃
[1014] • Heating rate: 10℃ / min
[1015] • Measurement frequency: 1Hz
[1016] • Deformation mode: Linear tension mode
[1017] Initial value of static tensile load: 0.2N
[1018] • Initial gap distance (at 25℃): 10mm
[1019] • Automatic strain adjustment: Disabled.
[1020] (ii) Static tensile load refers to the midpoint between the maximum and minimum stress under each periodic motion, and sinusoidal load refers to the vibration stress centered on the static tensile load.
[1021] (iii) The sinusoidal stretching mode refers to measuring the vibration stress while performing periodic motion with a fixed amplitude of 0.1%. In the sinusoidal stretching mode, the vibration stress is measured by changing the gap distance and the static tensile load in such a way that the difference between the static tensile load and the sinusoidal load is within 5%. When the sinusoidal load is below 0.1N, the static tensile load is fixed at 0.1N to measure the vibration stress.
[1022] (iv) Calculate the storage modulus (E') and loss modulus (E”) based on the relationship between the obtained sinusoidal load and amplitude value and the following formula:
[1023] σ * =σ0·Exp[i(ωt+δ)]、
[1024] ε * =ε0·Exp(iωt),
[1025] σ * =E * ·ε *
[1026] E * =E'+iE”
[1027] In the formula, σ * Vibration stress, ε * : strain, i: imaginary unit, ω: angular frequency, t: time, δ: phase difference between vibration stress and strain, E * E': complex modulus; E”: energy storage modulus; E”: loss modulus
[1028] Vibration stress: sinusoidal load / initial cross-sectional area
[1029] Static tensile load: The load at the point of minimum vibration stress (the point of minimum gap distance within each period) during each cycle.
[1030] Sine wave load: the difference between the measured vibration stress and the static tensile load.
[1031] In addition, the average of the maximum value and the minimum value of E' is calculated, which is recorded as average E' (E' ave ), and the average of the maximum value and the minimum value of E" is calculated, which is recorded as average E" (E" ave ).
[1032] It should be noted that E' and E" are the maximum and minimum values of each storage modulus or each loss modulus at -50°C to 250°C in the dynamic viscoelasticity measurement data. More specifically, when no fracture of the sample (sharp decrease in elastic modulus) is observed within -50°C to 250°C, the maximum and minimum values within -50°C to 250°C are calculated; when fracture of the sample occurs within -50°C to 250°C, the value at the temperature where the fracture occurs is taken as the minimum value. In addition, in the art, the storage modulus and the loss modulus can be interconverted according to the following formula:
[1033] tanδ=E" / E'
[1034] {In the formula, tanδ represents the loss tangent, E' represents the storage modulus, and E" represents the loss modulus.}.
[1035] The membrane softening transition temperature is the temperature corresponding to the minimum value obtained by first-order differentiation of the curve of the gap distance of the sample in the dynamic viscoelasticity measurement data. In addition, the membrane breaking temperature is the temperature at which sample fracture (sharp decrease in elastic modulus) is observed in the dynamic viscoelasticity measurement data. From the perspective of the thermal decomposition reaction of polyolefin resin, the measurement limit temperature is sometimes set to 250°C. However, the phenomenon can also be equivalently understood through measurement at a high temperature higher than 250°C, so this embodiment can implement a separator for an electricity storage device having a membrane breaking temperature of 180°C or higher.
[1036] <Membrane breaking temperature of layer A>
[1037] Using the constant length mode of TMA50 (trademark) manufactured by Shimadzu Corporation, the ambient temperature is varied between 25°C and 250°C, and the temperature at the moment when the load is completely released is determined as the TMA membrane breaking temperature (the membrane breaking temperature of layer A measured by TMA).
[1038] Specifically, a sample piece with a TD of 3 mm and a MD of 14 mm (a sample piece with MD as the long side) is taken from layer A. Both ends of the MD of the sample piece are mounted on a special probe with a distance between clamps of 10 mm, and a load of 1.0 g is applied to the sample piece. The furnace carrying the test piece is heated, and the temperature at which the load shows 0 g is taken as the membrane breaking temperature (°C).
[1039] It should be noted that when measuring the sample piece TD with TD as the long side, take TD14mm and MD3mm from layer A and use them as the sample piece. Clamp both ends of TD with a special probe, set the distance between the clamps to 10mm, apply an initial load of 1.0g, and perform the same operation as above.
[1040] <Heat shrinkage rate at 150℃>
[1041] Take TD100mm and MD100mm from the laminate (including layer A and layer B) before the cross-linking structure is formed, and use it as a sample sheet. Place the sample sheet in an oven at 150°C for 1 hour. During this time, sandwich the sample sheet between two sheets of paper to prevent hot air from directly blowing onto it. After removing the sample sheet from the oven and cooling it, measure the area of the sample sheet and calculate the thermal shrinkage rate (T1) at 150°C before the cross-linking structure is formed using the following formula.
[1042] Heat shrinkage rate (%) at 150℃ = (10,000 (mm) 2 - Area of the heated sample piece (mm²) 2 ))×100 / 10,000
[1043] In addition, for the laminate after the cross-linking structure is formed, TD100mm and MD100mm are taken as sample pieces and the same operation as above is performed to calculate the thermal shrinkage rate (T2) at 150°C after the cross-linking structure is formed.
[1044] Then, the ratio (T2 / T1) is obtained by dividing the heat shrinkage rate (T2) by the heat shrinkage rate (T1). The value of this ratio (T2 / T1) corresponds to the change factor of the heat shrinkage rate (T2) at 150°C after the formation of the cross-linked structure relative to the heat shrinkage rate (T1) at 150°C before the formation of the cross-linked structure.
[1045] <Battery Damage Safety Test 1>
[1046] Battery safety test 1 involves driving a nail through a 4.5V battery at a speed of 20mm / sec to induce an internal short circuit. This test clarifies the phenomena of an internal short circuit by measuring the time-varying voltage drop and surface temperature rise caused by the short circuit. Furthermore, due to inadequate sealing of the separator or membrane rupture at low temperatures during an internal short circuit, the battery may sometimes overheat, leading to electrolyte ignition, smoke, and / or explosion.
[1047] (The fabrication of the battery used in Battery Destruction Safety Test 1)
[1048] 1a. Production of the positive electrode
[1049] A slurry was prepared by dispersing 92.2% by mass of lithium cobalt composite oxide (LiCoO2) as the positive electrode active material, 2.3% by mass each of flake graphite and acetylene black as conductive materials, and 3.2% by mass of polyvinylidene fluoride (PVDF) as a resin binder in N-methylpyrrolidone (NMP). The slurry was then coated onto one side of a 20 μm thick aluminum foil constituting the positive electrode current collector using a die coater. After drying at 130°C for 3 minutes, the foil was compressed and shaped using a roller press. At this point, the coating weight of the positive electrode active material was adjusted to 250 g / m². 2 The bulk density of the active substance was adjusted to 3.00 g / cm³. 3 .
[1050] 1b. Production of the negative electrode
[1051] A slurry was prepared by dispersing 96.9% by mass of artificial graphite (as the negative electrode active material), 1.4% by mass of ammonium salt of carboxymethyl cellulose (as a resin binder), and 1.7% by mass of styrene-butadiene copolymer latex in purified water. The slurry was coated onto one side of a 12 μm thick copper foil constituting the negative electrode current collector using a die coater. After drying at 120°C for 3 minutes, it was compressed and shaped using a roller press. At this point, the coating amount of the active material for the negative electrode was adjusted to 106 g / m². 2 The bulk density of the active substance was adjusted to 1.35 g / cm³. 3 .
[1052] 1c. Preparation of non-aqueous electrolytes
[1053] A non-aqueous electrolyte was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate and methyl ethyl carbonate in a volume ratio of 1:2 to achieve a concentration of 1.0 mol / L.
[1054] 1d. Battery assembly
[1055] Cut separators to a width (TD) of 60 mm and a length (MD) of 1000 mm. Fold the separators repeatedly, alternating layers of positive and negative electrodes between the separators (12 positive electrodes and 13 negative electrodes). Note that the positive electrode uses a material with an area of 30 mm × 50 mm, and the negative electrode uses a material with an area of 32 mm × 52 mm. Place the repeatedly folded stack into a laminated bag, inject the non-aqueous electrolyte obtained in step c above, and seal it. After standing at room temperature for one day, charge the battery at 3 mA (0.5C) to a battery voltage of 4.2V at 25°C. Once reached, maintain the voltage at 4.2V while gradually decreasing the current from 3 mA. Perform this initial charge for 6 hours after battery fabrication. Then, discharge the battery at 3 mA (0.5C) to a battery voltage of 3.0V.
[1056] (Maximum heating rate)
[1057] After the nail is driven through the battery, the maximum heating rate is determined by measuring the surface temperature of the battery with a thermocouple for 300 seconds and using a temperature change chart.
[1058] (Voltage drop time)
[1059] The time required for the voltage to drop from 4.5V to 3V after the nail is driven through the battery is defined as the voltage drop time (the time it takes to drop to 3V).
[1060] <Cyclic performance evaluation and battery manufacturing method>
[1061] The battery for cycle performance evaluation is manufactured according to the same method as 1a. to 1c. of the battery manufacturing method used in the above-mentioned item <Battery Destruction Safety Test 1>, but assembled according to 1d-2. below.
[1062] 1d-2. Battery Assembly
[1063] The separator was cut into circles with a diameter of 18 mm, and the positive and negative electrodes were cut into circles with a diameter of 16 mm. The positive electrode, separator, and negative electrode were stacked sequentially with their active material surfaces facing each other, and housed in a covered stainless steel container. The container and lid were insulated from each other; the container was in contact with the copper foil of the negative electrode, and the lid was in contact with the aluminum foil of the positive electrode. The non-aqueous electrolyte obtained in 1c. of the <Battery Destruction Safety Test 1> above was poured into the container and sealed. After being left at room temperature for one day, the battery was charged at 3 mA (0.5C) to a voltage of 4.2V at 25°C. Once reached, the current was gradually reduced from 3 mA while maintaining the voltage at 4.2V. This initial charging was performed for a total of 6 hours. Then, the battery was discharged at 3 mA (0.5C) to a voltage of 3.0V.
[1064] The resulting battery underwent 100 charge-discharge cycles at 60°C. Charging was performed at a current of 6.0 mA (1.0C) until the battery voltage reached 4.2V. After reaching this voltage, the current was gradually reduced from 6.0 mA while maintaining 4.2V, and this charging process was repeated for a total of 3 hours. Discharging was performed at a current of 6.0 mA (1.0C) until the battery voltage reached 3.0V.
[1065] (Cyclic Characteristic Evaluation 1)
[1066] The capacity retention rate is calculated based on the discharge capacity of the 100th cycle and the discharge capacity of the 1st cycle. A high capacity retention rate is considered to indicate good cycling characteristics.
[1067] (Cyclic performance evaluation 2)
[1068] Based on the discharge capacity of the 300th cycle and the discharge capacity of the 1st cycle, the capacity retention rate (%) is calculated using the following formula. A high capacity retention rate is considered to indicate good cycling characteristics.
[1069] Evaluation result (%) = (Retention capacity after 100 × 300 cycles / Discharge capacity in the first cycle)
[1070] <Fusing / Melting Debris (F / MD) Characteristics>
[1071] (i) Pressurization of 0.5 MPa and heating rate of 2 °C / min
[1072] The positive electrode, separator, and negative electrode were cut into 200mm diameter circles and overlapped. A non-aqueous electrolyte was added to the resulting laminate, allowing it to permeate the entire structure. The laminate was clamped in the center of a 600mm diameter circular aluminum heater, and a hydraulic jack was used to pressurize the heater from top to bottom to 0.5MPa, completing the preparation for the measurement. While heating the laminate with the aluminum heater at a heating rate of 2℃ / min, the resistance (Ω) between the electrodes was measured. The temperature at which the separator melted and the resistance between the electrodes increased, first exceeding 1000Ω, was taken as the melting temperature (shutdown temperature). Furthermore, heating was continued until the resistance decreased to below 1000Ω, which was taken as the melting and rupture temperature (film breaking temperature).
[1073] (ii) Maximum pressure of 10 MPa and heating rate of 15 °C / min
[1074] The positive electrode, separator, and negative electrode were cut into 200mm diameter circles. A non-aqueous electrolyte was added to the resulting laminate, allowing it to permeate the entire assembly. The laminate was clamped in the center of a 600mm diameter circular aluminum heater, and a hydraulic jack was used to apply pressure to the heater from top to bottom to 10MPa, completing the preparation for the measurement. The laminate was heated with the aluminum heater at a heating rate of 15°C / min while the resistance (Ω) between the electrodes was measured. The temperature at which the resistance first exceeded 1000Ω was taken as the shut-off temperature (°C). Furthermore, heating was continued until the resistance dropped below 1000Ω, which was taken as the melting and cracking temperature (°C).
[1075] It should be noted that for either evaluation in (i) and (ii), a resistance measuring wire is attached to the back of the aluminum foil of the positive electrode prepared in "1a. Preparation of the positive electrode" of the aforementioned item <Battery Destruction Safety Test 1> using conductive silver paste. Furthermore, a resistance measuring wire is attached to the back of the copper foil of the negative electrode prepared in "1b. Preparation of the negative electrode" of the aforementioned item <Battery Destruction Safety Test 1> using conductive silver paste. Moreover, the electrolyte containing electrolyte prepared in "1c. Preparation of the non-aqueous electrolyte" of the aforementioned item <Battery Destruction Safety Test 1> is also used for the F / MD characteristic test.
[1076] <Safety Test (Prick Test 2)>
[1077] 2a. Production of the positive electrode
[1078] The positive electrode active material is a nickel, manganese, and cobalt composite oxide (NMC) (Ni:Mn:Co = 1:1:1 (elemental ratio), density 4.70 g / cm³). 3 90.4% by mass, graphite powder (KS6) as a conductive additive (density 2.26 g / cm³) 3 1.6% by mass of number-average particle size (6.5 μm) and acetylene black powder (AB) (density 1.95 g / cm³). 3 The number-average particle size was 48 nm, 3.8% by mass, and PVDF (density 1.75 g / cm³) was used as a resin binder. 3 The materials were mixed at a ratio of 4.2% by mass and dispersed in NMP to prepare a slurry. This slurry was then coated onto one side of a 20 μm thick aluminum foil constituting the positive electrode current collector using a die coater. After drying at 130°C for 3 minutes, the foil was compressed using a roller press to form the positive electrode. At this point, the coating amount of the positive electrode active material was 109 g / m². 2 .
[1079] 2b. Construction of the negative electrode
[1080] Graphite powder A (density 2.23 g / cm³) will be used as the negative electrode active material. 3 Number-average particle size 12.7 μm) 87.6% by mass and graphite powder B (density 2.27 g / cm³) 3A slurry was prepared by dispersing 9.7% by mass of a mixture of carboxymethyl cellulose (6.5 μm) as a number-average particle size, 1.4% by mass of ammonium salt of carboxymethyl cellulose (converted to solids content) (1.83% by mass aqueous solution), and 1.7% by mass of diene rubber latex (converted to solids content) (40% by mass aqueous solution) in purified water. The slurry was then coated onto one side of a 12 μm thick copper foil constituting the negative electrode current collector using a die coater. After drying at 120°C for 3 minutes, the foil was compressed using a roller press to form the negative electrode. At this point, the coating amount of the negative electrode active material was 52 g / m². 2 .
[1081] 2c. Preparation of non-aqueous electrolytes
[1082] A non-aqueous electrolyte was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate and methyl ethyl carbonate in a volume ratio of 1:2 to achieve a concentration of 1.0 mol / L.
[1083] 2D Battery Making
[1084] Using the positive electrode, negative electrode, and non-aqueous electrolyte obtained in 2a to 2c above, as well as the separator (the separator of the embodiment or the separator of the comparative example), a laminated secondary battery with dimensions of 100mm × 60mm and a capacity of 3Ah was manufactured after being charged with constant current constant voltage (CCCV) for 3 hours under the conditions of a current value of 1A (0.3C) and a terminal battery voltage of 4.2V.
[1085] 2e. Spike Evaluation
[1086] The fabricated laminated secondary battery was placed on an iron plate in a temperature-adjustable explosion-proof chamber. The temperature inside the chamber was set to 40°C. A 3.0mm diameter iron nail was driven through the center of the laminated secondary battery at a speed of 2mm / s, maintaining the penetration. The temperature of a thermocouple, positioned to measure the internal temperature of the laminated battery after the nail has penetrated the battery, was measured to assess the possibility of ignition.
[1087] The evaluation was repeated using newly fabricated laminated secondary batteries produced in the same manner, and the number of samples that did not ignite (non-ignition) was calculated as a percentage using the following formula.
[1088] Evaluation result (%) = (100 × number of samples that did not catch fire / total number of samples)
[1089] Regarding the pass rate of spike evaluation, for example, it is preferred to be above 50% when 200 cycles are selected and above 5% when 1000 cycles are selected.
[1090] <Experimental Group I>
[1091] [Manufacturing method of silane-grafted modified polyolefins]
[1092] The raw material polyolefin used in silane graft-modified polyolefins can have a viscosity-average molecular weight (Mv) of 100,000 or more and 1,000,000 or less, a weight-average molecular weight (Mw) of 30,000 or more and 920,000 or less, and a number-average molecular weight of 10,000 or more and 150,000 or less. It can be a propylene or butene copolymer α-olefin. While the raw material polyethylene is melt-blended using an extruder, an organic peroxide (di-tert-butyl peroxide) is added. After free radicals are generated in the polymer chain of the α-olefin, trimethoxyalkylene oxide is injected to replace vinylsilane. Alkoxysilane is introduced into the α-olefin polymer through an addition reaction to form a silane graft structure. In addition, to adjust the free radical concentration in the system, an appropriate amount of antioxidant (pentaerythritol tetratetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) is added to inhibit the chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin was cooled in water, granulated, and then dried at 80°C for 2 days to remove moisture or unreacted trimethoxyalkylene oxide-substituted vinylsilane. It should be noted that the residual concentration of unreacted trimethoxyalkylene oxide-substituted vinylsilane in the granules is approximately 10–1500 ppm.
[1093] The silane-grafted modified polyethylene obtained by the above manufacturing method is used as "silane-modified polyolefin (B)" in Table 8.
[1094] [Example I-1]
[1095] To 79.2% by mass of a homopolymer polyethylene (A) with a weight average molecular weight of 500,000, 19.8% by mass of silane-grafted polyethylene (silane-modified polyethylene (B)) with an MFR (190°C) of 0.4 g / min (obtained by modification of vinylsilane by replacing vinylsilane with trimethoxyalkylene oxide using a polyolefin with a viscosity average molecular weight of 20,000 as a raw material) was added (therefore, the resin compositions of (A) and (B) were 0.8 and 0.2, respectively), and 1% by mass of pentaerythritol-tetra-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant, a mixture was obtained by dry mixing using a drum mixer. The resulting mixture was fed to a twin-screw extruder under a nitrogen atmosphere. Additionally, liquid paraffin (kinematic viscosity at 37.78°C 7.59 × 10⁻⁶) was pumped via a plunger pump. -5 m 2 / s) is injected into the extruder drum.
[1096] The mixture and liquid paraffin were melt-blended in an extruder. The feeder and pump were adjusted so that the liquid paraffin accounted for 70% by mass of the extruded polyolefin composition (i.e., the polymer concentration was 30% by mass). The melt-blending conditions were set at a temperature of 220°C, a screw speed of 240 rpm, and a discharge rate of 18 kg / h.
[1097] Next, the molten compound is extruded through a T-die onto a cooling roller with a surface temperature controlled at 25°C and then cast to obtain a gel sheet (sheet-shaped molded body) with a blank film thickness of 1400 μm.
[1098] Next, the sheet-shaped molded body is guided to a biaxial stretching machine for biaxial stretching to obtain the stretched material. The stretching conditions are set as follows: MD ratio 7.0, TD ratio 6.0 (i.e., 7×6), and biaxial stretching temperature 125℃.
[1099] Next, the stretched gel sheet is guided into a methyl ethyl ketone (MEK) bath and fully impregnated in MEK to extract and remove liquid paraffin. Then, it is dried to remove MEK and obtain a porous body.
[1100] Next, the porous body is guided to the TD stretcher for heat setting (HS) and HS is performed at a heat setting temperature of 125°C and a stretching ratio of 1.8. Then, a relaxation operation of 0.5 times in the TD direction is performed (i.e., the HS relaxation rate is 0.5 times) to obtain a microporous membrane.
[1101] Then, the ends of the obtained microporous membrane are cut off and wound into a master roll with a width of 1,100 mm and a length of 5,000 m.
[1102] During the above evaluation, the microporous membrane released from the master roll is cut as needed and used as evaluation separators.
[1103] [Examples I-2 to I-6]
[1104] As shown in Table 8, the ratio of components A to B and the crosslinking method / conditions were changed. Otherwise, the same operation as in Example I-1 was performed to obtain the microporous membrane shown in Table 8.
[1105] [Comparative Examples I-1, I-2]
[1106] To 79.2% by mass of a homopolymer polyethylene (A) with a weight average molecular weight of 500,000, 19.8% by mass of silane-grafted polyethylene (silane-modified polyethylene (B)) with an MFR (190°C) of 0.4 g / min (obtained by modification of vinylsilane by replacing vinylsilane with trimethoxyalkylene oxide using a polyolefin with a viscosity average molecular weight of 20,000 as a raw material) was added (therefore, the resin compositions of (A) and (B) were 0.8 and 0.2, respectively), and 1% by mass of pentaerythritol-tetra-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant, a mixture was obtained by dry mixing using a drum mixer. The resulting mixture was fed into a twin-screw extruder under a nitrogen atmosphere. Additionally, liquid paraffin (kinematic viscosity at 37.78°C 7.59 × 10⁻⁶) was pumped via a plunger pump. -5m² / s) is injected into the extruder drum.
[1107] The mixture and liquid paraffin were melt-blended in an extruder. The feeder and pump were adjusted so that the liquid paraffin accounted for 70% by mass of the extruded polyolefin composition (i.e., the polymer concentration was 30% by mass). The melt-blending conditions were set at a temperature of 220°C, a screw speed of 240 rpm, and a discharge rate of 18 kg / h.
[1108] Next, the molten compound is extruded through a T-die onto a cooling roller with a surface temperature controlled at 25°C and then cast to obtain a gel sheet (sheet-shaped molded body) with a blank film thickness of 1400 μm.
[1109] Next, the sheet-shaped molded body is guided to a biaxial stretching machine for biaxial stretching to obtain the stretched material. The stretching conditions are set as follows: MD ratio 7.0, TD ratio 6.0 (i.e., 7×6), and biaxial stretching temperature 125℃.
[1110] Next, the stretched gel sheet is guided into a methyl ethyl ketone (MEK) bath and fully impregnated in MEK to extract and remove liquid paraffin. Then, it is dried to remove MEK and obtain a porous body.
[1111] Next, the porous body is guided to the TD stretcher for heat setting (HS) at a heat setting temperature of 125°C and a stretching ratio of 1.8. Then, a relaxation operation of 0.5 times in the TD direction is performed (i.e., the HS relaxation rate is 0.5 times).
[1112] Then, it is guided into an ethanol bath (affinity treatment tank), immersed and left for 60 seconds to perform affinity treatment on the heat-treated porous body, thus obtaining an affinity-treated porous body.
[1113] Furthermore, in Comparative Example I-1, the affinity-treated porous body was immersed in a 25% sodium hydroxide aqueous solution (temperature 80°C, pH 8.5-14), and in Comparative Example I-2, the affinity-treated porous body was immersed in a 10% hydrochloric acid aqueous solution (temperature 60°C, pH 1-6.5), and the bodies were immersed and held for 60 seconds to perform crosslinking treatment on the affinity-treated porous body, thereby obtaining a crosslinked porous body.
[1114] Next, the cross-linked porous body is guided into water (washing tank), immersed and held for 60 seconds to wash the cross-linked porous body. It is then guided to a conveyor dryer and dried at 120°C for 60 seconds to obtain a microporous membrane.
[1115] Then, the ends of the obtained microporous membrane are cut off and wound into a master roll with a width of 1,100 mm and a length of 5,000 m.
[1116] During the above evaluation, the microporous membrane released from the master roll is cut as needed and used as evaluation separators.
[1117] [Evaluation Results]
[1118] For the microporous membranes and batteries obtained in Examples I-1 to I-6 and Comparative Examples I-1 to I-2, various evaluations were performed according to the evaluation methods described above, and the evaluation results are shown in Table 8. Furthermore, the relationship between temperature and resistance of the battery using the microporous membrane obtained in Example I-1 as a separator is shown in Table 8. Figure 3 .Depend on Figure 3 As shown in Table 8, the shut-off temperature of the separator obtained in Example I-1 is 143°C, and the film rupture temperature is above 200°C. Furthermore, the pre-crosslinking state of the separator obtained in Example I-1... 1 H and 13 The C-NMR spectrum (b) is shown in Figure 13 .
[1119] [Table 8]
[1120]
[1121] It should be noted that "silane-modified polyethylene (B)" in Table 8 is obtained by using a polyolefin with a viscosity-average molecular weight of 20,000 as a raw material, through a modification reaction based on the substitution of vinylsilane with trimethoxyalkylene oxide, and has a density of 0.95 g / cm³. 3 Silane-modified polyethylene with a melt mass flow rate (MFR) of 0.4 g / min at 190°C.
[1122] <Experimental Group IIa>
[1123] [Manufacturing method of silane-grafted modified polyolefins]
[1124] The raw material polyolefin used in silane graft-modified polyolefins can have a viscosity-average molecular weight (Mv) of 100,000 or more and less than 1,000,000, a weight-average molecular weight (Mw) of 30,000 or more and less than 920,000, and a number-average molecular weight of 10,000 or more and less than 150,000. It can be an ethylene homopolymer or a copolymer of ethylene and propylene or butene. While the raw material polyethylene is melt-blended using an extruder, an organic peroxide (di-tert-butyl peroxide) is added. After free radicals are generated in the polymer chain of the α-olefin, trimethoxyalkylene oxide is injected to replace vinylsilane. Through an addition reaction, alkoxysilane is introduced into the α-olefin polymer to form a silane graft structure. In addition, to adjust the free radical concentration in the reaction system, an appropriate amount of antioxidant (pentaerythritol tetratetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) is added to inhibit the chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin was cooled in water, granulated, and then heated and dried at 80°C for 2 days to remove moisture or unreacted trimethoxyalkylene oxide-substituted vinylsilane. It should be noted that the residual concentration of unreacted trimethoxyalkylene oxide-substituted vinylsilane in the granules is approximately below 1500 ppm.
[1125] The silane-grafted modified polyethylene obtained by the above manufacturing method is used as "silane-modified polyethylene (B)" in Table 9.
[1126] [Example II-1]
[1127] To 80% by mass of a homopolymer polyethylene (polyethylene (A)) with a weight average molecular weight of 700,000, 20% by mass of a silane-grafted polyethylene (silane-modified polyethylene (B)) with an MFR (190°C) of 0.4 g / min (therefore, the resin compositions of (A) and (B) are 80% and 20%, respectively), and 1% by mass of pentaerythritol-tetra-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant, were dry-mixed using a drum mixer to obtain a mixture. The resulting mixture was fed into a twin-screw extruder under a nitrogen atmosphere. Additionally, liquid paraffin (kinematic viscosity at 37.78°C 7.59 × 10⁻⁶) was pumped via a plunger pump. -5 m 2 / s) is injected into the extruder drum.
[1128] The mixture and liquid paraffin were melt-blended in an extruder. The feeder and pump were adjusted so that the liquid paraffin accounted for 70% by mass of the extruded polyolefin composition (i.e., the polymer concentration was 30% by mass). The melt-blending conditions were set at a temperature of 220°C, a screw speed of 240 rpm, and a discharge rate of 18 kg / h.
[1129] Next, the molten compound is extruded through a T-die onto a cooling roller with a surface temperature controlled at 25°C and then cast to obtain a gel sheet (sheet-shaped molded body) with a blank film thickness of 1100 μm.
[1130] Next, the sheet-shaped molded body is guided to a biaxial stretching machine for biaxial stretching to obtain the stretched material. The stretching conditions are set as follows: MD ratio 7.0, TD ratio 6.2, and biaxial stretching temperature 120°C.
[1131] Next, the stretched gel sheet is guided into a dichloromethane bath and fully impregnated in dichloromethane to extract and remove liquid paraffin. Then, it is dried to remove the dichloromethane and obtain a porous body.
[1132] Next, the porous body is guided to the TD stretcher for heat setting (HS) at a heat setting temperature of 133°C and a stretch ratio of 2.1 times. Then, a relaxation operation is performed to TD 2.0 times.
[1133] Then, the ends of the obtained microporous membrane are cut off and wound into a master roll with a width of 1,100 mm and a length of 5,000 m.
[1134] During the above evaluation, the microporous membrane released from the master roll is cut as needed and used as evaluation separators.
[1135] [Examples II-2 to II-8, Comparative Examples II-1 to II-3]
[1136] As shown in Table 9, the same procedures as in Example II-1 were performed by changing the ratio of components A to B, the presence or absence of other resins (C) as additional components, the membrane properties, and the crosslinking method / conditions, to obtain the microporous membrane shown in Table 9. It should be noted that the component "PP" in Table 9 was selected based on an MFR of 2.5 g / 10 min or less and a density of 0.89 g / cm³, measured at 230°C and 2.16 kg. 3 The above refers to unmodified polypropylene with silane. Furthermore, in the crosslinking method "alkali-treated crosslinking" in Table 9, the samples were treated with a 25% sodium hydroxide aqueous solution (temperature 80°C, pH 8.5–14).
[1137] [Evaluation Results]
[1138] For the microporous membranes and batteries obtained in Examples II-1 to II-8 and Comparative Examples II-1 to II-3, various evaluations were performed according to the evaluation methods described above, and the evaluation results are shown in Table 9. Furthermore, regarding the viscoelasticity measurement of the obtained microporous membranes as separators for energy storage devices, the relationships between temperature, gap distance, energy storage modulus, and loss modulus in Example II-1 are shown in Table 9. Figure 4(a) shows the comparative example II-1. Figure 4 (b) Furthermore, the film softening transition temperatures determined based on the first derivatives of temperature, gap distance, and gap displacement in Example II-1 are shown in [the table / example]. Figure 5 (a) shows the comparative example II-1. Figure 5 (b) No membrane rupture was observed in Examples II-1 to II-8 and Comparative Example II-3 at the measurement limit temperature of 250°C. It should be noted that in Examples II-1 and Comparative Example II-1, 26 films with a thickness of 8 μm were overlapped, and the storage modulus, loss modulus, membrane softening transition temperature, and membrane rupture temperature were measured under the condition that the total film thickness of the sample was 208 μm.
[1139] [Table 9A]
[1140]
[1141] [Table 9B]
[1142]
[1143] <Experimental Series IIb>
[1144] [Standard membrane]
[1145] As a separator for energy storage devices without silane-modified polyolefin (hereinafter referred to as "standard membrane"), a silane-grafted unmodified polyolefin microporous membrane with a solid composition change rate (hereinafter referred to as "degree of gelation") of approximately 0% before and after heating in a decahydronaphthalene solution at 160°C is used. When measuring the degree of gelation, the solid composition refers only to the resin and does not include inorganic substances or other materials.
[1146] It should be noted that, in this specification, the separator for energy storage devices that does not contain silane-grafted modified polyolefins can be manufactured using any one of the following groups: polyethylene (PE):X (viscosity average molecular weight 100,000 to 400,000), PE:Y (viscosity average molecular weight 400,000 to 800,000), and PE:Z (viscosity average molecular weight 800,000 to 9,000,000), or a mixture of two or three of the following groups: X, Y, and Z, in any proportion. It should also be noted that polyolefins consisting solely of a hydrocarbon backbone, such as low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), polypropylene (PP), and olefin-based thermoplastic elastomers, can be added to the mixed composition.
[1147] Cross-linked membrane
[1148] As a separator for an energy storage device after the silane crosslinking reaction (hereinafter referred to as "crosslinked membrane"), the polyolefin microporous membrane of Example II-1 described above after contact with the electrolyte, or the polyolefin microporous membrane of Example II-1 taken from the battery after its first charge and discharge, is dried and used. The degree of gelation of the crosslinked membrane is 30% or more or 70% or more.
[1149] [Viscoelastic behavior]
[1150] The above-mentioned parameters (storage modulus, loss modulus, membrane softening transition temperature, and membrane rupture temperature (version 3)) were measured on the standard membrane and the cross-linked membrane. The results are shown in Table 10.
[1151] [Table 10]
[1152]
[1153] <Experimental Group III>
[1154] [Manufacturing method of silane-grafted modified polyolefins]
[1155] The raw material polyolefin used in silane graft-modified polyolefins can have a viscosity-average molecular weight (Mv) of 100,000 or more and less than 1,000,000, a weight-average molecular weight (Mw) of 30,000 or more and less than 920,000, and a number-average molecular weight of 10,000 or more and less than 150,000. It can also be a copolymer of propylene or butene α-olefin. While the raw material polyethylene is melt-blended using an extruder, an organic peroxide (di-tert-butyl peroxide) is added. After free radicals are generated in the α-olefin polymer chain, trimethoxyalkylene oxide is injected to replace vinylsilane. Alkoxysilane is introduced into the α-olefin polymer through an addition reaction to form a silane graft structure. In addition, to adjust the free radical concentration in the system, an appropriate amount of antioxidant (pentaerythritol tetratetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) is added to inhibit the chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin was cooled in water, granulated, and then dried at 80°C for 2 days to remove moisture or unreacted trimethoxyalkylene oxide-substituted vinylsilane. It should be noted that the residual concentration of unreacted trimethoxyalkylene oxide-substituted vinylsilane in the granules is approximately 1000–1500 ppm.
[1156] The silane-grafted modified polyolefins obtained by the above manufacturing method are referred to as "silane-modified polyethylene" in Tables 11 and 12.
[1157] [Preparation methods for modified PE and copolymers with various functional groups other than silane-modified PE]
[1158] Modified PE and copolymers with various functional groups, excluding silane-modified PE, are manufactured according to the following methods.
[1159] For any given raw material, the molecular weight (MI) is adjusted to be within the range of 0.5 to 10. Hydroxyl-modified PE is manufactured by saponifying and neutralizing EVA copolymers. Amine-modified, oxazoline-modified, and other modified resins are subjected to hydrogen peroxide conditions where a tungsten-based catalyst acts on the terminal vinyl groups of PE polymerized using a chromium catalyst, converting the vinyl groups into epoxy groups. Subsequently, a known functional group conversion organic reaction is used to convert the target reaction site into the desired functional group, yielding various modified PEs. For example, in the case of amine-modified PE, while melt-blending the epoxy-modified PE at 200°C in an extruder, a primary or secondary amine is injected in liquid form to carry out the reaction. Then, unreacted amines are removed through a pressure reducing valve, and the resulting amine-modified resin is extruded into filaments and cut into granules.
[1160] The modified PE obtained by the above manufacturing method is indicated in Tables 11 and 12 as one of "modified PE or copolymer (B)".
[1161] [Example III-1]
[1162] To 79.2% by mass of a homopolymer polyethylene (A) with a weight average molecular weight of 500,000, 19.8% by mass of silane-grafted polyethylene (PE(B)) with an MFR of 0.4 g / min (obtained by modification of vinylsilane by replacing vinylsilane with trimethoxyalkylene oxide using a polyolefin with a viscosity average molecular weight of 20,000 as a raw material, the resin compositions of (A) and (B) are 0.8 and 0.2, respectively), and 1% by mass of pentaerythritol-tetra-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant, were dry-mixed using a drum mixer to obtain a mixture. The resulting mixture was fed into a twin-screw extruder under a nitrogen atmosphere. Additionally, liquid paraffin (kinematic viscosity at 37.78°C 7.59 × 10⁻⁶) was pumped via a plunger pump. -5 m 2 / s) is injected into the extruder drum.
[1163] The mixture and liquid paraffin were melt-blended in an extruder. The feeder and pump were adjusted so that the liquid paraffin accounted for 70% by mass of the extruded polyolefin composition (i.e., the polymer concentration was 30% by mass). The melt-blending conditions were set at a temperature of 220°C, a screw speed of 240 rpm, and a discharge rate of 18 kg / h.
[1164] Next, the molten compound is extruded through a T-die onto a cooling roller with a surface temperature controlled at 25°C and then cast to obtain a gel sheet (sheet-shaped molded body) with a blank film thickness of 1400 μm.
[1165] Next, the sheet-shaped molded body is guided to a biaxial stretching machine for biaxial stretching to obtain the stretched material. The stretching conditions are set as follows: MD ratio 7.0, TD ratio 6.0 (i.e., 7×6), and biaxial stretching temperature 125℃.
[1166] Next, the stretched gel sheet is guided into a methyl ethyl ketone (MEK) bath and fully impregnated in MEK to extract and remove liquid paraffin. Then, it is dried to remove MEK and obtain a porous body.
[1167] Next, the porous body is guided to the TD stretcher for heat setting (HS) and HS is performed at a heat setting temperature of 125°C and a stretching ratio of 1.8. Then, a relaxation operation of 0.5 times in the TD direction is performed (i.e., the HS relaxation rate is 0.5 times) to obtain a microporous membrane.
[1168] Then, the ends of the obtained microporous membrane are cut off and wound into a master roll with a width of 1,100 mm and a length of 5,000 m.
[1169] During the above evaluation, the microporous membrane released from the master roll is cut as needed and used as evaluation separators.
[1170] For the evaluation separators and batteries, various evaluations were conducted according to the above evaluation methods, and the evaluation results are shown in Table 11.
[1171] [Examples III-2 to III-18]
[1172] As shown in Table 11 or Table 12, the types, ratios, and crosslinking methods / conditions of resins A and B were changed, but the same procedures as in Example III-1 were performed to obtain the microporous membranes and batteries shown in Table 11 or Table 12. Various evaluations were performed on the obtained microporous membranes and batteries according to the evaluation methods described above, and the evaluation results are also shown in Table 11 or Table 12. It should be noted that in Examples III-8 to III-10, and III-15 to III-18, electrolytes containing pre-dissolved appropriate amounts of the additives listed in Table 11 or Table 12 were used during electrolyte injection.
[1173] [Comparative Examples III-1, III-2]
[1174] As shown in Table 12, the types, ratios, and crosslinking methods / conditions of resins A and B were changed, but the same procedures as in Example III-1 were performed to obtain the microporous membrane shown in Table 12. The obtained microporous membrane was then subjected to electron beam crosslinking by irradiation with a specified dose. Various evaluations were performed on the obtained electron beam crosslinked microporous membrane and the battery according to the evaluation methods described above, and the evaluation results are also shown in Table 12.
[1175] Regarding Comparative Example III-2 and Example III-1, the strain-crystal subdivision ratio is plotted in... Figure 8 Observe the changes in X-ray crystal structure during tensile fracture test. Figure 8 In the figures, the microporous membrane of Comparative Example III-2 is represented by a dotted line as "EB crosslinking", and the microporous membrane of Example III-1 is represented by a solid line as "before chemical crosslinking" and a dashed line as "after chemical crosslinking".
[1176] [Table 11A]
[1177]
[1178] [Table 11B]
[1179]
[1180] [Table 12A]
[1181]
[1182] [Table 12B]
[1183]
[1184] Explanation of abbreviations in Tables 11 and 12
[1185] * "Silane-modified polyethylene" is obtained by using polyolefins with a viscosity-average molecular weight of 20,000 as raw materials and through a modification reaction based on the substitution of vinylsilane with trimethoxyalkylene oxides, and has a density of 0.95 g / cm³. 3 Silane-modified polyethylene with a melt mass flow rate (MFR) of 0.4 g / min at 190°C.
[1186] "-COOH modified PE", "-oxazoline modified PE", "-oxazoline, -OH modified PE", "-OH modified PE", "-OH, -NH- modified PE" and "-OH, amine modified PE" are all modified PEs obtained by the above [manufacturing methods of modified PE and copolymers with various functional groups other than silane modified PE].
[1187] ** (I) Condensation reaction of multiple identical functional groups
[1188] (II) Reactions between multiple different functional groups
[1189] (III) Chain condensation reaction between functional groups and electrolyte
[1190] (IV) Reaction of functional groups with additives
[1191] (V) Crosslinking reaction in which a plurality of identical functional groups are crosslinked via coordinate bonds with eluted metal ions
[1192] *** EC: Ethylene carbonate
[1193] **** BS(PEG)5: succinimide at both terminals, 5 repeating EO units
[1194] Diisocyanate: a compound formed by connecting isocyanate groups at both terminals to a hexane unit via urethane bonds
[1195] Diepoxide: a compound formed by connecting epoxy groups at both terminals to a butane unit
[1196] <Experimental Group IV>
[1197] [Example IV-1]
[1198] <Preparation of Layer A>
[1199] (Preparation of Silane-Grafted Modified Polyolefin)
[1200] Using polyethylene with a viscosity average molecular weight of 120,000 as the raw material polyethylene, an organic peroxide (di-tert-butyl peroxide) is added while melt-kneading the raw material polyethylene with an extruder. After generating free radicals in the polymer chain of the α-olefin, trimethoxyalkoxide-substituted vinylsilane is injected, and alkoxysilyl groups are introduced into the α-olefin polymer through an addition reaction to form a silane graft structure. In addition, an appropriate amount of antioxidant (pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) is added simultaneously to adjust the free radical concentration in the reaction system, so as to inhibit the linear chain reaction (gelation) in the α-olefin. The obtained molten silane-grafted polyolefin resin is cooled in water, pelletized, and then heated and dried at 80°C for 2 days to remove moisture or unreacted trimethoxyalkoxide-substituted vinylsilane. It should be noted that the residual concentration of unreacted trimethoxyalkoxide-substituted vinylsilane in the pellets is about 1500 ppm or less.
[1201] As described above, through the modification reaction using trimethoxyalkoxide-substituted vinylsilane, a silane-modified polyethylene with an MFR (190°C) of 0.4 g / min is obtained.
[1202] (Preparation of Layer A)
[1203] 35% by mass of the silane-modified polyethylene obtained above is blended with 65% by mass of homopolymer polyethylene having a weight average molecular weight of 800,000 to form a resin blend. 1% by mass of pentaerythritol-tetrakis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant is added to the blend, and dry blending is performed using a drum mixer, thereby obtaining a mixture. The resulting mixture is fed to a twin-screw extruder via a feeder under a nitrogen atmosphere. Further, liquid paraffin (kinematic viscosity at 37.78°C is 7.59×10 -5 m 2 / s) is injected into the extruder barrel.
[1204] The mixture and liquid paraffin are melt-kneaded in the extruder, and the feeder and pump are adjusted such that the content of liquid paraffin in the extruded polyolefin composition is 70% by mass (i.e., the polymer concentration is 30% by mass). The melt-kneading conditions are a set temperature of 220°C, a screw speed of 240 rpm and a discharge rate of 18 kg / h. Then, the melt-kneaded product is extruded through a T-die onto a cooling roll whose surface temperature is controlled at 25°C and cast, thereby obtaining a gel sheet (sheet-shaped formed body) with a raw sheet thickness of 1400 µm.
[1205] Then, the sheet-shaped formed body is guided to a simultaneous biaxial tenter stretching machine and subjected to biaxial stretching to obtain a stretched product. The stretching conditions are set as follows: a draw ratio in MD of 7.0 times, a draw ratio in TD of 6.3 times (i.e., 7×6.3 times), and a biaxial stretching temperature of 122°C.
[1206] Then, the stretched gel sheet is guided into a dichloromethane tank, fully immersed in dichloromethane to extract and remove the liquid paraffin, and then dichloromethane is removed by drying to obtain a porous body.
[1207] Then, for heat setting (HS), the porous body is guided to a TD tenter, subjected to HS at a heat setting temperature of 133°C and a draw ratio of 1.8 times, and then subjected to a relaxation operation to 1.7 times in TD, to obtain a microporous membrane.
[1208] Then, for the obtained microporous membrane, the end portions are cut off, and the membrane is wound into a master roll having a width of 1,100 mm and a length of 5,000 m.
[1209] In the above evaluation, the microporous membrane unwound from the master roll is slit as needed and used as layer A for evaluation.
[1210] For the obtained layer A for evaluation, the membrane thickness, air permeability, porosity and the like are measured, and the results are shown in Table 13.
[1211] <Preparation of Layer B>
[1212] A dispersion was prepared by uniformly dispersing 95 parts by mass of aluminum hydroxide (average particle size 1.4 μm) as inorganic particles and 0.4 parts by mass (converted to solids content) of an aqueous solution of ammonium polycarboxylate (SAN NOPCO LIMITED SNDispersant 5468, 40% solids content) as an ionic dispersant in 100 parts by mass of water. The resulting dispersion was then subjected to a bead mill (tank volume 200 cc, zirconia microspheres diameter 0.1 mm, filling rate 80%) to adjust the particle size distribution of the inorganic particles to D50 = 1.0 μm, thus producing a slurry containing inorganic particles.
[1213] Next, the microporous membrane is continuously unwound from the aforementioned microporous membrane master roll, and a slurry containing inorganic particles is coated on one side of the microporous membrane using a photogravure reverse coating machine. Then, it is dried in a 60°C dryer to remove water, and wound up to obtain the master roll of the separator.
[1214] During evaluation, the separators released from the master roll are cut as needed and used as evaluation separators.
[1215] [Examples IV-2 to IV-5, and Comparative Examples IV-1 to IV-2]
[1216] With the physical properties listed in Table 13 as the target, at least one of the following conditions of the homopolymer polyethylene was changed: weight-average molecular weight, stretching conditions, heat setting conditions, and relaxation conditions. Furthermore, the composition of layer B was changed as shown in Table 13.
[1217] Apart from these changes, the separator was manufactured using the same method as in Example IV-1, and the resulting separator was used for the above evaluation. The evaluation results are shown in Table 13.
[1218] [Table 13]
[1219]
[1220] <Experimental Group V>
[1221] [Manufacturing method of silane-grafted modified polyolefins]
[1222] The raw material polyolefin used in silane graft-modified polyolefins can have a viscosity-average molecular weight (Mv) of 100,000 or more and 1,000,000 or less, a weight-average molecular weight (Mw) of 30,000 or more and 920,000 or less, and a number-average molecular weight of 10,000 or more and 150,000 or less. It can also be a copolymer of propylene or butene into α-olefins. While the raw material polyethylene is melt-blended using an extruder, an organic peroxide (di-tert-butyl peroxide) is added. After free radicals are generated within the polymer chain of the α-olefin, trimethoxyalkylene oxide is injected to replace the vinylsilane. Through an addition reaction, alkoxysilane groups are introduced into the α-olefin polymer to form a silane graft structure. In addition, to adjust the free radical concentration in the reaction system, an appropriate amount of antioxidant (pentaerythritol tetratetra[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]) is added to inhibit the chain reaction (gelation) within the α-olefin. The obtained silane-grafted polyolefin molten resin was cooled in water, granulated, and then dried at 80°C for 2 days to remove moisture or unreacted trimethoxyalkylene oxide-substituted vinylsilane. It should be noted that the residual concentration of unreacted trimethoxyalkylene oxide-substituted vinylsilane in the granules is approximately 10–1500 ppm.
[1223] The silane-grafted modified polyolefins obtained by the above manufacturing method are used as "silane-modified polyethylene (B)" in Tables 14-16. It should be noted that the density of the silane-grafted modified polyolefin used in this study is 0.94 g / cm³. 3 And the MFR is 0.65g / min.
[1224] [Example V-1]
[1225] (Formation of microporous membranes)
[1226] To 79.2 wt% of a homopolymer polyethylene (A) with a weight average molecular weight of 500,000, 19.8 wt% of a silane-grafted polyethylene (silane-modified polyethylene (B)) with an MFR (190°C) of 0.4 g / min (obtained by modification with a polyolefin of viscosity average molecular weight of 20,000 as a raw material and by replacing vinylsilane with trimethoxyalkylene oxide) was added (therefore, the resin compositions of (A) and (B) were 80% and 20%, respectively), and 1 wt% of pentaerythritol-tetra-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant, a mixture was obtained by dry mixing using a drum mixer. The resulting mixture was fed into a twin-screw extruder under a nitrogen atmosphere. Additionally, liquid paraffin (kinematic viscosity at 37.78°C 7.59 × 10⁻⁶) was pumped via a plunger pump. -5 m 2 / s) is injected into the extruder drum.
[1227] The mixture and liquid paraffin were melt-blended in an extruder. The feeder and pump were adjusted so that the liquid paraffin accounted for 70% by weight of the extruded polyolefin composition (i.e., a polymer concentration of 30% by weight). The melt-blending conditions were set at a temperature of 220°C, a screw speed of 240 rpm, and a discharge rate of 18 kg / h.
[1228] Next, the molten compound is extruded through a T-die onto a cooling roller with a surface temperature controlled at 25°C and then cast to obtain a gel sheet (sheet-shaped molded body) with a blank film thickness of 1400 μm.
[1229] Next, the sheet-shaped molded body is guided to a biaxial stretching machine for biaxial stretching to obtain the stretched material. The stretching conditions are set as follows: MD ratio 7.0, TD ratio 6.0 (i.e., 7×6), and biaxial stretching temperature 125℃.
[1230] Next, the stretched gel sheet is guided into a methyl ethyl ketone (MEK) bath and fully impregnated in MEK to extract and remove liquid paraffin. Then, it is dried to remove MEK and obtain a porous body.
[1231] Next, the porous body is guided to the TD stretcher for heat setting (HS) and HS is performed at a heat setting temperature of 125°C and a stretching ratio of 1.8. Then, a relaxation operation of 0.5 times in the TD direction is performed (i.e., the HS relaxation rate is 0.5 times) to obtain a microporous membrane.
[1232] Then, the ends of the obtained microporous membrane are cut off and rolled into a microporous membrane master roll with a width of 1,100 mm and a length of 5,000 m.
[1233] (Manufacturing method of acrylic latex)
[1234] Acrylic latexes used as resin binders can be manufactured using the following methods.
[1235] 70.4 parts by mass of ion-exchanged water, 0.5 parts by mass of "Aquaron KH1025" (registered trademark, 25% aqueous solution manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd.) and 0.5 parts by mass of "ADEKA REASOAP SR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Co., Ltd.) as emulsifiers were added to a reaction vessel equipped with a stirrer, reflux condenser, dropping tank and thermometer. Next, the temperature inside the reaction vessel was raised to 80°C, and while maintaining the temperature at 80°C, 7.5 parts by mass of a 2% aqueous solution of ammonium persulfate was added to obtain an initial mixture. Five minutes after the addition of the ammonium persulfate aqueous solution was completed, the emulsion was added dropwise from the dropping tank to the reaction vessel over 150 minutes.
[1236] It should be noted that the above emulsion was prepared by mixing the following substances for 5 minutes using a homogenizer: 70 parts by weight of butyl acrylate; 29 parts by weight of methyl methacrylate; 1 part by weight of methacrylic acid; 3 parts by weight of "AquaronKH1025" (registered trademark, manufactured by Daiichi Kogyo Pharmaceutical Co., Ltd., 25% aqueous solution) and 3 parts by weight of "ADEKA REASOAPSR1025" (registered trademark, manufactured by ADEKA Co., Ltd., 25% aqueous solution) as emulsifiers; 7.5 parts by weight of 2% aqueous solution of ammonium persulfate; and 52 parts by weight of deionized water.
[1237] After the emulsion was added dropwise, the temperature inside the reaction vessel was maintained at 80°C for 90 minutes, and then cooled to room temperature. The resulting emulsion was adjusted to pH 8.0 with a 25% ammonium hydroxide aqueous solution, and a small amount of water was added to obtain an acrylic latex with a solid content of 40%. The number average particle size of the obtained acrylic latex was 145 nm, and the glass transition temperature was -23°C.
[1238] (Formation of inorganic porous layers)
[1239] A dispersion was prepared by uniformly dispersing 95 parts by weight of aluminum hydroxide (average particle size 1.4 μm) as inorganic particles and 0.4 parts by weight (solid content conversion) of an aqueous solution of ammonium polycarboxylate (SAN NOPCO LIMITED SNDispersant 5468, 40% solid content concentration) as an ionic dispersant in 100 parts by weight of water. The resulting dispersion was then subjected to a bead mill (tank volume 200 cc, zirconia microspheres diameter 0.1 mm, filling rate 80%) to adjust the particle size distribution of the inorganic particles to D50 = 1.0 μm. 4.6 parts by weight (solid content conversion) of an acrylic latex (40% solid content concentration, average particle size 145 nm, glass transition temperature -23 °C, monomers: butyl acrylate, methyl methacrylate, methacrylic acid) as a resin binder was added to the particle size-adjusted dispersion to prepare a slurry containing inorganic particles.
[1240] Next, the microporous membrane is continuously unwound from the aforementioned microporous membrane master roll, and a slurry containing inorganic particles is coated on one side of the microporous membrane using a photogravure reverse coating machine. Then, it is dried in a 60°C dryer to remove water, and wound up to obtain the master roll of the separator.
[1241] During evaluation, the separators released from the master roll are cut as needed and used as evaluation separators.
[1242] [Examples V-2 to V-12, Comparative Example V-2]
[1243] As shown in Tables 14-16, the ratio of components A to B, the presence or absence of the inorganic layer or its composition, and the crosslinking method / conditions were changed. Otherwise, the same operation as in Example V-1 was performed to obtain the microporous membranes shown in Tables 14-16.
[1244] [Comparative Example V-1]
[1245] To 79.2 wt% of a homopolymer polyethylene (A) with a weight average molecular weight of 500,000, 19.8 wt% of a silane-grafted polyethylene (Silane-modified polyethylene (B)) with an MFR (190°C) of 0.4 g / min (obtained by modification with a polyolefin of viscosity average molecular weight of 20,000 as a raw material and by replacing vinylsilane with trimethoxyalkylene oxide) was added (therefore, the resin compositions of (A) and (B) were 80% and 20%, respectively), and 1 wt% of pentaerythritol-tetra-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] as an antioxidant, a mixture was obtained by dry mixing using a drum mixer. The resulting mixture was fed into a twin-screw extruder under a nitrogen atmosphere. Additionally, liquid paraffin (kinematic viscosity at 37.78°C 7.59 × 10⁻⁶) was pumped via a plunger pump. - 5m² / s) is injected into the extruder drum.
[1246] The mixture and liquid paraffin were melt-blended in an extruder. The feeder and pump were adjusted so that the liquid paraffin accounted for 70% by weight of the extruded polyolefin composition (i.e., a polymer concentration of 30% by weight). The melt-blending conditions were set at a temperature of 220°C, a screw speed of 240 rpm, and a discharge rate of 18 kg / h.
[1247] Next, the molten compound is extruded through a T-die onto a cooling roller with a surface temperature controlled at 25°C and then cast to obtain a gel sheet (sheet-shaped molded body) with a blank film thickness of 1400 μm.
[1248] Next, the sheet-shaped molded body is guided to a biaxial stretching machine for biaxial stretching to obtain the stretched material. The stretching conditions are set as follows: MD ratio 7.0, TD ratio 6.0 (i.e., 7×6), and biaxial stretching temperature 125℃.
[1249] Next, the stretched gel sheet is guided into a methyl ethyl ketone (MEK) bath and fully impregnated in MEK to extract and remove liquid paraffin. Then, it is dried to remove MEK and obtain a porous body.
[1250] Next, the porous body is guided to the TD stretcher for heat setting (HS) at a heat setting temperature of 125°C and a stretching ratio of 1.8. Then, a relaxation operation of 0.5 times in the TD direction is performed (i.e., the HS relaxation rate is 0.5 times).
[1251] In Comparative Example V-1, in order to use the heat-treated porous body as a separator, the ends of the obtained porous body were cut off and wound into a master roll with a width of 1,100 mm and a length of 5,000 m.
[1252] Regarding Comparative Example V-1, during the above evaluation, the microporous membrane released from the master roll was cut as needed and used as a separator for evaluation.
[1253] [Evaluation Results]
[1254] For the microporous membranes and batteries obtained in Examples V-1 to V-12 and Comparative Examples V-1 to V-2, various evaluations were performed according to the evaluation methods described above, and the evaluation results are also shown in Tables 14 to 16.
[1255] [Table 14]
[1256]
[1257] [Table 15]
[1258]
[1259] [Table 16]
[1260]
[1261] <Experimental Group VI>
[1262] Porous membranes were formed in the same manner as Examples 1-3 and Comparative Examples 2-3 given in Patent Document 5 (Japanese Patent Application Publication No. 2001-176484), and are designated as porous membranes V-1 to V-5, respectively. For porous membranes V-1 to V-5, the gelation rate (%), heat resistance temperature (°C), and needle penetration strength (gf / 25μm) were evaluated according to the method described in Patent Document 5. Furthermore, according to the above items <storage modulus, loss modulus, and transition temperature (version 1)> in this specification, the change factor R of the storage modulus and loss modulus of porous membrane V-4 before and after contact with the electrolyte was measured. △E’ and R △E” The results are shown in Table 17.
[1263] [Table 17]
[1264]
[1265] The following points can be clarified from Table 17.
[1266] (a) Even the porous membrane V-4 with the lowest gel rate (Comparative Example 2 of Patent Document 5, gel rate 36%), the elastic modulus change factor remained unchanged at 1. Therefore, it is confirmed that the porous membranes V-1 to V-5 have all undergone complete cross-linking reaction. The porous membrane described in Patent Document 5 does not have self-cross-linking properties (uncross-linked part).
[1267] (b) In addition, Comparative Example 1 of Patent Document 5 is an unmodified silane product.
[1268] (c) The value of the separator in the seventh embodiment of the present invention described above lies in the selective chemical crosslinking of the amorphous region between the crystal and the crystalline portion. When unmodified silane polyolefin and silane-modified polyolefin form a mixed crystal, the modified unit is repelled by the amorphous portion and dispersed irregularly. In this state, the connected crosslinking units come into contact and a crosslinking reaction occurs.
[1269] On the other hand, if multiple crosslinking units are far apart from each other, they cannot contribute to the crosslinking reaction even if they are present. In particular, the crosslinking reaction from silanol to siloxane in porous membranes proceeds immediately once its (complete) reaction conditions are met, and the units that can participate in crosslinking can be fully crosslinked. Therefore, it is impossible for residual units to undergo further crosslinking within the battery, which includes the porous membrane.
[1270] Therefore, even if there are residual silanol groups in porous membranes such as porous membranes V-1 to V-5, as long as crosslinking treatment is carried out during the manufacturing process of these membranes, the crosslinking reaction in the battery containing the membrane will not occur (i.e., the residual silanol groups cannot contribute to the crosslinking structure).
[1271] (d) Regarding the separator in the seventh embodiment of the present invention, by adjusting the molecular weight of the raw material resin, copolymer concentration, mixing ratio, etc., and further combining it with the stretching and film-forming process, experiments were conducted to discover the intercrystalline distance capable of high-probability cross-linking reactions of the cross-linking units and the crystal structure with a dispersed distribution of cross-linking units. As a result, the battery's resistance to damage and heat resistance safety were successfully improved, and the degradation of battery cycle performance caused by residual heterofunctional groups was successfully suppressed.
Claims
1. A method for manufacturing an energy storage device, characterized in that, The energy storage device includes a separator for the energy storage device containing a microporous membrane of silane-modified polyolefin. No cross-linking reaction is carried out in the manufacturing process of the separator. When the separator for the energy storage device comes into contact with a non-aqueous electrolyte containing water and / or hydrogen fluoride in the manufacturing process of the energy storage device, the silane cross-linking reaction of the silane-modified polyolefin is initiated. Wherein, the silane-modified polyolefin is not a masterbatch resin containing a dehydration condensation catalyst that crosslinks the silane-modified polyolefin. The separator for the energy storage device also includes polyethylene in addition to the silane-modified polyolefin. The mass ratio of the silane-modified polyolefin to the polyethylene, i.e., the mass of the silane-modified polyolefin / mass of the polyethylene, is 0.05 / 0.95~0.40 / 0.
60.
2. The method for manufacturing the energy storage device according to claim 1, comprising the following steps: (1) Sheet forming process: The mixture of silane-modified polyolefin, polyethylene and plasticizer is extruded, cooled and solidified to form a sheet, thus obtaining a sheet; (2) Stretching process: stretching the sheet along at least one uniaxial direction to obtain a stretched material; (3) A porous body forming process, wherein the plasticizer is extracted from the stretched material in the presence of an extraction solvent, thereby porousening the stretched material to form a porous body; and (4) Heat treatment process, wherein the porous body is subjected to heat treatment.
3. The method for manufacturing an energy storage device according to claim 1 or 2, wherein an energy storage device assembly kit is used, the energy storage device assembly kit comprising the following two elements: Element 1: An outer casing housing a laminated or wound body containing separators for electrodes and energy storage devices; and Element 2: Containers containing non-aqueous electrolytes.
4. The method for manufacturing the energy storage device according to claim 3, wherein, The non-aqueous electrolyte contains a fluorine (F)-containing lithium salt.
5. The method for manufacturing the energy storage device according to claim 3, wherein, The non-aqueous electrolyte contains lithium hexafluorophosphate (LiPF6).
6. The method for manufacturing the energy storage device according to claim 3, wherein, The non-aqueous electrolyte is an acid solution and / or an alkaline solution.
7. The method for manufacturing the energy storage device according to claim 6, comprising the following steps; The process of preparing the aforementioned energy storage device assembly kit, and The process of initiating the silane crosslinking reaction of the silane-modified polyolefin is to bring the separator of the energy storage device in element 1 of the energy storage device assembly kit into contact with the non-aqueous electrolyte in element 2.
8. The method for manufacturing the energy storage device according to claim 7, further comprising the following steps: The process of connecting lead terminals to the electrode of element 1, and The process involves performing at least one charge-discharge cycle.
Citation Information
Patent Citations
Ion conductor for lithium secondary battery, and lithium secondary battery using this ion conductor
JP1998261435A
Porous membrane, battery separator comprising porous membrane, and manufacture thereof
JP1999144700A
Porous film, battery separator comprising porous film, and its production
JP1999172036A
Production of microporous resin film
JP2000319441A
Porous film
JP2001176484A